EdTech, Learning and Equity: The EdTech Hub Research Portfolio - Haßler, Björn; Wagner, Dan; Outhwaite, Laura (EdTechHub, 2023)
ZenodoArchiveID: 10079721 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1000 ZenodoArchiveConcept: 10079720
Keywords: _internal; _r:AddedByMyEducationEvidence

TCPD in Tanzania: Design-Based Implementation Research Cycle 1 Recommendations Policy Brief - Koomar, Saalim; Massam, Winston; Chachage, Kristeen; Anthony, Gervace; Mrope, Winifrida Jacob; Malibiche, Mustafa; Mutura, Emmanuel; Adam, Taskeen; Hennessy, Sara; Mtenzi, Frederick; Komba, Aneth; Mwakabungu, Fika; et al. (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or teacher continuous professional development [TCPD]) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The research project, 'The Impact of a Tech-Supported, School-Based TPD Model on Learning Outcomes in Tanzania, using Design-Based Implementation Research (DBIR)', closely aligns with the Tanzania National TCPD implementation plan, to evaluate the implementation of MEWAKA at school level. This policy brief presents a summary of the key findings and recommendations from the first cycle of the DBIR carried out between September and December 2022. Keywords: TCPD; teacher professional development; design-based implementation research; primary education; tanzania; communities of learning An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7948836 ZenodoArchiveConcept: 7948835 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7948836 10.53832/edtechhub.0166 2339240:N4CC2DD8 2405685:FICAJDR3 2405685:HUR5C9QN 2405685:XVCIV366
Keywords: _r:AddedByZotZen

Opinion: Why all research programmes should have a helpdesk - Proctor, Jamie (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org/
ZenodoArchiveID: 13694715 KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.1055 ZenodoArchiveConcept: 13694714
Keywords: _r:AddedByMyEducationEvidence

Sustainable Solutions to Rural Girls’ Education: A Rapid Evaluation of Lyra in Africa’s Green Hostels - Simmons, Hannah (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7858344 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7858344 ZenodoArchiveConcept: 7858343
Keywords: _r:AddedByZotZen

Financial sustainability of digital learning environments - Oliveira, Andre Correade; Rui, YangTingting; Upadhyay, Arjun (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7847815 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7847815 ZenodoArchiveConcept: 7847814
Keywords: _comingsoon; _r:AddedByZotZen

Decolonising EdTech: Unpacking Conceptual Frameworks. Writers Workshop 1 - Adam, Taskeen; Moustafa, Nariman (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7850804 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7850804 ZenodoArchiveConcept: 7850803
Keywords: _comingsoon; _r:AddedByZotZen

Teknolojia na maendeleo ya taaluma ya walimu nchini Tanzania: Zana za utafiti - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chacage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
Kifurushi hiki kina zana za utafiti zilizotengenezwa na EdTech Hub, Aga Khan University, na Taasisi ya Elimu Tanzania kwa ajili ya utafiti unaochunguza athari za programu ya maendeleo ya kitaaluma ya walimu kwenye matokeo ya masomo ya ngazi ya msingi. Zana zimetengenezwa na kufanyiwa majaribio makubwa katika warsha, pamoja na shuleni. Zana hizi zimetengenezwa kwa kuzingatia mifano mizuri kama vile zana ya Benki ya Dunia ya TEACH ya uchunguzi wa darasani, pamoja na miradi mingine ya utafiti ambayo timu imefanyia kazi. Tunaweka zana hizi zipatikane kwa watafiti wengine na watendaji tukitumai kuwa zitakuwa za manufaa. Zana hizi zinapatikana kwa umbizo linaloweza kuhaririwa ili wengine waweze kuhariri inavyofaa kwao.
ZenodoArchiveID: 7701270 ZenodoArchiveConcept: 7701269 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7701270 10.53832/edtechhub.0149 2405685:6V4DBZR8
Keywords: _r:AddedByZotZen

Technology and Teacher Professional Development in Tanzania: Research instruments pack - Koomar, Saalim; Massam, Winston; Jacob, Winnie; Gervace, Anthony; Adam, Taskeen; Hennessy, Sara; Chachage, Kristeen; Malibiche, Mustafa; Mutura, Emmanuel; Mtenzi, Fredrick; Mwakabungu, Fika (EdTech Hub, 2023)
This pack contains links to research instruments developed by EdTech Hub, Aga Khan University, and Tanzania Institute of Education for a study investigating the impact of a national teacher professional development programme on primary-level learning outcomes. The tools have been developed iteratively, with substantive piloting having taken place, both in workshop settings and in schools. They draw on good practice examples, such as the World Bank’s TEACH tool for classroom observation and other research projects the team have worked on. We are making these tools available to other researchers and practitioners and hope that they will prove useful. They are provided in editable format so that others can modify them as they see fit.
ZenodoArchiveID: 7691834 ZenodoArchiveConcept: 7691833 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7434218 10.5281/zenodo.7691834 10.53832/edtechhub.0148 2405685:GXM765F3
Keywords: _r:AddedByZotZen

Sustainable Solutions to Rural Girls’ Education: A Rapid Evaluation of Lyra in Tanzania - Simmons, Hannah (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7642746 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7642746 ZenodoArchiveConcept: 7642745
Keywords: _r:AddedByZotZen

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6817992 10.53832/edtechhub.0171 2405685:KAAC2B78
Keywords: _r:AddedByZotZen

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8116387 ZenodoArchiveConcept: 8116386 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8116387 10.53832/edtechhub.0172 2339240:V4SEB3GI 2405685:V8CZHW5B 2405685:ZY6RMGAF
Keywords: _r:AddedByZotZen

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521062 ZenodoArchiveConcept: 7521061 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521062 10.53832/edtechhub.0145 2405685:M3D6NGR4 2405685:WVRHTVIZ 2486141:V94NMZIU
Keywords: _r:AddedByZotZen

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7521375 ZenodoArchiveConcept: 7521374 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521375 10.53832/edtechhub.0154 2405685:AHVWDNGT
Keywords: _r:AddedByZotZen

Under the Hood of an EdTech Study in Kenya: Implementation challenges, successes, and lessons learnt - Büchel, Konstantin; Crossley, Colin; Cullen, Claire; Letsomo, Thato (EdTech Hub, 2023)
In the years following a global pandemic that left 1.6 billion learners out of school, the global learning crisis has grown more urgent. Governments worldwide have sought technology-enabled education platforms that can support higher quality, resilient education systems. One cheap and easy tool for delivering remote educational support is basic mobile phones, which represent a potentially cost-effective and remote platform for adapting a range of proven pedagogical methods. To do so successfully, programme delivery should consider three key factors that include (1) careful training on delivering pedagogical methods in a phone setting, (2) Appropriate monitoring systems to ensure weekly delivery fidelity and, (3) an appropriate data and/or delivery infrastructure to enable programme monitoring. If done successfully, mobile phone programmes can present education ministries with an efficient delivery option for quality education at a fraction of the cost of higher-tech solutions. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8370318 ZenodoArchiveConcept: 8370317 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8370318 10.53832/edtechhub.0175 2405685:XRGSHEUJ
Keywords: _r:AddedByZotZen

Teacher Continuous Professional Development in Tanzania: Lessons Learnt - Chachage, Kristeen; Thakrar, Jay (EdTech Hub, 2023)
This report shares the experience and learning from the activities carried out as part of the Government of Tanzania's efforts to operationalise its National Framework for Teacher Continuous Professional Development (TCPD), which shifts TCPD from discreet workshops to cost-effective, ongoing, school-based professional development. It is among the first of its kind at a national level, particularly in low- and middle-income country contexts. Through a collaborative and responsive approach of adaptive technical assistance and innovation, the EdTech Hub team supported Government of Tanzania partners in developing and implementing a technology-enhanced, school-based, national TCPD system. This report begins with an overview of the activities implemented and then consolidates reflection through nine lessons learnt that could help inform current and future thinking on the design, delivery, and funding of TCPD programming in Tanzania. The TCPD reflected in this report is specific to Tanzania's teaching and learning environment. While we recognise that environments can vary widely, even between countries with similar goals and objectives, the report also seeks to contribute to any current and future analyses that collate features of effective TCPD from around the world. Keywords: teacher professional development; teacher training; technology; learning management system; communities of learning; teacher needs assessment; An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7677950 ZenodoArchiveConcept: 7677949 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7677950 10.53832/edtechhub.0157 2339240:RBNTBT7Z 2405685:9WBV8KPN 2405685:EGL4QHDZ
Keywords: _r:AddedByZotZen

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7335773 ZenodoArchiveConcept: 7335772 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7299806 10.5281/zenodo.7335773 10.53832/edtechhub.0165 2339240:LJTXPKUD 2405685:4NSU75DR 2405685:ABK6ZFI8 2405685:PFKAMFI6
Keywords: _r:AddedByZotZen

School-to-School Mobility Patterns and Retention Rates of Payroll Teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alisdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone. Recent studies from this series have shown that being put on the government payroll can incentivise teachers to relocate to remote areas of the country. There is a concern, however, that being put on the payroll does not necessarily ensure the retention of teachers in these areas and that teachers will soon move to locations they consider more favourable. As there is no data on teacher mobility patterns and schools’ teacher retention rates, policies tend to be based on anecdotal evidence. This paper aims to fill this evidence gap by exploring teachers’ school-to-school mobility trends and retention rates using the Annual School Census (ASC) data from 2015 to 2021. Using data on teachers’ individual characteristics, as well as geospatial location data of each school, the paper explores whether mobility patterns vary by teachers’ gender or qualifications and whether the teaching workforce is urbanising. While studies have looked at teacher retention, this study is the first in a low-income country to use school census data to create a panel dataset to study teachers’ movements and school retention rates over time. Keywords: teacher mobility; teacher retention rates; mobility patterns; teacher deployment; Sierra Leone; education An output of the EdTech Hub https://edtechhub.org
ZenodoArchiveID: 7421516 ZenodoArchiveConcept: 7421515 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7421516 10.53832/edtechhub.0143 2405685:DE7XUSMJ 2405685:IWFRG7US 2486141:MQHWRFUH
Keywords: _r:AddedByZotZen

The National Numeracy Programme — Outputs Register - Haßler, Björn (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7581622 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7581622 ZenodoArchiveConcept: 7581621
Keywords: _r:AddedByZotZen

Outputs Register: The Impact of GIS-Supported Teacher Allocation in Sierra Leone - Haßler, Björn; McBurnie, Chris; Beoku-Betts, Iman; Frazer, Madleen Madina (EdTech Hub, 2023)
EdTech Hub, Fab Inc, and the Education Workforce Initiative have produced the outputs listed in this document as part of the EdTech Hub-commissioned research project on ‘GIS-supported teacher allocation in Sierra Leone’. This research project began in January 2022. This document lists all outputs produced under this project. All outputs are available to the public via the EdTech Hub Evidence Library. An output of the EdTech Hub, https://edtechhub.org
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6396199 10.5281/zenodo.6472492 10.53832/edtechhub.0089 10.53832/edtechhub.0163 10.53832/edtechhub.0164 2129771:3J4TNGDZ 2339240:QAKR5YM8 2405685:9XJGEX5Z 2405685:NNBEHF4D 2405685:WXBISTFE
Keywords: Author:OpenDevEd; HLR3; _C:Sierra Leone SLE; _r:AddedByZotZen

Uzoefu wa Walimu katika kufundisha kwa kutumia teknolojia nchini Tanzania Mapendekezo Juu ya Sera na Utekelezaji - Hennessy, Sara; Koomar, Saalim; Kreimeia, Adam (EdTech Hub, 2023)
This is a Swahili version of the policy brief Teachers’ Experiences of Teaching With Technology in Tanzania: Recommendations for policy and practice published in October 2022. Muhtasari huu wa masuala ya kisera unatoa ripoti ya utafiti wa walimu nchini Tanzania (Julai-Novemba 2021) ambao EdTech Hub iliagiza HakiElimu kuufanya ili kuchangia taarifa itakayosaidia mchakato endelevu wa serikali kuleta mageuzi ya MEWAKA katika ngazi za shule na vituo vya walimu. Dodoso zilichukuliwa kutoka katika uchunguzi wa kihistoria wa kimataifa uliohusisha takriban walimu 20,000+ , kuhusu uzoefu na changamoto zao katika ufikiaji na matumizi ya EdTech, ufundishaji na ujifunzaji, na maendeleo ya kitaaluma katika mwaka 2021, iliyoripotiwa na timu kutoka T4 Education na EdTech Hub. Maneno muhimu: teknolojia ya elimu; matokeo ya kujifunza; mahitaji ya mwalimu; mafunzo endelevu ya taaluma ya ualimu; sauti ya mwalimu / Kauli ya mwalimu; ufikiaji wa teknolojia An output of the EdTech Hub, https://edtechhub.org
DOI 10.53832/edtechhub.0147 ZenodoArchiveID: 7652491 ZenodoArchiveConcept: 7652490 2405685:ECXPS38I KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8363989 10.53832/edtechhub.0174 2405685:ECXPS38I 2405685:MDC3E34G
Keywords: _r:AddedByZotZen

Learners and Caregivers' Barriers and Attitudes to SMS-based Mobile Learning in Kenya: Key findings from a telephone survey - Jordan, Katy; Damani, Kalifa; Myers, Christina; Khagame, Phoebe; Mumbi, Albina; Njuguna, Lydia (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7689021 ZenodoArchiveConcept: 7689020 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7689021 10.53832/edtechhub.0162 2405685:FQV2DUEH 2405685:JV87UGDX
Keywords: _r:AddedByZotZen

Randomised Controlled Trial Protocol: Digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms - Major, Louis; Daltry, Rebecca; Otieno, Mary; Otieno, Kevin; Zhao, Annette; Hinks, Jessica; Sun, Chen; Friedburg, Aidan (EdTech Hub, 2023)
This protocol provides a detailed overview of a cluster-randomised controlled trial (RCT) being undertaken in pre-primary schools in Kenya. The RCT seeks to rigorously investigate the impact of a classroom-integrated digital personalised learning (DPL) tool on early grade numeracy and literacy learning outcomes. The protocol is being disseminated prior to endline data analysis to promote transparency and a comprehensive understanding of the RCT approach and design. This protocol was originally published in October 2023. This is an updated version where we have a) clarified that the sample size stated in Sections 2 and 2.2 is the 'pre-attrition' sample; and b) added a paragraph to Section 2.4.1 to provide further clarification regarding the use of code-switching. No changes to the analytical approach have been made. Keywords: digital personalised learning; DPL; Randomised controlled trial; RCT; research methodology; learning outcomes; Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8354887 ZenodoArchiveConcept: 8354886 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8354887 10.53832/edtechhub.0176 2405685:JNH4277Z
Keywords: _r:AddedByZotZen

Learning Continuity in Response to Climate Emergencies: Pakistan's 2022 floods - Mazari, Haani; Baloch, Imdad; Thinley, Sangay; Radford, Kate; Kaye, Tom; Perry, Freya (EdTech Hub, 2023)
Building on EdTech Hub's preliminary insights, this extended resource explores Learning continuity in response to climate emergencies following the 2022 Pakistan floods. The intention is to support stakeholders in identifying scalable and feasible ways of using EdTech in response to Pakistan’s 2022 floods and improving learning responses in future climate emergencies. We identified these approaches by interviewing flood-affected parents and teachers, government education officers, development partners, local NGOs, and international experts in education in emergencies. We find that during the different phases of response to the emergency, communities’ needs and infrastructural realities keep changing. However, existing responses to support learning have not been able to address these needs at scale. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7334016 ZenodoArchiveConcept: 7334015 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7334016 10.5281/zenodo.7716210 10.53832/edtechhub.0135 2339240:JDMXQUFN 2405685:42XI4RCK 2405685:EQ454TF3 2405685:QEMBQCJ6 2405685:ZXRRJ5S6
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7074857 ZenodoArchiveConcept: 7074856 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6326179 10.5281/zenodo.7074857 10.53832/edtechhub.0114 2405685:K5BJUBRE 2405685:REW8F5TJ 2405685:U6G7C62D
Keywords: _r:AddedByZotZen

Raising Readers: Can mobile technology enable Kenyan schools to improve parent and carer engagement in reading with their children? - Nicolai, Susan; Khan, Amina; Kartha, Ashwati; Bapna, Akanksha; Kamninga, Tony (EdTech Hub, 2023)
Deploying design-based, mixed-methods research, the study Raising Readers (Phase 1) explores how technology can be best used to strengthen parent and carer engagement with children’s reading in Kenya. In close collaboration with Worldreader, a digital reading organisation, five co-designed modalities (parental training, feedback loops, nudges/messaging, incentives, and reading celebrations) were tested in 14 schools across Nairobi and Kiambu counties over 12 weeks in 2022. The intervention helped to assess the potential of the different modalities in facilitating parental/carer engagement around children’s reading using the BookSmart app. As measured by average reading time, intervention groups showed higher engagement using BookSmart than the control group. ‘Incentives’ led with 39 hours 29 minutes average reading time per school over 12 weeks, followed by ‘reading celebrations’ with 24 hours 13 minutes. ‘Feedback loops’ and ‘training’ had comparable levels (10 hours, 28 minutes, and 9 hours, 27 minutes per school, respectively). ‘Messaging / nudges’ had the lowest engagement (5 hours 57 minutes versus 3 hours 2 minutes in the control group). Parental/carer knowledge, attitudes, and practices supporting their child's reading improved with the interventions. Findings of Phase 1 were used to inform the design of Phase 2. Keywords: Education, app, reading, school, child, Kenya An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8208265 ZenodoArchiveConcept: 8208264 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.8208265 10.53832/edtechhub.0057 10.53832/edtechhub.0173 2405685:47KMRR48 2405685:N2E79MUD
Keywords: _r:AddedByZotZen

The Use of Technology to Promote Equity and Inclusion in Education in North and Northeast Kenya - Otieno, Jennifer; Kaye, Tom; Mbugua, Wanjiku (EdTech Hub, 2023)
Kenya has been lauded as having one of the most progressive and effective education systems in Africa. Significant investments in education funding, innovative technology-enabled approaches to improve teaching and learning, and committed leadership make Kenya an example for neighbours and others across the world. However, at a sub-national level, significant variances in education access and quality arise. While many improvements have been made to participation, quality, equity, and inclusion in education in Kenya, there are persistent disparities in access and outcomes for rural learners, girls, learners with disabilities, and other vulnerable populations. The North and Northeastern (N/NE) counties of Kenya are where some of the greatest disparities exist. Our research examines the context of N/NE Kenya to understand why these disparities exist, and how technology can play a role in increasing equity and inclusion in education in the region. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7781293 ZenodoArchiveConcept: 7781292 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7781293 10.53832/edtechhub.0159 2405685:GS45WQWR
Keywords: _r:AddedByZotZen

Using evidence in practice when there is high uncertainty on what works - Rahman, Asad; Simpson, Lea; Wilkinson, James; Kuria, Catherine; Kably, Nathan; Plaut, Daniel; Tanweer, Rabia; Mbugua, Ciku (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7645994 ZenodoArchiveConcept: 7645993 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7645994 10.53832/edtechhub.0158 2405685:8VUZEK29
Keywords: _r:AddedByZotZen

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 6980271 ZenodoArchiveConcept: 6980270 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6980271 10.53832/edtechhub.0109 2405685:HPWRQP7M
Keywords: _r:AddedByZotZen

Bringing Digital Learning to Rural Schools: A Rapid Evaluation of Lyra in Africa - Simmons, Hannah (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 8391601 ZenodoArchiveConcept: 8391600 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7857255 10.5281/zenodo.8391601
Keywords: _r:AddedByZotZen

Exploring the Relationship Between Teachers’ Use of Technology During the Covid-19 Pandemic in India and Their Perspectives on Students’ Motivation to Learn - Tailor, Kavita; Hennessy, Sara; Jordan, Katy (EdTech Hub, 2023)
During the Covid-19 pandemic, a wealth of research emerged to quantify student learning and the accessibility of technology for learners. However, existing evidence highlights that access to technology did not equate to learning, yet few studies have investigated the underlying reasons behind this. As a correlating factor of learning achievement, this report investigates student motivation to learn, as perceived by teachers, and how this may have been influenced by their use of remote technologies during the pandemic. It elucidates the perspectives of teachers working remotely during the pandemic by presenting a secondary data analysis using the world’s largest teacher survey post-Covid-19 (the T4 teacher survey). It complements these findings with qualitative data gathered from eight teachers and education practitioners in India via an online focus group. Results from this study imply that teachers’ pedagogy was more important for student learning motivation than their use of technology and confirmed that more frequent interaction between teachers and students or parents can increase teacher perceptions of student learning motivation. Findings also suggest that student learning motivation may have significantly depended on the continued development of academic and socio-emotional skills. These findings have practical implications for improving remote learning and blended learning environments and for addressing the salient issue of rote learning in India. Keywords: student motivation, technology, learning loss, Covid-19, digital pedagogy, self-determination theory An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7373033 ZenodoArchiveConcept: 7373032 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7373033 10.53832/edtechhub.0144 2405685:499UU2BN 2405685:D7VXZW6I
Keywords: _r:AddedByZotZen

Testing EdTech Interventions in Bandarban: Key Findings from the EdTech Hub Sandbox - Tanweer, Rabia; Plaut, Daniel; Datta, Rupa; Nashtaran, Trishia; Rahman, Asad; Ahmed, Shakil; Fazly, BMRabbi; Hoque, Rashedul; Moon, NurunNahar; Afroze, Sadia (EdTech Hub, 2023)
The Covid-19 pandemic has catalysed the need for technology-enhanced education globally. This is no different in Bangladesh, where the Education Section of the UNICEF Bangladesh Country Office is seeking a better understanding of the role and potential of EdTech to improve numeracy skills among the most marginalised learners. In efforts to do this, UNICEF Bangladesh partnered with EdTech Hub to in which EdTech interventions contribute the most to numeracy learning for marginalised learners in Bangladesh. This was explored through a sandbox in Bandarban, a remote region in South-Eastern Bangladesh. This report synthesises the evidence generated from this EdTech Hub sandbox. While further research is needed, its findings suggest that multimedia classrooms, which were found to be present and functioning in most schools in the region, are a promising intervention. Their effectiveness and implementation are worthwhile avenues for further research. Keywords: Bangladesh, Low connectivity/electricity, rural, marginalised learners, blended learning, tablets An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7591685 ZenodoArchiveConcept: 7591684 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7591685 10.53832/edtechhub.0146 2405685:J8IB7LVG 2405685:V4EVQ39I
Keywords: _r:AddedByZotZen

Building an Acceptable Use Policy - Tanweer, Rabia; Wyss, Natalie (EdTech Hub, 2023)
Acceptable use policies (AUPs) aim to define how digital and technological tools and services (both devices and ICT services) should be used in or by education systems and actors. These policies address the rights, privileges, responsibilities, and ramifications associated with the use of technology in education spaces and for educational purposes. In doing so, AUPs attempt to promote good practice and responsible, safe use of the internet and digital technologies. This brief uses global examples of AUP policies and guidance on the development of AUPs to outline best practices and key considerations for the development of AUPs. Keywords: EdTech usage; acceptable use policy; tablets; laptops; desktop computers; EdTech hardware; EdTech software. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7754059 ZenodoArchiveConcept: 7754058 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7521858 10.5281/zenodo.7754059 10.53832/edtechhub.0161 2405685:6E2WK46K
Keywords: _r:AddedByZotZen

School mapping and decision-making - Vijil-Morin, Alejandra; Godwin, Katie; Ramirez, Ana; Mackintosh, Alasdair; Haßler, Björn (GEM Report UNESCO, 2023)
Reliable and timely data is essential for decision-makers at all administrative levels to ensure inclusive, equitable, and quality education for all. Geospatial data has the potential to provide valuable insights across a range of areas of interest to the education sector, from identifying potential threats to schools and the education community, such as throughdata on natural disaster patterns, to supporting equitable allocation of resources based on data showing the remoteness of schools. However, the use of Geographic Information Systems (GIS) is not widespread in the education sector. In this paper, we shed light on the experiences of five country governments, one regional agency, one international initiative, one implementing partner and one private entity, all using GIS for education decision-making in Latin America, the Caribbean, and sub-Saharan Africa.This paper presents the findings from primary data collection and analysis of interviews with representatives from these organisations from August –December 2022. Across these countries, we identified two central applications of school geospatial data, which included education planning -which school mapping is a part of -and cross-sector coordination. Among the main challenges to effectively using school geospatial data to make decisions, we found significant issues with capacity building, funding, bridging the data, and policymaking. On the other hand, when school mapping was used effectively, it helped increase transparency and equity, intersectoral collaboration, cost-effectiveness, and accuracy and reliability. After comparing the seven cases, we concluded that two key enablers need to be in place to promote the impact of geospatial data on educational decision-making: ‘usability’ and ‘availability and openness’.
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7346673 10.54676/EJZH8821 2405685:7GYKP2XC 2405685:BUDHW7MW
Keywords: _r:AddedByZotZen

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
oldDOI: 10.5281/zenodo.6498098 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.6498098 10.5281/zenodo.7716253 10.53832/edtechhub.0082 10.53832/edtechhub.0170 2339240:7MIS2I79 2405685:MS3CKE8G 2405685:T3F6DCHP 2405685:UJWVTSCK
Keywords: _r:AddedByZotZen

Conceptual modeling: Topics, themes, and technology trends - Storey, Veda C.; Lukyanenko, Roman; Castellanos, Arturo (ACM Computing Surveys, 2023)
Conceptual modeling is an important part of information systems development and use that involves identifying and representing relevant aspects of reality. Although the past decades have experienced continuous digitalization of services and products that impact business and society, conceptual modeling efforts are still required to support new technologies as they emerge. This paper surveys research on conceptual modeling over the past five decades and shows how its topics and trends continue to evolve to accommodate emerging technologies, while remaining grounded in basic constructs. We survey over 5,300 papers that address conceptual modeling topics from the 1970s to the present, which are collected from 35 multidisciplinary journals and conferences, and use them as the basis from which to analyze the progression of conceptual modeling. The important role that conceptual modeling should play in our evolving digital world is discussed, and future research directions proposed.
KerkoCite.ItemAlsoKnownAs: 10.1145/3589338 2405685:I4MW7HVE 2486141:DE5MJL8K
Keywords: _Added-ailr-2024

Adapting to tech winter: Strategies for resilience in the dynamic tech industry - Akbar, Fitra (Bootcamp, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:3SZPGNJB 2405685:2VZZ98TD

Why states can’t access N64bn UBEC fund – NGF - Zakariyau, Abdulrahman (Punch Newspapers, 2023)
The Nigeria Governors’ Forum has called for a review of the Universal Basic Education Commission Act to reduce the out-of-school children.
KerkoCite.ItemAlsoKnownAs: 2339240:I9G6DLYZ 2405685:9BV2SKAS

paperdigest (AI-Powered Research Platform) (Paper Digest, 2023)
Based in New York, we serve users from thousands of universities & companies on search, review, text rewriting and more.
KerkoCite.ItemAlsoKnownAs: 2405685:W9ZJSRE6 2486141:P4Y6JGVW

Learners and caregivers barriers and attitudes to SMS-based mobile learning in Kenya - Jordan, Katy; Damani, Kalifa; Myers, Christina; Mumbi, Albina; Khagame, Phoebe; Njuguna, Lydia (African Educational Research Journal, 2023)
The use of mobile phones has been identified as a potential way to bring the benefits of educational technology to a wider audience, including in low-connectivity settings. This is a topic that has received renewed interest recently as a result of the COVID-19 pandemic and school closures. While a number of recent studies have demonstrated good potential for mobile phones and SMS to be used to support learning, there are also questions about how equitable this medium is in practice. We conducted a telephone survey with learners (n = 122) and their caregivers (n = 124) who use M-Shule, an SMS-based educational platform in Kenya, in order to understand their attitudes towards mobile learning, and the benefits and constraints. In particular, we consider whether there are differences in responses according to gender and/or location, to shed light on whether use is equitable. We find that girls and boys face similar barriers to use, and the technology is perceived to be equally beneficial. We identify some areas for potential further support for all learners through mobile learning.
KerkoCite.ItemAlsoKnownAs: 10.30918/AERJ.114.23.088 2405685:6BR2KK45

Assessing Digital and Financial Literacy in Timor-Leste: A Survey on Knowledge, Skills and Access - United Nations Capital Development Fund Pacific Office (UNCDF, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:GLLHJNMP 2405685:NPEGNI5T
Keywords: ⛔ No INSPIRE recid found

Fixing Ed-Tech’s Investment Model - Labun, Jakub (Stanford Social Innovation Review, 2023)
The sector currently suffers from a version of the classic “lemons problem.”
KerkoCite.ItemAlsoKnownAs: 10.48558/epwa-p379 2339240:YQMY8XW7 2405685:S63AQTR6

ChatGPT Pricing: How Much Does ChatGPT Cost? - Drapkin, Aaron (Tech.co, 2023)
ChatGPT has lots of different plans, models and services. But how much do they actually cost? We take a closer look.
KerkoCite.ItemAlsoKnownAs: 2405685:AN26LXEA 2486141:XCIX2SMK

Vietnam Digital Transformation Agenda - OpenDevelopment Vietnam (2023)
Vietnam is pushing toward Industry 4.0 with the government's Digital Transformation Agenda (DTA) to leverage digital technologies to drive economic growth, improve governance, and promote social development. Digital transformation is being promoted as the key to unlocking the country's two primary development goals: achieving net zero carbon emission by 2050 and becoming a high-income country
KerkoCite.ItemAlsoKnownAs: 2339240:JEZF39C7 2405685:Y3DTWWS5

AI's climate impact goes beyond its emissions - Coleman, Jude (Scientific American, 2023)
To understand how AI is contributing to climate change, look at the way it’s being used
KerkoCite.ItemAlsoKnownAs: 2405685:Z9G6569K

Digital competencies and the 21 century skills of university teachers in Nigeria - Ogunbodede, Kolawole Francis; Ewata, Thompson O.; Kumar, Amit; Okediji, Oyekanmi Gabriel (European Journal of Interactive Multimedia and Education, 2023)
The study examined university teachers’ digital literacy in Nigeria’s south-south geopolitical region. The descriptive survey approach was used, and three research questions served as the study’s direction. Data were gathered via an online questionnaire. SPSS version 23 was used to calculate the mean and standard deviation after frequency counts and simple percentages were used to evaluate the data while the independent t-test was used to test the hypothesis. The online survey was distributed to 200 faculty members, and 91 of them fill it out, yielding a 46% response rate. The sample for the study consisted of 91 lecturers who answered the online survey. Two measurement and evaluation specialists and two experts in digital technology evaluated the questionnaire. Cronbach’s alpha was employed to determine the instrument’s dependability, and the result was 0.74. The results showed that university lecturers possess high levels of both fundamental and multidimensional digital competence. The survey found that among the difficulties experienced by university teachers in acquiring digital skills were a lack of opportunity for information and communication technology (ICT) training, the high cost of ICT literacy training, inadequate ICT facilities, and a lack of sponsorship. Lastly, the outcome of the hypothesis test indicates that there is no statistically substantial difference in the levels of digital competence between male and female university lecturers. Based on their findings, the researchers suggested that university administrators set up digital skills training for university faculty members as well as assistance and incentives to promote development of digital abilities. The government should be dedicated to education overall by investing adequate finances for teacher training, infrastructural development, and enhanced welfare programs to deliver excellent university education in this digital era.
KerkoCite.ItemAlsoKnownAs: 10.30935/ejimed/13966 2339240:5ECG87D3 2405685:BMLZCI77

Making preschool STEM education accessible, affordable in Vietnam - HundrEd (2023)
KidsEdu is Vietnam's first preschool STEM curriculum validated by STEM.org. It aims to bring digital literacy to millions of preschool children, with focus on computational thinking and robotics. KidsEdu makes it possible to deliver preschool STEM program at fee as low as USD 3.5/student/month, by: localizing curriculum; sponsoring STEM labs; supporting preschool STEM teacher development.
KerkoCite.ItemAlsoKnownAs: 2339240:FI57USH2 2405685:T2CIKIN7

Foreign aid surges due to spending on refugees and aid for Ukraine - OECD (OECD, 2023)
Foreign aid from official donors in 2022 rose to an all-time high of USD 204 billion, up from USD 186 billion in 2021, as developed countries increased their spending on processing and hosting refugees and on aid to Ukraine, according to preliminary data collected by the OECD.
KerkoCite.ItemAlsoKnownAs: 2339240:63WVQCM5 2405685:E6VWTZWU

Implementing educational technology in Higher Education Institutions: A review of technologies, stakeholder perceptions, frameworks and metrics - Chugh, Ritesh; Turnbull, Darren; Cowling, Michael A.; Vanderburg, Robert; Vanderburg, Michelle A. (Education and Information Technologies, 2023)
In a world driven by constant change and innovation, Higher Education Institutions (HEIs) are undergoing a rapid transformation, often driven by external factors such as emerging technologies. One of the key drivers affecting the design and development of educational delivery mechanisms in HEIs is the fast pace of educational technology development which not only impacts an institution’s technical capacity to infuse hardware and software solutions into existing learning infrastructure but also has implications for pedagogical practice, stakeholder acceptance of new technology, and HEI administrative structures. However, little is known about the implementation of contemporary educational technology in HEI environments, particularly as they relate to competing stakeholder perceptions of technology effectiveness in course delivery and knowledge acquisition. This review fills that gap by exploring the evidence and analyses of 46 empirical research studies focussing on technology implementation issues in a diverse range of institutional contexts, subject areas, technologies, and stakeholder profiles. This study found that the dynamic interplay of educational technology characteristics, stakeholder perceptions on the effectiveness of technology integration decisions, theoretical frameworks and models relevant to technology integration in pedagogical practices, and metrics to gauge post-implementation success are critical dimensions to creating viable pathways to effective educational technology implementation. To that end, this study proposes a framework to guide the development of sound implementation strategies that incorporates five dimensions: technology, stakeholder perceptions, academic discipline, success metrics, and theoretical frameworks. This study will benefit HEI decision-makers responsible for re-engineering complex course delivery systems to accommodate the infusion of new technologies and pedagogies in ways that will maximise their utility to students and faculty.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-023-11846-x 2339240:NSN58M2M 2405685:PF6THKHJ

EdTech Quality Frameworks and Standards Review - Foster, Dina; McLemore, Caitlin; Olzeweski, Brandon; Chaudhry, Ali; Cooper, Ekaterina; Forcier, Laurie; Luckin, Rose (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:V5GYGL6B 2405685:ZNZZJVWB
Keywords: ⛔ No DOI found

Technology in Education: A Case Study on Viet Nam - Le, Anh Vinh; Luong, Minh Phuong; Do, Duc Lan; Tran, My Ngoc; Bui, Thi Dien (Global Education Monitoring Report Team and Viet Nam National Institute of Educational Sciences, 2023)
KerkoCite.ItemAlsoKnownAs: 10.54676/GPDF6007 2339240:EJZELGYX 2405685:ZU8DYU3K

Integrating ICT for teaching and learning in selected SEAMEO countries - UNESCO Global Education Monitoring Report Team; SEAMEO Regional Centre for STEM Education (STEM-ED) (SEAMEO Regional Centre for STEM Education (STEM-ED), 2023)
KerkoCite.ItemAlsoKnownAs: 10.54676/BBIC8850 2339240:QG2BQRH5 2405685:KXKEERFU

Technology and Open and Distance Learning - UNESCO Global Education Monitoring Report Team; SEAMEO Regional Open Learning Centre (SEAMOLEC) (GEM Report UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 10.54676/XZAZ1743 2339240:VZQYJYU4 2405685:5BS7XGUT

Artificial intelligence in education unplugged: A new era for the underserved - da Silva, Thomaz Edson Veloso (eLearning Industry, 2023)
This opinion piece explores the potential of AIED Unplugged for underserved communities, particularly in the global south.
KerkoCite.ItemAlsoKnownAs: 2405685:RV965VYQ

Digital Education Action Plan (2021-2027) - European Education Area - European Commission (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:GBPGATMQ 2405685:9P3LIND6

Effectiveness of technology-based interventions for school-age children with attention-deficit/hyperactivity disorder: Systematic review and meta-analysis of randomized controlled trials - Wong, Ka Po; Qin, Jing; Xie, Yao Jie; Zhang, Bohan (JMIR Ment Health, 2023)
Background: Attention-deficit/hyperactivity disorder (ADHD) is relatively common among school-age children. Technology-based interventions, such as computer-assisted training programs, neurofeedback training, and virtual reality, show promise in regulating the behaviors and cognitive functions of children with ADHD. An increasing number of randomized controlled trials have been conducted to evaluate the effectiveness of these technologies in improving the conditions of children with ADHD. Objective: This study aims to conduct a systematic review of technological interventions for school-age children with ADHD and perform a meta-analysis of the outcomes of technology-based interventions. Methods: A total of 19 randomized controlled studies involving 1843 participants were selected from a pool of 2404 articles across 7 electronic databases spanning from their inception to April 2022. ADHD behaviors, cognitive functions, learning ability, and quality of life were addressed in this study. Results: Random effects meta-analyses found that children with ADHD receiving technology-based intervention showed small and significant effect sizes in computer-rated inattention (standardized mean difference [SMD] −0.35; P<.04), parent-rated overall executive function measured by the Behavior Rating Inventory of Executive Function (SMD −0.35; P<.04), parent-rated disruptive behavior disorder measured by the Child Behavior Checklist (SMD −0.50; P<.001) and Disruptive Behavior Disorder Rating Scale (SMD −0.31; P<.02), and computer-rated visual attention measured by the Continuous Performance Test (SMD −0.42; P<.001) and Reaction Time (SMD −0.43; P<.02). Conclusions: Technology-based interventions are promising treatments for improving certain ADHD behaviors and cognitive functions among school-age children with ADHD. Trial Registration: PROSPERO CRD42023446924; https://tinyurl.com/7ee5t24n
KerkoCite.ItemAlsoKnownAs: 10.2196/51459 2339240:CIVEFIIJ 2405685:PJV9TAVU
Keywords: ADHD; attention-deficit/hyperactivity disorder; cognitive functions; computer-assisted training program; neurofeedback training; school-age children; virtual reality

ChatGPT Pricing, Explained: Plus & Tokens (2024) - Ch, David (Guides.ai, 2023)
ChatGPT Plus costs $20 per month ($23.80/month for EU + UK). The ChatGPT API costs $0.002 for every 1000 tokens.
KerkoCite.ItemAlsoKnownAs: 2405685:YISLU5WQ 2486141:5D3R2MC3

Achieving Impact, Advancing Research, and Leveraging Results - Cook, Kristin (Sesame Workshop, 2023)
Reflecting on Ahlan Simsim’s Fifth Year

A review of the Nigeria data protection act 2023 - Eke, Sandra; Okoro, Franklin; Abdulsalam, Maryam; Idorenyin, Ekpenyong (Mondaq, 2023)
Mondaq Award Winner - In an increasingly interconnected and data-driven world, the protection of personal information has become a matter of paramount importance. Individuals and organizations alike...
KerkoCite.ItemAlsoKnownAs: 2405685:UB372UW3

Making Teacher Policy Work - World Bank (World Bank Group, 2023)
Making Teacher Policy Work (English)
KerkoCite.ItemAlsoKnownAs: 2339240:JJX4HP9E 2405685:FHQTPVFS

Making Teacher Policy Work - World Bank (World Bank Group, 2023)
Making Teacher Policy Work (English)
KerkoCite.ItemAlsoKnownAs: 2339240:JJX4HP9E 2405685:FHQTPVFS

A systems thinking approach to e-learning on climate change: Capacity-building for junior high school teachers in the Philippines - Ignacio, John Trixstan Santos; Gonzales, Charlotte Kendra Gotangco; Lee-Chua, Queena (International Journal of Disaster Resilience in the Built Environment, 2023)
A mixed-method study was performed to determine the impact of integrating systems thinking (ST) into an electronic learning module for junior high school teachers in the Philippines. The study aims to assess how an ST approach to pedagogy compared against a conventional approach in terms of contribution to the participants’ global climate change content knowledge, holistic thinking and depth and accuracy of knowledge and reasoning.,The study implemented e-learning modules using an ST approach versus a conventional approach in teaching climate science to junior high school teachers. The paper presents quantitative data obtained from pre and posttests results of the 20 teacher-participants and qualitative data obtained during the focus-group discussion (FGD) after the implementation of the study.,The results from the statistical analysis indicated that the ST group obtained a significant increase in their assessment scores compared to the non-ST group, according to predetermined criteria. Content knowledge, depth and accuracy of knowledge and reasoning increased the most. The participants mentioned during the FGD that the module helped deepen their understanding of climate change.,The study was limited to 20 teacher-participants, but it has relevance for public school teachers in the country given that participants had raised concerns regarding the lack of training in their schools for teaching climate science. They admitted that they lacked critical information to include in climate change topics in their classes.,This paper shows how the ST approach can be used to teach climate change to junior high students. The e-learning module can provide teachers with better understanding, knowledge and reasoning to teach climate change to high school students more effectively.
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/IJDRBE-02-2023-0022 2339240:3D9RVHFE 2405685:I6Q5NPMF

Reviews and reviewing: Approaches to research synthesis. An annual review of information science and technology (ARIST) paper - Smith, Linda C. (Journal of the Association for Information Science and Technology, 2023)
Abstract Reviews have long been recognized as among the most important forms of scientific communication. The rapid growth of the primary literature has further increased the need for reviews to distill and interpret the literature. This review on Reviews and Reviewing: Approaches to Research Synthesis encompasses the evolution of the review literature, taxonomy of review literature, uses and users of reviews, the process of preparing reviews, assessment of review quality and impact, the impact of information technology on the preparation of reviews, and research opportunities for information science related to reviews and reviewing. In addition to providing a synthesis of prior research, this review seeks to identify gaps in the published research and to suggest possible future research directions.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/asi.24851 KerkoCite.ItemAlsoKnownAs: 10.1002/asi.24851 2405685:32NYSPUF 2486141:A9F7UUQ3 2486141:MWWYUBP8
Keywords: _Added-ailr-2024

The creation of a nudging protocol to support online student engagement in higher education - Brown, Alice; Lawrence, Jill; Basson, Marita; Axelsen, Megan; Redmond, Petrea; Turner, Joanna; Maloney, Suzanne; Galligan, Linda (Active Learning in Higher Education, 2023)
Combining nudge theory with learning analytics, ‘nudge analytics’, is a relatively recent phenomenon in the educational context. Used, for example, to address such issues as concerns with student (dis)engagement, nudging students to take certain action or to change a behaviour towards active learning, can make a difference. However, knowing who to nudge, how to nudge or when to nudge can be a challenge. Providing students with strategic, sensitive nudges that help to move them forward is almost an art form. It requires not only technical skills to use appropriate software and interpret data, but careful consideration of what to say and how to say it. In this article a nudge protocol is presented that can be used in online courses to encourage student engagement with key course resources that are integral to supporting their learning.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.1177/14697874211039077 2339240:UIHACPNQ 2405685:VQ794IWE

Nigeria: Commission to Integrate Almajiri, Out-of-School Children System - Olugbemi, Adeniyi (Leadership, 2023)
Minister of state for education, Dr Yusuf Tanko Sununu, has said the federal government will soon integrate the over 10 million Almajirai and out-of-school children, with the establishment of National Commission for Almajirai and Out-of-School Children. He said this is with a view to teaching them skills to make them self-reliant.
KerkoCite.ItemAlsoKnownAs: 2339240:YNSSEEHZ 2405685:QAI3CDGM
Keywords: Education; Nigeria; West Africa

AI language tools risk scientific diversity and innovation - Nakadai, Ryosuke; Nakawake, Yo; Shibasaki, Shota (Nature Human Behaviour, 2023)
Number: 11 Publisher: Nature Publishing Group KerkoCite.ItemAlsoKnownAs: 10.1038/s41562-023-01652-3 2405685:QIX9ZW5M 2486141:LHWYJQUZ
Keywords: Cultural evolution; Scientific community

bwallace/abstrackr-web - Wallace, Byron (2023)
web-based citation screening tool
original-date: 2010-11-23T17:57:59Z KerkoCite.ItemAlsoKnownAs: 2405685:E5ERD9TQ 2486141:AQSINRND

Perplexity AI: Review, Advantages & Guide (2023) - Aayush (Elegant Themes Blog, 2023)
AI assistants are changing how we interact with technology, helping us with tasks like answering questions and creating content. Google and Bing have already added AI like Bard and Bing Chat to their platforms. However, there’s a new player in the market: Perplexity AI. In this post, we will look at Perplexity AI and its […]
KerkoCite.ItemAlsoKnownAs: 2405685:YMCJBWYJ 2486141:7S6I2AFZ

Seeking sustainable solutions in refugee education: Who pays? - Naylor, Ruth Naylor (The Education and Development Forum (UKFIET), 2023)
Inclusion of refugees in national education systems is seen by UNHCR, and many others, as the most sustainable solution for protecting refugees’ right to education. But when a low-income country is…
KerkoCite.ItemAlsoKnownAs: 2339240:5CJVJIRA 2405685:4D7FIFXC

When public policy ‘fails’ and venture capital ‘saves’ education: Edtech investors as economic and political actors - Komljenovic, Janja; Williamson, Ben; Eynon, Rebecca; Davies, Huw C. (Globalisation, Societies and Education, 2023)
Educational technology (Edtech) investors have become increasingly influential in education; however, they remain under-researched. We address this deficit and introduce the grammar and landscape of Edtech investment into education research. We empirically examine venture capital Edtech investors and argue that they are economic and political actors. Investors construct the Edtech industry through their investment and advancing particular imaginaries. They legitimate their authority in education through narratives of expertise and measures of social impact. They consolidate the Edtech industry by constructing social networks to perform the political work of futuring. The analysis provides original insights into the power of Edtech investors in education and proposes a research agenda examining new relations between the education, technology, and finance industries.
Publisher: Routledge _eprint: https://doi.org/10.1080/14767724.2023.2272134 KerkoCite.ItemAlsoKnownAs: 10.1080/14767724.2023.2272134 2339240:HGYZ37KG 2405685:RYXRH7ZR
Keywords: Education technology; Futures; Investment; Investor; Venture capital

Revolutionizing Text Data Analysis with AI Autocoding with NVivo - Lumivero (Lumivero, 2023)
As the original AI qualitative data analysis software, NVivo has fine-tuned the autocoding feature that lets researchers conduct text data analysis with AI to detect and code themes and sentiments.
KerkoCite.ItemAlsoKnownAs: 2405685:UNJD6IY6 2486141:PA4EZZ36

Use of Assistive Education Technologies to Support Children with Visual and Hearing Difficulties in the East Asia and Pacific Region - Yarrow, Noah; Pynnonen, Lauri; Song, Chuyu; Bhardwaj, Riaz; Spiezio, Mario (World Bank, 2023)
Evidence on the uptake, use, and impact of EdTech at scale on participation and learning among students with disabilities in low- and middle-income countries remains very limited. This report presents findings on access to EdTech for children with difficulties in hearing and vision in middle-income countries (MICs) in the East Asia and Pacific (EAP) region using three approaches: (i) a systematic regional literature review; (ii) interviews with 17 actors from the education technology private sector across the EAP region; and (iii) case studies from four countries: Vietnam, the Philippines, China, and Tonga. The main findings from the literature review are that most EdTech solutions in EAP MICs were applied at very small scale, with a focus on the tech testing stage, and only two of the 13 identified studies from a sample of 1,661 studies measured changes in student learning outcomes. The private sector interviews indicate qualitatively that most actors in this space are unaware of the needs of children with vision and hearing disabilities, and that other challenges such as profitability and general inequalities related to access to devices and high-speed internet receive the most attention. The case studies report no examples of national deployment of any assistive education technology, though there are multiple examples of small-scale digital approaches developed by individual schools or NGOs and shared locally or, in two cases, regionally. In looking at country contexts for the case studies, we found a lack of publicly available data on spending for assistive EdTech in EAP, a lack of data on (a) prevalence of disabilities among the student population, (b) student learning, and (c) student persistence in higher grades. We examine new data on policy-maker estimates of access and inclusion of children with disabilities, and find that despite support for inclusion, there is large scope for improving data collection, service delivery and access to assistive EdTech in MICs in the EAP region.
KerkoCite.ItemAlsoKnownAs: 10.1596/40510 2339240:2A4TZG2M 2405685:AHFJK3U9

Ethical Aspects of Faking Emotions in Chatbots and Social Robots - Indurkhya, Bipin (arXiv, 2023)
Telling lies and faking emotions is quite common in human-human interactions: though there are risks, in many situations such behaviours provide social benefits. In recent years, there have been many social robots and chatbots that fake emotions or behave deceptively with their users. In this paper, I present a few examples of such robots and chatbots, and analyze their ethical aspects. Three scenarios are presented where some kind of lying or deceptive behaviour might be justified. Then five approaches to deceptive behaviours - no deception, blatant deception, tactful deception, nudging, and self deception - are discussed and their implications are analyzed. I conclude by arguing that we need to develop localized and culture-specific solutions to incorporating deception in social robots and chatbots.
arXiv:2310.12775 [cs] KerkoCite.ItemAlsoKnownAs: 2339240:KR5WVJGX 2405685:UPY4I2DF
Keywords: Computer Science - Robotics; I.2.9

Launching the 2024 OpenAI Learning Impact Prize - Tools Competition (2023)
Tools Competition is thrilled to partner with OpenAI to drive edtech innovation leveraging AI to change the way we teach and learn.
KerkoCite.ItemAlsoKnownAs: 2405685:QGATP9KI

Evidence of the ISTE Standards for Educators leading to learning gains - Crompton, Helen (Journal of Digital Learning in Teacher Education, 2023)
The International Society for Technology in Education (ISTE) empirically designed and published educator standards to provide a roadmap for educators on effective technology integration. The purpose of this further study was to determine what empirical evidence demonstrates that the educator practices have a positive impact on student learning. Using a scoping review methodology, a transparent protocol was used for searching, identifying, and selecting articles that map to the practices within the ISTE Standards. The findings of this study reveal that all the practices in ISTE educator standards led to learning gains. This study is important for researchers, practitioners, funders, and policymakers as it provides empirical evidence that the technology practices within the ISTE Standards lead to student learning gains.
Publisher: Routledge _eprint: https://doi.org/10.1080/21532974.2023.2244089 KerkoCite.ItemAlsoKnownAs: 10.1080/21532974.2023.2244089 2339240:I4DQIJFH 2405685:PF96ZE25
Keywords: ISTE standards; teacher education; technology standards

What Explains Vietnam's Exceptional Performance in Education Relative to Other Countries? Analysis of the 2012, 2015, and 2018 PISA Data - Dang, Hai-Anh; Glewwe, Paul; Lee, Jongwook; Vu, Khoa (Economics of Education Review, 2023)
Despite being the poorest or second poorest participant, Vietnam outperformed all other developing countries, and many wealthier countries, on the 2012, 2015, and 2018 PISA assessments. We investigate Vietnam's strong performance, evaluating several possible explanations for this apparent exemplary achievement. After correcting for potentially non-representative PISA samples, including bias from Vietnam's large out-of-school population, Vietnam remains a large positive outlier conditional on its income. Possible higher motivation of, and coaching given to, Vietnamese students can at most only partly explain Vietnam's performance. The child-, household- and school-level variables in the PISA data explain little of Vietnam's strong PISA performance relative to its income level. At most, they explain about 30% of Vietnam's exceptional performance in math and reading. Further research is needed to understand the exceptional performance of Vietnamese students.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.econedurev.2023.102434 2339240:Q7F8JJWZ 2405685:8AQ4Z7GC
Keywords: PISA; Vietnam; education; enrollment; student learning; test scores

The Seewo interactive whiteboard (IWB) for ESL teaching: How useful it is? - Luo, Zhanni; Tan, Xiaoyong; He, Mu; Wu, Xianyou (Heliyon, 2023)
Publisher: Elsevier KerkoCite.ItemAlsoKnownAs: 10.1016/j.heliyon.2023.e20424 2339240:4TDXU5CZ 2405685:2VKBHQ3M 6018420:D86VP562
Keywords: Grounded theory; Interactive whiteboard (IWB); Perceived usefulness (PU); Teacher perception; Technology acceptance

Stakeholders’ perspectives of enablers and barriers to successfully implementing an integrated early childhood development program in an informal urban settlement in Kenya - Ssewanyana, Derrick; Martin, Marie-Claude; Angwenyi, Vibian; Kabue, Margaret; Proulx, Kerrie; Zhang, Linlin; Malti, Tina; Njoroge, Eunice; Nasambu, Carophine; Marangu, Joyce; Odhiambo, Rachel; Ombech, Eunice; et al. (SAGE Open, 2023)
Integrated early childhood development (ECD) programs boost child health and developmental outcomes. However, the factors contributing to the successful implementation of such programs in informal urban settlements are not well researched. We conducted 14 focus group discussions and 13 key informant interviews with 125 caregivers of children under the age of 5 years and stakeholders, exploring their views on enablers and barriers to implementing an integrated ECD program in an informal settlement in Kenya. Strategic engagement, capacity building, transparency, fair compensation of ECD workforce, communication skills, and the need to tailor ECD programs to local realities were discussed. An equity-focused implementation approach for integrated ECD programs is timely.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.1177/21582440231208986 2339240:AJEW5QXZ 2405685:DKJM4M97

Strengthening digital education systems in Türkiye for the COVID-19 pandemic and beyond - Bathanti, Jacob; Abdul-Hamid, Husein (World Bank Group, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:KQG5KAS8 2405685:CKYEY894 6018420:ANWC43W9

Cambodia Dataset - International Monetary Fund (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:JXQASGZR 2405685:842TTWG9

Timor-Leste - International Monetary Fund (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:4UEYFMAX 2405685:SYJ2M3AL
Keywords: ⛔ No INSPIRE recid found

High-quality education for better sustainability and resiliency - Prazian, Michael V; Prykhodko, Viktoria M (IOP Conference Series: Earth and Environmental Science, 2023)
The world meets poly crises in climate, pandemic, energy, food, human rights, and migration; hot and cold wars have come in Europe and other regions. The scope of the tasks becomes unprecedented, and their complexity demands high-level skill sets and teaching culture. Education moves into epicentres of the fight for better sustainability and resilience. The United National Sustainable Development Goals Four (SDG4) supposes allocating and diligently using several trillion US dollars for the next decades. The ambitious goals drive the educational system to be at a decent level regarding outcome and process. Saving gratitude to functions of a fundamental human right, a public good, gender equality, and an absolute right to education for all, the author urges that high-quality education is the priority because it will help society to cope with a new level of challenges and even existential threats the climate-like. The article describes the methodology and the importance of soft-hard skills for teaching and learning. The secondary-based sources research illustrates practical results regarding the educational process. The Triple Bottom Line principle (Planet, Profit, People) encompasses many disciplines engaging the main aspects of sustainability and resiliency and climate change for the university curricula in a coherent way. The article considers future trends in high education and case studies connected with the European Green Deal, environmental, social, and governance (ESG) reporting and practical aspects of Green Growth and De-Growth Theory. The Quality of Education reflects the regulator’s requirements and social and personal expectations. Life-long learning becomes a norm. The authors consider university products, processes and platforms through the lens of future trends, threats and opportunities. In times of turbulence, the results obtained through students’ upskilling and reskilling programs should fit the demands of new jobs, technologies, and financial mechanisms.
Publisher: IOP Publishing KerkoCite.ItemAlsoKnownAs: 10.1088/1755-1315/1254/1/012031 2339240:A62E4QP4 2405685:FILG383T

Supporting STEM Career Transitions for Girls in ASEAN - UNICEF (UNICEF, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:T9TBY2WH 2405685:S88URYJ3

A cultural transformation: Pakistani girls outperforming boys in education - Ullah, Hazir; Ullah, Raza; Shoaib, Muhammad (Qlantic Journal of Social Sciences, 2023)
In this paper, we highlight and present a nuanced picture of girls’ outperformance and boys’ underperformance in education in the urban centres of Pakistan. This is a very interesting and remarkable gender reverse trend in education performance in the dominated socio-cultural context of Pakistan. The paper takes into account the annual results of two examination boards: a) Board of Intermediate and Secondary Education (BISE) Peshawar and b) Board of Intermediate and Secondary Education (BISE) Faisalabad, Pakistan. Employing content analysis techniques, we have examined young boys’ and girls’ educational performance in secondary school certificate (SSC) and higher secondary schools certificate (HSSC) examinations from 2002 to 2016. The paper takes into account the first three positions as an indicator of outperformance. The paper simply highlights the trend of structure transformation and does not inquire about reasons for boys’ underperformance and girls’ outperformance. The study findings suggest that girls are outperforming boys in the urban centres of Pakistan.
KerkoCite.ItemAlsoKnownAs: 10.55737/qjss.355122226 2339240:SUYUFI38 2405685:UIYCJPPE

Leveraging transformative AI to support curriculum alignment - Alexandre, Jamie (Medium, 2023)
Curriculum alignment is critical but tedious; we’re building open ML and AI tools to automate and streamline the process.
KerkoCite.ItemAlsoKnownAs: 2405685:QWMVUYAH

Experiences of inclusive school settings for children and young people on the autism spectrum in the UK: A systematic review - El-Salahi, Shama; Khaki, Zahra; Vohora, Reena (Review Journal of Autism and Developmental Disorders, 2023)
Increasing numbers of Children and Young People on the Autism Spectrum (CYP-AS) are attending inclusive education settings in the UK, yet research about the impact on their psychosocial well-being is scarce. This qualitative review examined the experiences of CYP-AS in British inclusive education settings. Systematic data retrieval on nine electronic databases identified 22 papers reporting 19 studies that were eligible for inclusion. A combination of narrative synthesis and critical review described and synthesised studies’ findings and assessed the risk of bias. The findings reinforce the idea that integration into mainstream schools alone is insufficient to support the psychosocial well-being of CYP-AS. Social connectedness and a sense of belonging may be critical factors that improve school experiences for this population.
KerkoCite.ItemAlsoKnownAs: 10.1007/s40489-023-00405-2 2339240:X62G5NLK 2405685:E5RZH38V

International experience of using E-learning during pandemics and military conflicts - Bakhmat, Nataliia; Krasnoshchok, Inna; Voron, Olha (E-Learning Innovations Journal, 2023)
The spread of the COVID-19 pandemic and certain military conflicts and wars in different regions have become recent critical conditions in the social development of humanity, which has led to the active spread of the electronic knowledge acquisition system. Therefore, the experience of studying the peculiarities of e-learning implementation during a pandemic and military conflicts has become relevant. The purpose of this study is to implement a comprehensive review and analysis of existing scientific works on the use of e-learning in crisis conditions. For this purpose, PubMed, Scopus, WebofScince were chosen as the main scientific and metric databases, and Ebsco and Sherpa Romeo were used as additional ones. The criteria for including the literature are based on relevance, relevance to the research topic, and the availability of a detailed methodology. In addition, the emphasis was placed on the works of less than 5 authors and publications written since 2014. Thus, based on these criteria, 62 items were selected for analysis. The analysis was based on thematic and comparative methods. The results characterize the dynamics of the emergence of scientific papers on e-education. It is determined that high rates of interest are present in 2020 and 2022 (both 27.42% of the total). It has also been found that modern countries use various electronic tools to adapt to the crisis: learning platforms, management systems, electronic communications, and electronic journals. The conclusions show that international experience shows that the global education system is adapting to the challenges. E-education has also proven to be effective during military conflicts, in particular the experience of Saudi Arabia, Syria, Ukraine and other countries, which indicates the widespread use of e-education elements.
Number: 2 KerkoCite.ItemAlsoKnownAs: 10.57125/ELIJ.2023.06.25.04 2339240:8JEGRCNI 2405685:4SHKS5W3
Keywords: critical conditions; development; electronic technologies; global educational system; war conditions

Coursera extends free access to courses for Ukrainian higher education institutions - Ministry of Education and Science of Ukraine (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:7NUABWH2 2405685:CE5W3TAS

Disability and caregiver burden: Unique challenges in a developing country - Hewawitharana, Bimba D.R.; Wijesinghe, Champa J.; De Silva, Aruna; Phillips, John P.; Hewawitharana, Gemunu P. (Journal of Pediatric Rehabilitation Medicine, 2023)
PURPOSE:This study aimed to identify factors, including degree of disability, that contribute to the caregiver burden of raising children with cerebral palsy in Sri Lanka.METHODS:Participants were caregivers of children with cerebral palsy attending the pediatric neurology clinic of the only tertiary care center in southern Sri Lanka. The locally validated Caregiver Difficulties Scale (CDS) was administered, and demographic information was obtained in a structured interview. Disability data was accessed through the medical record.RESULTS:Of 163 caregivers who participated in this study, 133 (81.2%) demonstrated a moderate to high level of burden, and 91 (55.8%) were at high risk for psychological burden. In the bivariate analysis, caregiver burden significantly correlated with degree of physical disability based on the Gross Motor Function Classification System (GMFCS) and the Manual Ability Classification System (MACS), the presence of medical co-morbidities, and having two or more children. However, only the GMFCS level and number of children remained significant predictors of caregiver burden after controlling for confounding effects.CONCLUSION:Raising a child with cerebral palsy in Sri Lanka is likely to cause caregiver burden, particularly if they have a high level of disability or one or more siblings. Monitoring caregiver burden as part of routine cerebral palsy management is important, which allows targeting psychosocial support to families most in need.
Publisher: SAGE Publications KerkoCite.ItemAlsoKnownAs: 10.3233/PRM-220070 2339240:35UXTUTF 2405685:Y8DJITB4

Nudging parents and teachers to improve learning and reduce child labor in Cote d’Ivoire - Wolf, Sharon; Lichand, Guilherme (npj Science of Learning, 2023)
Whether SMS-based nudge interventions can increase parent engagement and improve child learning outcomes across diverse contexts such as rural West Africa is unknown. We conducted a school-randomized trial to test the impacts of an audio or text-message intervention (two messages per week for one school year) to parents and teachers of second and fourth grade students (N = 100 schools, 2246 students) in Cote d’Ivoire. Schools were randomly assigned to have messages sent to (i) parents only, (ii) teachers only, (iii) parents and teachers together, or (iv) control. There were statistically non-significant impacts of the parents-only treatment on learning, although with typical effect sizes (d = 0.08, p = 0.158), and marginally statistically significant increases in child labor (d = 0.11, p < 0.10). We find no impacts of the other treatment conditions. Subgroup analyses based on pre-registered subgroups show significantly larger improvements in learning for children with below-median baseline learning levels for the parents-only arm and negative impacts on learning for girls for the teachers-only arm, suggesting different conclusions regarding impacts on equity for vulnerable children.
Number: 1 Publisher: Nature Publishing Group KerkoCite.ItemAlsoKnownAs: 10.1038/s41539-023-00180-z 2339240:TBVAYFZC 2405685:XET829T4
Keywords: Economics; Education

A study of mobile app use for teaching and research in higher education - Hinze, Annika; Vanderschantz, Nicholas; Timpany, Claire; Cunningham, Sally Jo; Saravani, Sarah-Jane; Wilkinson, Clive (Technology, Knowledge and Learning, 2023)
The exponential growth in the use of digital technologies and the availability of mobile software applications (apps) has been well documented over the past decade. Literature on the integration of mobile technology into higher education reveals an increasing focus on how mobile devices are used within the classroom environment, both physical and online, rather than on how mobile applications may be used for either teaching or the research process. Our study surveyed staff and higher degree research students at a New Zealand university using an online questionnaire to gain insight into the use of mobile apps for tertiary teaching and research, seeking information, particularly on which apps were used for which tasks and what obstacles hindered their use. The online survey used 29 questions and ran in 2016/2017. 269 participants completed the survey, nearly 20% of the potential sample. We found that mobile apps were used by academics and students for both teaching and research, primarily in the form of document and data storage and exchange, and communication. Very little app use was recorded for in-class activities (teaching) or in-field activities (research). Apps use resulted from personal motivation rather than institutional planning. Both students and academics reported that institutional support and flexibility would likely provide motivation and lead to increased app use for both research and teaching.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10758-022-09599-6 2339240:CQPWS23K 2405685:4MNEEC9L

Report of Case Studies on Responses to the Covid-19 Pandemic in Africa’s Educational Systems - Kiru, Elisheba; Ochieng, Vollan; Wawire, Brenda; Habiamana, Oliver; Ngware, Moses (APHRC, 2023)
This report presents case studies from seven African countries (i.e., Burkina Faso, Kenya, Malawi, Mali, Mozambique, Niger, and Nigeria) that implemented programs and innovations in response to the effects of the COVID-19 pandemic on the education systems. The report provides insights into building resilience within Africa’s education systems for the future. The case studies fill existing knowledge gaps on promising practices and add value to discussions on the contextual drivers that facilitated the implementation of the interventions, including active government involvement in mobilizing and supporting the initiatives. The programs include the PRONAE national school feeding program in Mozambique, the online teacher professional development program in Kenya, teacher training in Niger, back-to-school campaigns in Malawi, basic education training in internally displaced camps in Burkina Faso and Niger, and initiatives addressing sexual and gender-based violence in Mali. The case studies also seek to examine the extent to which the interventions addressed gender, equity, and inclusion. For the Global Partnership for Education (GPE) partner countries, these case studies provide valuable information regarding the operations of education systems and the well-being of learners.
Accepted: 2023-09-06T13:30:22Z KerkoCite.ItemAlsoKnownAs: 2339240:KW99KLTL 2405685:7V8V344E

Digital Application Akelius as a Blended Learning Tool - Manapbayeva, Zhannura; Aliyeva, Dinara (2023 IEEE 12th International Conference on Intelligent Data Acquisition and Advanced Computing Systems: Technology and Applications (IDAACS), 2023)
The article deals with modern approaches to the problem of blended learning, which are based on different criteria for organizing the learning environment depending on the expected learning outcomes. The advantages of blended teaching Russian as a foreign language are creating an individual learning trajectory, taking into account the level of language proficiency, the changing social environment (students are children of migrants), and an inclusive environment. The authors demonstrate the possibilities of using the Akelius digital application for teaching Russian as a foreign language, based on the experience of using it in a blended learning format, possible ways of using the Akelius application in the educational process when teaching language literacy in combination with traditional forms of education. The article focuses on the advantages of this application, built on the principle of a communicative-activity approach, which involves situational learning of a foreign language and is in the nature of inclusion of everyday communication in the language environment. The role of the teacher in the organization of the educational process when learning a new language in conditions of blended learning has also been noted. The authors offer modern teaching technologies that contribute to the transformation of the learning environment into a creative process of socialization of migrant children; demonstrate a lesson model with the use of the Akelius digital application.
ISSN: 2770-4254 KerkoCite.ItemAlsoKnownAs: 10.1109/IDAACS58523.2023.10348848 2339240:G5K77QEQ 2405685:L78JPC2X
Keywords: Akelius digital application; Data acquisition; Education; Hybrid learning; Organizations; Task analysis; Training; Trajectory; blended learning; methodology for teaching a foreign language

Ghana’s Education Reforms in Spotlight - Ministry of Education Ghana (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:E93CMPA3 2405685:Q9MZE3PD

Strengthen Educational Accountability in Ghana (SAGES) - A USAID-funded program - U.S Embassy - Ghana (USAID News & Events, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:3AEUYQAV 2405685:5JPNEEXM

Usability Testing of a Mobile-based Learning Management System for Teacher Continuous Professional Development in Tanzania - Kondoro, Aron; Maro, Salome; Mtebe, Joel; Haßler, Björn; Proctor, Jamie; EdTech Hub (The International Journal of Education and Development using Information and Communication Technology, 2023)
The last two decades have seen the growing adoption of mobile devices to enhance the quality of teachers' continuous professional development (TCPD) in low-income countries. Using mobile devices, typically not designed for educational use, presents new usability challenges, preventing teachers from effectively accessing learning materials in learning management systems (LMS). Therefore, it is important to test usability to improve the delivery of TCPD via mobile devices. This study evaluated the usability of TCPD-focused mobile-based LMS accessed via a mobile web browser and mobile app. The evaluation used a hybrid think-aloud method involving 63 teachers from 12 schools in Tanzania. Half of the schools were evaluated using a concurrent think-aloud method, and the other half using a retrospective think-aloud method. The study found that teachers encountered many usability problems in using the mobile app compared to those who accessed the LMS via mobile web browsers. The study also found usability flaws in the registration and login process, poor language translation, technical errors, and issues with quiz questions. These findings show the importance of user testing, even for well-developed LMS, such as Moodle. Additionally, this work provides useful guidance for those who want to implement mobile learning via an LMS in low-income countries.
KerkoCite.ItemAlsoKnownAs: 2339240:ZTWSB6CB 2405685:L5AY2YZI
Keywords: ⛔ No DOI found

PISA 2022 ICT Framework - OECD (PISA 2022 Assessment and Analytical Framework, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1787/dfe0bf9c-en 2405685:2SWALTJD

International Development Association Project Paper on a Proposed Additional Credit in the Amount of Sdr 521.3 Million (us$700.0 Million Equivalent) to the Federal Republic of Nigeria for the Adolescent Girls Initiative for Learning and Empowerment Project - World Bank (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:7X6XH5NA 2405685:E5NGJ8G6

Digital literacy through Let’s Read app to improve the reading interest of elementary school students - Samsudin, Dea Fariska Ardiana; Rahmawati, Fitri Puji (Atlantis Press, 2023)
This study aimed to determined digital literacy through Let's Read application (app) as an innovation to increase students’ reading interest and to find out the results of using the let's read app in reading activities in elementary schools. The method used in this study was descriptive qualitative with a case study design. The authors collected...
ISSN: 2352-5398 KerkoCite.ItemAlsoKnownAs: 10.2991/978-2-38476-086-2_36 2339240:ZARBNQJG 2405685:VZV3N3BY

Parents’ attitudes and opinions towards their children's use of technology - Akgun, Fatma (International Journal of Research in Education and Science, 2023)
The aim of the study is to determine the level of parents’ attitudes towards their children's use of information and communication technologies and to obtain parental views on the use of technology. To this end, the study was carried out with parents whose children were studying at primary and secondary school levels. Data were collected from 417 guardians for the quantitative dimension of the study, which was designed with a mixed methodological approach in which qualitative and quantitative models were used together, and interviews were conducted with 10 parents in the same sample group for the qualitative dimension. For the analysis of the data, descriptive statistics, independent sample t-test, one-way analysis of variance (ANOVA) and multiple comparison tests and descriptive analysis technique was used. The results of the analysis of the data showed that the attitudes of the parents towards their children's use of technology were at a "good" level. In the study, no significant difference was found between the attitudes of parents towards their children's use of technology and the gender variables, while there was a significant difference between the variables of age, educational level, occupation, computer usage skills and computer usage time. The study also addressed which technological device their children use for which purpose, the technology-assisted applications used by their children for educational purposes, and the support given by parents to their children in terms of knowledge, skills, time management and safe use when using technology, and the positive and negative aspects of technology use, and various suggestions were made to parents for the correct and effective use of technology by parents.
KerkoCite.ItemAlsoKnownAs: 10.46328/ijres.3157 2339240:QFG75NID 2405685:RPWG43RQ

The equalizing effect of teacher dashboards on feedback in K–12 classrooms - Knoop-van Campen, Carolien A. N.; Wise, Alyssa; Molenaar, Inge (Interactive Learning Environments, 2023)
Teacher dashboards provide real-time information about students’ performance and progress, which help K-12 teachers to adjust feedback to student’ specific needs during learning. Prior research indicated two problems with respect to how teachers provide feedback: (i) teachers do not always select the most effective feedback to support student’ learning and (ii) feedback is not allocated equally to students with different abilities. Specifically, process feedback is considered most effective yet is relatively scarce. In order to understand how dashboards influence the type and allocation of feedback, we compared characteristics of feedback given after dashboard consultation (dashboard-prompted feedback) to feedback triggered by teachers themselves or in response to students’ questions (human-prompted feedback) in thirty-five K-12 classrooms. Results showed that dashboards led to equal amounts of task and process feedback, while human-prompts led to much more task than process feedback and this difference was especially large for low-ability students. Hence the different types of dashboard-prompted feedback were more equally distributed among students of different ability levels. These results indicate that dashboards can have an important equalizing effect on teacher feedback practices.
Publisher: Routledge _eprint: https://doi.org/10.1080/10494820.2021.1931346 KerkoCite.ItemAlsoKnownAs: 10.1080/10494820.2021.1931346 2339240:8B8RAQU9 2405685:M8LPDYII
Keywords: K-12; Teacher dashboards; ability levels; adaptive learning technology; feedback; learning analytics

Digital Personalised Learning to Improve Literacy and Numeracy Outcomes in Kenyan Classrooms - Daltry, Rebecca; Major, Louis; Sun, Chen; Otieno, Mary; Otieno, Kevin; Otieno, Louis Major, Chen Sun, Mary Otieno and Kevin, Rebecca Daltry (EdTech Hub, 2023)
This blog forms part of a wider research study on digital personalised learning to improve literacy and numeracy outcomes in Kenyan classrooms, and outlines emergent findings from a randomised controlled trial following the first two rounds of assessment (baseline and midline). The preliminary findings will be strengthened after further analyses and endline assessment.
KerkoCite.ItemAlsoKnownAs: 2339240:SL5WSSVM 2405685:5BIU6BJ5

Public Procurement in the Post-War Reconstruction of Ukraine: Main challenges - OECD (2023)
Series: OECD Policy Responses on the Impacts of the War in Ukraine KerkoCite.ItemAlsoKnownAs: 10.1787/c427b561-en 2339240:ZFEXX4R4 2405685:GCYP5SWE

Emergence of national nutrition policy in the Lao People’s Democratic Republic: An analysis of collaborations between governmental and external actors - Sengchaleun, Viengsamay; Kounnavong, Sengchanh; Reinharz, Daniel (Tropical Medicine and Health, 2023)
In most developing countries, addressing malnutrition involves a coalition of stakeholders that includes the government and international development partners. This study explores the evolution of the malnutrition actor coalition landscape before and after the emergence of the National Nutrition Policy in the Lao People’s Democratic Republic (Lao PDR) in 2008.
1 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.1186/s41182-023-00532-w 2339240:AM8J244B 2405685:4B4L8B6T
Keywords: Coalition; Lao PDR; Malnutrition; Multisectoral collaborations; Nutrition policy; Stakeholders; ⛔ No INSPIRE recid found

Drafted National ICT Policy, 2023 - Ministry of Information, Communication and Information Technology (Government of Tanzania, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:7J7M97L6 2405685:JMHNKQLJ

Pentagonal Strategy Phase I - Royal Government of Cambodia (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:LCLGRSN5 2405685:LC8A3756

Experimental education research: rethinking why, how and when to use random assignment - Sims, Sam; Anders, Jake; Inglis, Matthew; Lortie-Forgues, Hugues; Styles, Ben; Weidmann, Ben (UCL Centre for Education Policy and Equalising Opportunities, 2023)
Over the last twenty years, education researchers have increasingly conducted randomised experiments with the goal of informing the decisions of educators and policymakers. Such experiments have generally employed broad, consequential, standardised outcome measures in the hope that this would allow decisionmakers to compare effectiveness of different approaches. However, a combination of small effect sizes, wide confidence intervals, and treatment effect heterogeneity means that researchers have largely failed to achieve this goal. We argue that quasi-experimental methods and multi-site trials will often be superior for informing educators' decisions on the grounds that they can achieve greater precision and better address heterogeneity. Experimental research remains valuable in applied education research. However, it should primarily be used to test theoretical models, which can in turn inform educators' mental models, rather than attempting to directly inform decision making. Since comparable effect size estimates are not of interest when testing educational theory, researchers can and should improve the power of theory-informing experiments by using more closely aligned (i.e., valid) outcome measures. We argue that this approach would reduce wasteful research spending and make the research that does go ahead more statistically informative, thus improving the return on investment in educational research.
KerkoCite.ItemAlsoKnownAs: 2339240:55K69EGU 2405685:C5QK4INN
Keywords: education; experiments; policy; randomized controlled trials; research

How are the children of Pakistan’s 2022 floods faring? - Perry, Freya; Barón, Juan D; Dahlin, Lauren (World Bank Blogs, 2023)
In 2022, catastrophic floods hit Pakistan, impacting access to education for more than 3.5 million children. A year on, the disruption to education and the lack of focus on learning recovery will likely have long-term effects on Pakistan’s human capital.
KerkoCite.ItemAlsoKnownAs: 2339240:4AGRU7N7 2405685:7H8QU9SE

The Use of SMS and Other Mobile Phone-based Messaging to Support Education at Scale: A Synthesis of Recent Evidence - Jordan, Katy; Damani, Kalifa; Myers, Christina; Zhao, Annette (Proceedings of the Tenth ACM Conference on Learning @ Scale, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1145/3573051.3596172 2339240:YW4HVVTD 2405685:82DMJDK6 2405685:ZBTT8ST5

Deployment of Offline Learning Management Systems: Comparing the Performance of Selected Micro-servers in Tanzania - Maro, Salome; Kondoro, Aron; Haßler, Björn; Mtebe, Joel; Proctor, Jamie (Journal of Learning for Development, 2023)
Low-powered mobile devices such as Raspberry Pis and tablets can be used as micro-servers to implement offline Learning Management Systems (LMS). Despite their potential, especially for low-income countries, such as Tanzania, no research is available detailing the affordances of these devices for supporting LMS features. This study investigated the suitability of various low-cost micro-servers for deploying LMSs. It compared the performance of the Raspberry Pi, Android tablet, and Chromebook in terms of LMS benchmarking, response time, and resource utilisation. Results showed all devices had sufficient hardware resources to support the LMS, however, software stacks, I/O performance, and platform optimisations affected the micro-servers' performance. The Chromebook had the best performance in terms of response time, followed by the Raspberry Pi and tablets. In terms of cost, the Raspberry PI was the cheapest option. The installation process for tablets was more cumbersome than the other devices, meaning the devices with better tooling and a more conventional software stack were a better option for deploying offline micro-servers.
KerkoCite.ItemAlsoKnownAs: 10.56059/jl4d.v10i2.835 2405685:IXJ5MQJN

List of Jordan Tenders - Government & Business Opportunities - Tender Impulse (Tender Impulse, 2023)
Explore tenders from Jordan published on 18 July 2023. Access verified government and business bids with Tender Impulse - your trusted global tender partner.
KerkoCite.ItemAlsoKnownAs: 2339240:9SL2V4ZN 2405685:6Y83S3B8

Children and Their Families Six Months After Pakistan’s Floods - Dahlin, Lauren; Barón, Juan D (World Bank, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1596/39978 2339240:SELX6D8I 2405685:H4B7Q3AI

Rensvandeschoot/software-overview-machine-learning-for-screening-text - van de Schoot, Rens (2023)
The repository aims to create an overview and comparison of software used for systematically screening large amounts of textual data using machine learning.
original-date: 2022-02-17T18:40:05Z KerkoCite.ItemAlsoKnownAs: 2405685:H75KUGV8 2486141:DYRPSJRR
Keywords: _Added-ailr-2024; active-learning; machine-learning; software-development; systematic-reviews

EdTech Investments in Vietnam in 2023 - Nguyen, Uyen (Vietnam Briefing News, 2023)
In this article, we look at key foreign-invested EdTech projects in Vietnam and why foreign firms have invested where they have.
KerkoCite.ItemAlsoKnownAs: 2339240:QZGEV6AH 2405685:2SH92E4R

Benefit Incidence Analysis of the Education Sector in Sierra Leone - Ministry of Finance (Government of Sierra Leone, 2023)
DOWNLOAD
KerkoCite.ItemAlsoKnownAs: 2339240:8GYX9MM4 2405685:WQW66Q4H

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Pacitto, Julia; Barnes, Katrina; Mukankusi, Aimée; Zazai, Rozina (EdTech Hub, 2023)
This article presents the ﬁndings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Ofﬁce (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identiﬁes the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls.
KerkoCite.ItemAlsoKnownAs: 10.53832/edtechhub.0172 2339240:IH7X7TBE 2405685:BCNUTSXS

How the COVID-19 shutdown revealed the effectiveness of a northern Nigerian educational media program - Borzekowski, Dina L.G.; Kauffman, Lauren E.; Jacobs, Lauren; Jahun, Mamun; Babayaro, Hadiza (Journal of Children and Media, 2023)
A team of researchers were investigating the impact of a Nigerian adaptation of Akili and Me when the COVID−19 pandemic struck. Schools shut down, interrupting the study’s quasi-experimental intervention design. Post-school reopening, researchers recon tacted 363 children (mean age = 5.1, SD = 1.1 years) who had pro vided data at baseline and had completed the intervention. The analyses revealed that during the shutdown, participating children watched Akili and Me, beyond the exposure experienced through the study intervention. Across viewing groups and including the control group, researchers found the children knew the program’s characters using a program receptivity score. The researchers found no differences associated with study’s initial group assignments. Those children who could name more Akili and Me characters performed significantly better on the outcomes of literacy, numer acy, shape, socio-emotional development, controlling for sex, age, baseline score, and group assignment. This study offers promising evidence that locally-produced educational media interventions can impact early learning skills, especially during a crisis when children rely on educational media for home learning.
KerkoCite.ItemAlsoKnownAs: 10.1080/17482798.2023.2222187 2339240:JVK39SLG 2405685:PLGYGNCQ

Issues of quality on Teachers Pay Teachers: An exploration of best-selling U.S. history resources - Harris, Lauren McArthur; Archambault, Leanna; Shelton, Catharyn C. (Journal of Research on Technology in Education, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1080/15391523.2021.2014373 2339240:XV9B9ANM 2405685:77NSH2CV

gpt-researcher - Elovic, Assaf (2023)
GPT based autonomous agent that does online comprehensive research on any given topic
original-date: 2023-05-12T10:33:54Z KerkoCite.ItemAlsoKnownAs: 2405685:LNM8ZPCU

Emotion Detection Research: A Systematic Review Focuses on Data Type, Classifier Algorithm, and Experimental Methods - Destyanto, Twin Yoshua R. (International Journal of Industrial Engineering and Engineering Management, 2023)
There is a lot of research being done on detecting human emotions. Emotion detection models are developed based on physiological data. With the development of low-cost wearable devices that measure human physiological data such as brain activity, heart rate, and skin conductivity, this research can be conducted in developing countries like Southeast Asia. However, as far as the author's research is concerned, a literature review has yet to be found on how this research on emotion detection was carried out in Southeast Asia. Therefore, this study aimed to conduct a systematic review of emotion detection research in Southeast Asia, focusing on the selection of physiological data, classification methods, and how the experiment was conducted according to the number of participants and duration. Using PRISMA guidelines, 22 SCOPUS-indexed journal articles and proceedings were reviewed. The review found that physiological data were dominated by brain activity data with the Muse Headband, followed by heart rate and skin conductivity collected with various wristbands, from around 5-31 participants, for 8 minutes to 7 weeks. Classification analysis applies machine learning, deep learning, and traditional statistics. The experiments were conducted primarily in sitting and standing positions, conditioned environments (for developing research), and unconditioned environments (applied research). This review concluded that future research opportunities exist regarding other data types, data labeling methods, and broader applications. These reviews will contribute to the enrichment of ideas and the development of emotion recognition research in Southeast Asian countries in the future.
KerkoCite.ItemAlsoKnownAs: 10.24002/ijieem.v5i1.7077 2339240:PKER7HQK 2405685:9AYVRB55

Salama Africa: Bridging the Gap for Out-of-School Children in Dzaleka Refugee Camp - Imagine Worldwide (Imagine Worldwide, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:22KVIIH8 2405685:QSDESVX8

Assessment of parent’s engagement in implementation of competency-based curriculum in private primary schools in Tharaka South Sub-County of Tharaka-Nithi County, Nithi County, Kenya - Njeru, Atanasia Ikoore; Kirimi, Josephine (European Journal of Education Studies, 2023)
Education is a shared responsibility and all stakeholders need to understand and appreciate what is being done and what is required of them to make meaningful contributions to the process. Because the Competency-Based Curriculum shifted its focus from teaching-centric to collaborative-centered, parents are important stakeholders for its successful implementation. Therefore, empowering and engaging a parent in the learning process is essential to the learner’s growth and development. The study examined parents’ engagement in CBC implementation. This study specifically aimed to determine parents’ engagement in the implementation of Competency-Based Curriculum in private primary schools in Tharaka South Sub-County of Tharaka-Nithi County. To get this, the researcher went to private primary schools in Tharaka South Sub County to observe how parents are embracing CBC and randomly selected some parents for interviews, teachers, and head teachers to fill out questionnaires. The study adopted a descriptive survey design where the targeted population was drawn from the 30 private schools in the sub-county. The study targeted 528 respondents. 66 respondents were sampled: 42 parents, 18 teachers and 6 head teachers. Simple random sampling was then used to select the participant. The study conducted a pretest study in 3 private primary schools for the purpose of validating the research instruments. Data was collected using questionnaires for head teachers and teachers and interview schedules for parents. The validity of the research instruments was determined through expert judgment whereas the reliability of the questionnaires was determined through a Cronbach’s alpha coefficient of 0.7982 was obtained. Qualitative data was analyzed thematically whereas quantitative data was summarized using percentages, mean, standard deviation and frequencies were used. This was facilitated by the Statistical Package for Social Sciences (SPSS) Version 21. The study established a significant relationship between the parent’s literacy and the implementation of CBC with a significance value of p=0.000<0.05. The study concluded that the implementation of CBC is greatly challenged by a lack of sensitization on the implementation of the CBC and perceived CBC as expensive, demanding and time-consuming. Thus, recommended that the private schools get more time with their parents to sensitize them on the CBC implementation and get to know their role in the academic performance of their children and also try to change their perception of CBC as expensive, demanding and time-consuming. Article visualizations:
Number: 7 KerkoCite.ItemAlsoKnownAs: 10.46827/ejes.v10i7.4890 2339240:U8V7ZQBP 2405685:6DAPRS4W
Keywords: competency-based curriculum; curriculum implementation; parent’s engagement

Education in times of restriction: an examination of refugee girls’ and young women’s access to learning during COVID-19 school closures in Pakistan - Barnes, Katrina; Ashlee, Amy; Mukankusi, Aimee; Pacitto, Julia; Rabi, Asma; Thomas, Matt; Ullah, Noor; Zazai, Rozina; Zhao, Annette (Educational Research for Policy and Practice, 2023)
This paper examines the extent to which refugee girls and young women were able to access learning during COVID-19 education closures in Pakistan, and the role that EdTech played in their learning access. It is based on findings from a survey with 403 Afghan refugee students, along with in-depth interviews with six young female refugees. The research shows that, while the majority of female refugee students were able to continue accessing education in some form during school closures, learning access was nevertheless limited, and a sizable minority were not engaged in any learning during this time. Teacher and institutional support was either absent or inadequate for many students, and infrastructure and devices that serve to support remote learning were not always reliable or accessible. Although male respondents were less likely than females to engage in independent study during the closures, refugee girls and young women were significantly less likely than their male counterparts to own the devices they needed for learning. The findings demonstrate how targeted investment in specific types of EdTech and teacher professional development, as well as supporting educational institutions in the establishment of remote learning opportunities, could help sustain learning during future periods of educational restriction.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10671-023-09353-4 2405685:SWPGW69K
Keywords: COVID-19; Distance education; Educational technology; Gender; Pakistan; Refugee education

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7966434 ZenodoArchiveConcept: 7966433 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7966434 10.53832/edtechhub.0168 2405685:CQ8JNCH8
Keywords: _r:AddedByZotZen

Sierra Leone | Technology | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:G8958J9Q 2405685:F5K8RR2H

Sierra Leone joins Elon Musk's Starlink satellite service - Komminoth, Leo (African Business, 2023)
The country now joins Nigeria, Mozambique, Rwanda, and Mauritius as African nations connected to Elon Musk's Starlink.
KerkoCite.ItemAlsoKnownAs: 2339240:NAF4JVME 2405685:UEE8UWYC

The importance of theoretical positioning and the relevance of using bibliometrics for literature reviews - Rowe, Frantz; Kanita, Nada; Walsh, Isabelle (Journal of Decision Systems, 2023)
The theoretical positioning of a review is of the utmost importance in terms of its contribution to knowledge. This paper clarifies the significance of this design principle for different types of review i.e. for describing, understanding, explaining or testing purposes. Furthermore, new tools now mean that it is both possible and relevant for bibliometrics novices to use bibliometrics to support literature reviews. Applying the BIBGT method and combining two bibliometric techniques – co-citation analysis of references and bibliographic coupling of documents – can enhance the efficiency of the first three types of literature review. This paper provides examples of published works that apply BIBGT to each of these types of review and highlights the bibliometric software used. It concludes with a survey of promising applications for all researchers and makes recommendations for both experienced literature review researchers and literature review novices.
KerkoCite.ItemAlsoKnownAs: 10.1080/12460125.2023.2217646 2405685:HGQ8Z5G8 2486141:AH357B5B
Keywords: _Added-ailr-2024

Parenting in context: Parents’ experiences of caring for a child with autism in Bangladesh - Uddin, Mohammad Jasim; Ashrafun, Laila (International Journal of Anthropology and Ethnology, 2023)
Although research on children with autism, their parents, and family-provider relations has substantially increased around the world, there has been a paucity of qualitative studies conducted on autism in developing countries or cross-cultural contexts. This qualitative study aims to explore parents’ experiences of raising a child with autism, as well as how autism is framed in everyday cultural contexts in Bangladesh. Using a semi-structured interview schedule, the study conducted interviews with four fathers and eighteen mothers of children with autism. The findings of this study reveal that parents who care for a child with autism experience emotions of sadness, frustration, and isolation. Despite the immense challenges that come with raising a child with autism, many parents report that their stress and anxiety are compounded by the stigma, avoidance, and disparaging remarks they receive from their own family members and neighbors. The findings of this study may help researchers and healthcare professionals understand better as to how local cultural beliefs, experiences, and understandings influence, how parents and families care for and view the development of their children with autism, and how they look for support and treatment services.
KerkoCite.ItemAlsoKnownAs: 10.1186/s41257-023-00089-w 2339240:FST7HD8T 2405685:IETYVWPW
Keywords: Autism; Bangladesh; Isolation; Parenting; Qualitative research; Stigma

Exploring donor-driven skills development as a channel of continued aid dependency - Harris, Jamelia (Third World Quarterly, 2023)
Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.1080/01436597.2023.2178889 2339240:WTZ26BCQ 2405685:3CVCLUXZ
Keywords: NGOs; Sierra Leone; Skills development; aid; dependency

Guidance Notes for Establishing and Sustaining (Virtual) Communities of Practice in Education in Displacement Context - Kasper, Julie (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:QKMWYW6M 2405685:5WVHWQ3F

Towards Improving the Accessibility and Usability of a Mobile-based Learning Management System for Blind Primary School Teachers - Kondoro, Aron; Maro, Salome; Mtebe, Joel; Proctor, Jamie; Komba, Aneth; Haßler, Björn (2023 IST-Africa Conference (IST-Africa), 2023)
KerkoCite.ItemAlsoKnownAs: 10.23919/IST-Africa60249.2023.10187797 2405685:D9ML5MHA

International Development Association: Project Appraisal Document on a Proposed Credit in the Amount of SDR 371.2 million to the Federal Republic of Nigeria for a Nigeria for Women Program Scale-Up Project - World Bank (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:53YFHVSM 2405685:JPJMF9PX

How can messaging apps, WhatsApp and SMS be used to support learning? A scoping review - Jordan, Katy (Technology, Pedagogy and Education, 2023)
In response to disruption to education during the COVID-19 pandemic, mobile phone-based messaging has emerged in some instances as an accessible, low-connectivity way of promoting interactivity. However, no recent reviews have been undertaken in relation to how social media and messaging apps can be used to effectively support education in low- and middle-income countries. In this scoping review, 43 documents were identified for inclusion, and three main thematic areas emerged: supporting student learning (including interacting with peers and other students, peer tutoring and collaborative learning; and interacting with teachers, through content delivery, teaching and assessment); teacher professional development (including structured support and prompts, and informal communities of practice); and supporting refugee education. The discussion and findings are both of practical use, to inform responses to the current pandemic and designing initiatives in the future, and will also be useful for advancing research in this expanding field.
KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2023.2201590 2339240:KR923MEV 2405685:NRTU24IH

Investing in imagined digital futures: The techno-financial ‘futuring’ of edtech investors in higher education - Williamson, Ben; Komljenovic, Janja (Critical Studies in Education, 2023)
Educational technology is the focus of increasing financial investment. In this article, we examine how edtech investors imagine and invest in the future of higher education through an empirical case study of a UK investing company. Utilising concepts and methods from economic sociology, we analyse how investment companies engage in techno-financial ‘futuring’ practices. We identify two kinds of futuring practices. First, investors’ imaginary practices produce qualitative ‘fictional expectations’ about the future of education, supported by quantitative financial valuation practices that predict the monetary returns on investment available from funding edtech. Second, we analyse the specific investment-supporting operations of edtech investors, highlighting how imagined futures of education are funded into existence (or not) as investors select and support edtech products or services. In these ways, imaginaries of the future may be materialised in educational institutions through financial investments in specific edtech products. We particularly trace how investment imaginaries and operations shift from edtech markets as selling commodities to edtech industry controlling digital products and resources as assets. Therefore, the two identified complementary futuring practices function as processes of ‘assetisation’, aimed at turning educational services and resources into digital assets with calculable future value for edtech investors.
Publisher: Routledge _eprint: https://doi.org/10.1080/17508487.2022.2081587 KerkoCite.ItemAlsoKnownAs: 10.1080/17508487.2022.2081587 2339240:D94LLVBI 2405685:9NIZHS29

Building the Next Generation of Girls (and Boys) in Technology in Sierra Leone - Abakah, Julian; Mason, Harriet (UNICEF Sierra Leone, 2023)
Building the next generation of Girls (and boys) in Technology in Sierra Leone
KerkoCite.ItemAlsoKnownAs: 2339240:SNRGEUMK 2405685:ADDZMLVR

Primary school learning in sub-Saharan Africa during COVID-19: A scoping review of responses and recovery initiatives induced during school closures - Wawire, Brenda; Barnes-Story, Adrienne; Kiru, Elisheba; Kim, Sungkyum (Current Issues in Comparative Education, 2023)
Globally, the COVID-19 pandemic caused unprecedented disruptions in education. School closures quickly followed the onset of the pandemic to contain the spread of the virus, forcing millions of students out of their regular academic calendars. Countries put in place interventions aimed to reduce the deleterious effects of school closures and disruptions in learning. For instance, many countries used various mediums to provide students with distance learning. This scoping review examines the interventions that education systems in low- and middle-income Sub-Saharan African (SSA) countries (LMIC) implemented to mitigate learning loss in reading and writing skills among early grade learners (i.e., children attending primary schools) and discusses the reach of those programs. This review highlights the proportion of students reached by the targeted mitigation measures, revealing that LMIC countries in SSA provided students with remote learning opportunities through radio and television programming, provided teachers with professional development on the use of novel tools, and provided parents and families with support to help learners at home. However, these disruptions affected the traditional assessment methods. Various assessment methods were implemented to measure student progress, but there is a need for appropriate progress monitoring tools and accurate data to measure the effectiveness of the interventions. Many LMIC implemented Return-to-School policy frameworks, processes, and principles that ensured safe learning continuity.
Number: 1 KerkoCite.ItemAlsoKnownAs: 10.52214/cice.v25i1.9969 2339240:JJCSJBZX 2405685:Q4MW8X56
Keywords: COVID-19; early grades; interventions; learning loss; literacy; responses

Analysis of emergency remote teaching in formal education: Crosschecking three contemporary techno-pedagogical frameworks - Kasperski, Ronen; Porat, Erez; Blau, Ina (Research in Learning Technology, 2023)
During the COVID-19 pandemic outbreak many countries around the world were forced to turn to Emergency Remote Teaching (ERT) and upscale the use of digital technologies for learning, teaching and assessment. The current study analysed field reports from 89 elementary and secondary Hebrew-speaking and Arabic-speaking information and communication technology schools in Israel, representing the cultural, ethnic, and religious diversity of the education system. The qualitative analysis of the collected data was based on three well established contemporary models of technology integration and Digital Competence of Educators (DigCompEdu): the International Society for Technology in Education, Technological Pedagogical Content Knowledge and DigCompEdu. The analysis (n = 872 statements) yielded aspects in the teachers’ reports that correspond with the theoretical models, alongside aspects that extend these models to ERT and aspects that were missing from the reports. Finally, based on our findings and previous work we suggested a comprehensive framework for ERT that can be used to design teachers’ professional development necessary for effective remote teaching in both emergency and routine times.
KerkoCite.ItemAlsoKnownAs: 10.25304/rlt.v31.2982 2339240:ANPQTXHM 2405685:8BBFIQT8
Keywords: COVID-19 pandemic; digital pedagogy; e-learning; emergency remote teaching; information and communication technology; online learning

Bridge or Barrier – Does generative AI contribute to more culturally inclusive higher education and research? - Atanasova, Dimitrinka (2023)
Whilst the ability of generative AI to produce text in English has been widely covered, the implications of its ability to translate and act as a cultural broker into English have received less att…
KerkoCite.ItemAlsoKnownAs: 2405685:6SRCZ3LI 2486141:TJRDQHQD

Learning Curve: Progress in the Replication Crisis - Angrist, Noam; Cullen, Claire; Ainomugisha, Micheal; Bathena, Sai Pramod; Bergman, Peter; Crossley, Colin; Letsomo, Thato; Matsheng, Moitshepi; Panti, Rene Marlon; Sabarwal, Shwetlena; Sullivan, Tim (AEA Papers and Proceedings, 2023)
We present detailed monitoring data across a five-country randomized trial of phone-based targeted tutoring–one of the largest multicountry replication efforts in education to date. We study an approach shown to work in Botswana and replicated in India, Kenya, Nepal, the Philippines, and Uganda. While the existing literature often finds diminishing effects as proof-of-concept studies are replicated and scaled, we find the opposite: implementation fidelity (the degree of targeted educational instruction) improves across replications and over time. This demonstrates that replication is not intractable; rather, equipped with mechanisms to learn from experience, organizational “learning curves” can enable effective replication and scale-up.
KerkoCite.ItemAlsoKnownAs: 10.1257/pandp.20231009 2405685:48MA4RDL

Developing dialogic classroom practices through supporting professional agency: Teachers’ experiences of using the T-SEDA practitioner-led inquiry approach - Calcagni, Elisa; Ahmed, Farah; Trigo-Clapés, Ana Laura; Kershner, Ruth; Hennessy, Sara (Teaching and Teacher Education, 2023)
Classroom dialogue is considered productive for learning but rarely observed, and practitioner professional development is needed. This study investigated how 67 teachers across educational phases in six countries contextualised the T-SEDA inquiry toolkit to conduct classroom inquiries and develop new practices. Surveys and inquiry reports yielded insights into how practitioner agency was further developed, with implications for sustainability. Change was evident in self-reported enhanced awareness and understanding of dialogue and use of dialogic strategies. Increases in students’ dialogic participation and plans for dissemination to colleagues were reported.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2023.104067 2405685:ZQQP3GIM
Keywords: Classroom dialogue; Dialogic teaching; Professional development; Professional learning; Reflective inquiry; Teacher agency

Investing in disaster preparedness and effective recovery of school physical infrastructure - Opabola, Eyitayo A.; Galasso, Carmine; Rossetto, Tiziana; Meilianda, Ella; Idris, Yunita; Nurdin, Sukiman (International Journal of Disaster Risk Reduction, 2023)
The importance of functioning education infrastructure for the post-disaster recovery of communities is well-acknowledged. Yet, recent natural-hazard events worldwide have highlighted that school facilities still face many post-disaster recovery-impeding challenges. A significant investment in resilience enhancement through appropriate disaster preparedness and post-disaster recovery management is needed to tackle such global challenges. This paper summarises a series of stakeholder engagements (through interviews and focus group discussions) aimed at providing evidence-based recommendations to foster a more rapid and effective post-disaster recovery of school physical infrastructure in disaster-prone marginalised communities. The case-study community is in Central Sulawesi, Indonesia – a region still recovering from the 2018 Central Sulawesi earthquake, tsunami, and liquefaction, which caused damage to over 1200 schools. The considered stakeholders have significant experience in post-disaster recovery management in Central Sulawesi. This paper identifies early-response funding mechanisms, genuine collaborations between stakeholders, and improved capacity for self-organisation as critical elements for an inclusive, sustainable, safer, and more resilient school physical infrastructure. Although the discussion in this paper focuses on Central Sulawesi, the project's outcomes are scalable to other regions in Indonesia, South-East Asia, and other disaster-prone developing nations.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijdrr.2023.103623 2339240:F6Y6I49L 2405685:AFUPK9YY
Keywords: Disaster risk reduction; Preparedness; Resilient recovery; School physical infrastructure; Stakeholder engagement

Education and Climate Change: How to develop skills for climate action at school age? - Bos, Maria Soledad; Schwartz, Liora (Inter-American Development Bank, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:7VKWIMG5 2405685:5RGQCWRG

Transforming Teaching, Education & Learning Directors' Report 2022 - 2023 - T-TEL (Transforming Teacher Education and Learning, 2023)
T-TEL's 3rd Annual General Meeting (AGM) Report
KerkoCite.ItemAlsoKnownAs: 2339240:QIY6C2M5 2405685:9HQR35CW

Girls’ Digital Literacy in the East Asia and Pacific Region - UNICEF EAPRO (UNICEF East Asia and Pacific Regional Office, 2023)
Spotlight on Cambodia, Indonesia, Lao PDR, Timor-Leste and Viet Nam
KerkoCite.ItemAlsoKnownAs: 2339240:B29N39XP 2405685:HMBTKPFM

Viet Nam is among few countries demonstrating gender parity in digital skills and the use of internet - UNICEF Viet Nam (UNICEF Viet Nam, 2023)
On International Day of Girls in ICT, new analysis warns that girls* are being left behind in many countries in an increasingly connected world
KerkoCite.ItemAlsoKnownAs: 2339240:B9BI4TRN 2405685:EFU9EG22

5 strategies for cultivating champions to scale education initiatives - Mukoyi, Tendekai; Qargha, Ghulam Omar (Youth Impact, 2023)
KerkoCite.ItemAlsoKnownAs: 2405685:Y7APUWF8

Approval of Multiplier Grant to Ukraine as Accelerated Funding - Global Partnership for Education (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:MBY5PT68 2405685:AR2K4ZK2

The global prevalence of ADHD in children and adolescents: a systematic review and meta-analysis - Salari, Nader; Ghasemi, Hooman; Abdoli, Nasrin; Rahmani, Adibeh; Shiri, Mohammad Hossain; Hashemian, Amir Hossein; Akbari, Hakimeh; Mohammadi, Masoud (Italian Journal of Pediatrics, 2023)
Abstract Background Attention-Deficit / Hyperactivity Disorder is a developmental neurological disorder that has three basic characteristics: Attention Deficit, Hyperactivity, and impulsivity. This study aimed to investigate the prevalence of ADHD in children and adolescents. Methods This investigation was carried out using the meta-analysis method under PRISMA guidelines. Until October 2020, the articles were gathered by scanning PubMed, Scopus, WOS, and Science Direct databases. The second version of Comprehensive Meta-Analysis software was used to run analyses after extracting data from chosen papers. At a significance level of 0.05, the I 2 test was used to analyze study heterogeneity, and the Egger test was used to assess publication bias. Results This analysis includes 61 cross-sectional research, with 53 research used to determine the prevalence of ADHD in children, 7.6% of 96,907 children aged 3 to 12 years had ADHD (95% confidence interval: 6.1–9.4%), and 5.6% of teenagers aged 12 to 18 years have ADHD (95% confidence interval: 4.8-7%). The prevalence of ADHD in children and adolescents according to the DSM-V criterion is also higher than previous diagnostic criteria, according to studies. Conclusion The findings of this study based on meta-analysis show the high prevalence of attention deficit hyperactivity disorder (ADHD). The findings of this study demonstrate the importance of management and policy in the treatment and control of ADHD in children and adolescents.
52 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.1186/s13052-023-01456-1 2339240:FW6NMPWT 2405685:YWI8SCYA
Keywords: ⛔ No INSPIRE recid found

7 Facts About Education in Laos - Philipp, Jennifer (The Borgen Project, 2023)
Education in Laos has improved in recent times due to domestic changes and international help. These interventions have focused on...
KerkoCite.ItemAlsoKnownAs: 2339240:SBE6Q759 2405685:MKSSYP87
Keywords: ⛔ No INSPIRE recid found

PISA 2022 Results (Volume I and II) - Country Notes: Ukrainian regions (18 of 27) - OECD (2023)
The Programme for International Student Assessment (PISA) assesses the knowledge and skills of 15-year-old students in mathematics, reading and science. The tests explore how well students can solve complex problems, think critically and communicate effectively. This gives insights into how well education systems are preparing students for real life challenges and future success. Ukraine participated for the first time in PISA in 2018; in 2022, survey operations could not be completed successfully in the regions most affected by war, and results refer only to 18 out of 27 regions. The designation “Ukrainian regions (18 of 27)” refers to the 18 PISA-participating jurisdictions of Ukraine: Cherkasy Oblast, Kirovohrad Oblast, Poltava Oblast, Vinnytsia Oblast, Chernihiv Oblast, Kyiv Oblast, Sumy Oblast, the City of Kyiv, Zhytomyr Oblast, Odesa Oblast, Chernivtsi Oblast, Ivano-Frankivsk Oblast, Khmelnytskyi Oblast, Lviv Oblast, Rivne Oblast, Ternopil Oblast, Volyn Oblast and Zakarpattia Oblast. By comparing results internationally, policy makers and educators in Ukraine can learn from other countries’ policies and practices.
KerkoCite.ItemAlsoKnownAs: 2339240:JBI7XPW4 2405685:EP52HS3K

Adaptive pedagogical strategies responding to emergency remote teaching – immediate responses of Hungarian primary school teachers - Horváth, László (Research in Learning Technology, 2023)
Digital disruption is not a new phenomenon in education; however, it has become more prominent during the COVID-19 pandemic due to school closures and the related emergency remote teaching (ERT) period. Our study aims to explore the different pedagogical strategies that primary school teachers adopted during this period and determine how successful these strategies were in involving and engaging students. Altogether, 4028 teachers from 343 primary schools answered our online survey from all the regions of Hungary. The sample adequately represents the Hungarian primary school teacher population in terms of gender and age. We used cluster analysis and identified four clusters of pedagogical strategies; then, we used analysis of variance to explore how teachers’ digital competence and their ability to involve students in online learning varied across different clusters. Our analysis grasps the complexity of the issue, as it shows that two rather distinct strategies were both successful in involving students, and thus, there is no single solution best suited to digital learning. Overall, digitally competent teachers loosened the originally strict structure of education and provided more feedback, which proved to be an important element in successfully involving students in digital learning during ERT. The framework validated in our research can be used by policymakers and school administrators in different national and educational contexts, enabling them to understand the complexity of online teaching and learning. Furthermore, our results can offer some practical pointers for school teachers on how to combine different pedagogical strategies.
KerkoCite.ItemAlsoKnownAs: 10.25304/rlt.v31.2978 2339240:V9P3ULX9 2405685:BYRGHATH
Keywords: COVID-19; ICT integration in education; cluster analysis; teachers’ digital competence

Teachmint pivots to focus solely on digitizing schools - Vardhan, Gyan; Upadhyay, Harsh (ENTRACKR, 2023)
Edtech startup Teachmint is now eyeing a bigger chunk of the education pie by offering their software to help digitize schools
KerkoCite.ItemAlsoKnownAs: 2405685:98TRFBE3

Efficacy of an Adaptive Game-Based Math Learning App to Support Personalized Learning and Improve Early Elementary School Students’ Learning - Bang, Hee Jin; Li, Linlin; Flynn, Kylie (Early Childhood Education Journal, 2023)
This study investigates whether using My Math Academy, which provides personalized content and adaptive embedded assessments to support existing curricula, can improve learning outcomes and engagement for kindergarten and first grade students (N = 505 treatment, 481 control). Findings indicate that students using My Math Academy made significant learning gains in math relative to children who did not. More skills mastered in My Math Academy was associated with greater learning gains on the external assessment, with the greatest impacts among students with lower levels of math knowledge, where there was more room for growth and on the most difficult skills. Teachers surveyed found My Math Academy easy to use in their classrooms and recognized it as a valuable learning resource that supplemented their existing curricula to improve students’ engagement, motivation, and confidence in learning math.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10643-022-01332-3 2339240:ACCHG7IU 2405685:WT3YZ6CJ
Keywords: Adaptive instructional systems; Early childhood education; Game-based learning; Math learning; Personalized learning

Unpacking K-12 teachers’ technology-supported, equitable practices: A mixed-methods systematic review - Cheah, Yin Hong; Oliveri, Anna R.; Hughes, Joan E. (Teaching and Teacher Education, 2023)
We conducted a mixed-methods systematic review of research literature from 2009 to 2019 to unpack researchers' conceptualizations about, approaches toward, and environmental supports in place that framed K-12 teachers' technology-supported, equitable practices. Findings revealed that equitable learning with technology was conceptualized as: (1) lifting students up through a neoliberal perspective; (2) attending to individual needs; (3) empowering students’ agency and civic participation; and (4) providing equal learning opportunities. Technology approaches and environmental supports in tandem with these four conceptualizations are articulated. Finally, we discuss the need for teachers to be reflective practitioners and critical enquirers when leveraging technology to promote equitable learning.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.tate.2022.103984 2339240:QJPU535F 2405685:NU3MR86D
Keywords: Digital equity; Equitable learning; K-12 teachers; Marginalized students; Systematic review; Technology use

Teachers for All: Improving primary school teacher deployment in Zambia - Kabir, Mabruk (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:CGIES8TI 2486141:WLFQX6S7

2022 Annual School Census Report - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:38CKEZFQ 2405685:QGJ7924G

Interview with the Center for National Distance Learning and Open School on data governance practices within the Ghana Ministry of Education. - CENDLOS (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:9N63SQZZ 2339240:A3P7Y95M 2405685:AAK65MWF 2405685:KI7ZJ29W

Interview with the National Teaching Council on data governance practices within the Ghana Ministry of Education. - Daniel, Asai Boso (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:KQX8LW2T 2405685:93DQHEKS

Interview with the Ghana Library Authority on data governance practices within the Ghana Ministry of Education. - Dennis, Mawuli Dakudzie (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:LDW4WJHK 2405685:BRPTDPR4

Teaching away from school: Do school digital support influence teachers’ well-being during Covid-19 emergency? - Diaz Lema, Melisa L.; Rossi, Lidia; Soncin, Mara (Large-scale Assessments in Education, 2023)
The Covid-19 pandemic coerced the closure of most schools around the world and forced teachers and students to change teaching and learning methods. Emergency Remote Teaching (ERT) generated consequences to teachers and students in terms of learning outcomes and personal well-being. This study focuses on teachers’ individual and working environment well-being in ERT conditions and intends to explore which factors related to the provision of digital equipment and the implementation of digital strategies by schools explain the school effect on both typologies of well-being during the Covid-19 emergency. To do so, data collected in the Responses to Educational Disruption Survey (REDS) across three countries were used, and a two-step analysis was conducted. A first step involves the use of linear mixed effect models to assess the school effect on teachers individual and working environment well-being. In the second step Regression Trees (RT) are used to investigate which factors and policies related to digital tools explained the identified school effects. The results show that schools and countries played a role in determining teachers perceived well-being during the Covid-19 disruption, in particular the school level explains more than 7% of the work environment well-being and 8% of individual one. In the second step of the analysis results show that a high positive effect on school environment well-being is observed when the school’s activity is not influenced by policies limiting the use of online tools and when teacher’s readiness for remote teaching, like the development of technical skills and the provision of internet access and digital devices, is met. To the best of our knowledge, this is the first study that evaluates the impact of digital tactics and instruments provided by schools on teachers’ well-being on a large scale.
KerkoCite.ItemAlsoKnownAs: 10.1186/s40536-023-00159-7 2339240:EYHNSXZ8 2405685:TCVR345K
Keywords: Covid-19; Digital Education and Educational Technology; REDS data; School digital support; School effect; Teachers’ well-being

Interview with the Ghana Education Service on data governance practices within the Ghana Ministry of Education. - Fred, Binkorang (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:6SUJY7SC 2405685:NPGMPZLS

Interview with the Statistics, Research & Information Management Directorate on data governance practices within the Ghana Ministry of Education. - Sackey, Robert (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:RGTDU93T 2405685:U8P9D9ZD

8 stages of Data lifecycle management - Deshpande, Rucha (scilife.io, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:6KDDVYE2 2405685:CBZ2XPK4

Ukraine Education Cluster: Basic standards for Digital Learning Centers - Education Cluster; Save the Children; UNICEF (2023)
Manual and Guideline in English on Ukraine about Education and Health; published on 22 Mar 2023 by Education Cluster, Save the Children and 2count other organizations
KerkoCite.ItemAlsoKnownAs: 2339240:VNVHB9NF 2405685:8CXXF933

Where do teachers go, and where do they stay? - Lurvink, Anne-Fleur; Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alasdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn; Godwin, Katie; Godwin, Patricia Espinoza-Revollo, Yusuf Ali, Oliver Garrod, Paul Atherton, Alasdair Mackintosh, Ana Ramirez, Iman Beoku-Betts, Björn Haßler and Katie, Anne-Fleur Lurvink (EdTech Hub, 2023)
In Sierra Leone, a government payroll position is tied to the teacher, not the school, meaning teachers can change schools once they go on the payroll. This leads to certain schools being chronically understaffed. It also suggests that deploying teachers to rural and understaffed schools (or putting teachers already there on payroll) might not tackle high pupil-to-qualified-teacher ratios in the longer term. Investigating the school-to-school movement of payroll teachers can help us understand where teachers go after they go on the payroll and how long they stay in a given school. We also looked at overall movement nationally to identify areas of the country that are outliers in terms of high and low retention of teachers.
KerkoCite.ItemAlsoKnownAs: 2405685:LC8X4TCC

Access to and use of technology by primary school teachers: A survey in the 23 regions of Madagascar - Rasolohery, Hasiniavo; Koomar, Saalim; Mitchell, Joel (EdTech Hub, 2023)
The Madagascar Ministry of National Education, through the National Institute for Pedagogical Training, plans to use new technology in teacher training for early-stage reading and writing in Malagasy. This initiative is undertaken within the framework of the Madagascar Basic Education Support Project. The main objective is to train 5,000 teachers of the T2 class remotely, drawing inspiration from systems such as the Distance Education for Primary Teachers (FADEP).
KerkoCite.ItemAlsoKnownAs: 2339240:V4Z9QSPV 2405685:9NYHCGPM

Access to and use of technology by primary school teachers: A survey in the 23 regions of Madagascar - Rasolohery, Hasiniavo; Koomar, Saalim; Mitchell, Joel; Mitchell, Saalim Koomar and Joel, Hasiniavo Rasolohery (EdTech Hub, 2023)
The Madagascar Ministry of National Education, through the National Institute for Pedagogical Training, plans to use new technology in teacher training for early-stage reading and writing in Malagasy. This initiative is undertaken within the framework of the Madagascar Basic Education Support Project. The main objective is to train 5,000 teachers of the T2 class remotely, drawing inspiration from systems such as the Distance Education for Primary Teachers (FADEP).

Radio Learning Brings Hope and Education to Displaced Children like Awana in North-East Nigeria | UNICEF Nigeria - Adebayo, Folashade (UNICEF Nigeria, 2023)
Through funding from donors, UNICEF is supporting radio learning classes and radio clubs as alternative learning pathways in north-east Nigeria.
KerkoCite.ItemAlsoKnownAs: 2339240:CAY3ZSRY 2405685:TM4QX2FQ

Taking Stock: Vietnam Economic Update, March 2023 - World Bank (2023)
Vietnam’s economic growth is projected to ease to 6.3 percent in 2023 from a robust 8 percent last year, as services growth moderates and higher prices and interest rates weigh on households and investors, according to the World Bank’s latest Taking Stock report.
KerkoCite.ItemAlsoKnownAs: 2339240:FGQZBRIZ 2405685:MNMNF9PB

Situational Analysis Report on the Rights of Persons with Disabilities in Viet Nam - United Nations Development Programme (UNDP, 2023)
This Situational Analysis Report on the Rights of Persons with Disabilities in Viet Nam reveals that the country is poised to harness its increased resources
KerkoCite.ItemAlsoKnownAs: 2339240:4N5N9CHV 2405685:99ZWTQT6

Pakistan Education Sector Working Group flood response performance monitoring dashboard (as of 28 February 2023) - Pakistan | ReliefWeb - Education Sector Working Group (2023)
Infographic in English on Pakistan about Contributions, Coordination, Flash Flood, Flood and more; published on 9 Mar 2023 by Education Cluster, Save the Children and 2count other organizations
KerkoCite.ItemAlsoKnownAs: 2339240:5CQRIMY5 2405685:TQ27WTTI

First Lessons from Our Study: Optimising Messaging for Returns to School - Kably, Nathan; Mitchell, Joel; Zhao, Annette; D'Rozario, Jonny (EdTech Hub, 2023)
This blog examines the valuable insights gained from EdTech Hub's initial research on the use of messaging (primarily text messaging) to assist caregivers in promoting their children's school attendance. In this blog, we delve into the workings of messaging mechanisms and share our study findings. Additionally, we outline critical considerations for those interested in developing a comparable intervention. Read on to learn more...
KerkoCite.ItemAlsoKnownAs: 2339240:4T3GP6TA 2405685:IQRXCPLV

MEWAKA in Tanzania: Emerging findings on tech-supported teacher professional development - Koomar, Saalim; Massam, Winston; Anthony, Gervace; Mrope, Winifrida; Adam, Taskeen; Hennessy, Sara; Mtenzi, Fredrick; Proctor, Jamie; Komba, Aneth; Mwakabungu, Fika; Barretto, Johnpaul; Barretto, Winston Massam, Gervace Anthony, Winifrida Mrope, Taskeen Adam, Sara Hennessy, Fredrick Mtenzi, Jamie Proctor, Aneth Komba, Fika Mwakabungu and Johnpaul, Saalim Koomar (EdTech Hub, 2023)
MEWAKA (Mafunzo Endelevu kwa Walimu Kazini, or Teachers’ Continuous Professional Development (TCPD)) is a landmark teacher professional development programme being implemented by the Government of Tanzania. The programme is decentralised, with teacher learning based in schools and focused on semi-structured Communities of Learning (CoLs). CoLs are spaces where teachers can gather weekly to discuss and reflect on issues most relevant to their schools as well as learn and improve their pedagogical skills. Peer facilitators help teachers to collaboratively solve problems, learn new approaches to improve their practice, and generally create a culture of reflection and school improvement.
KerkoCite.ItemAlsoKnownAs: 2339240:AQZAQSU7 2405685:KMN7H8UA

The charm or chasm of digital personalized learning in education: Teachers’ reported use, perceptions and expectations - Van Schoors, Rani; Elen, Jan; Raes, Annelies; Vanbecelaere, Stefanie; Depaepe, Fien (TechTrends, 2023)
Although digital personalized learning (DPL) is assumed to be beneficial for the student as well as the teacher, the implementation process of DPL tools can be challenging. Therefore, the aim of our study is to scrutinize teachers’ perceptions towards the implementation of DPL in the classroom. A total of 370 teachers from primary and secondary education (students aged 6–18 years old) were questioned through an online survey. An overview of descriptive results is presented regarding (1) teachers’ reported technology use, (2) their perceptions towards adaptivity and dashboards in DPL tools and (3) their expectations of support in view of implementing DPL. Based on a cluster analysis, three teacher clusters are distinguished. Results reveal all three clusters had positive perceptions towards DPL. Nevertheless, there is great variety in reported use of DPL tools.
KerkoCite.ItemAlsoKnownAs: 10.1007/s11528-022-00802-0 2339240:IPG87SFI 2405685:UEIBMJ9K
Keywords: Adaptive technology; Cluster analysis; Digital Education and Educational Technology; Digital personalized learning; Educational technology; Teachers

The Charm or Chasm of Digital Personalized Learning in Education: Teachers’ Reported Use, Perceptions and Expectations - Van Schoors, Rani; Elen, Jan; Raes, Annelies; Vanbecelaere, Stefanie; Depaepe, Fien (TechTrends, 2023)
Although digital personalized learning (DPL) is assumed to be beneficial for the student as well as the teacher, the implementation process of DPL tools can be challenging. Therefore, the aim of our study is to scrutinize teachers’ perceptions towards the implementation of DPL in the classroom. A total of 370 teachers from primary and secondary education (students aged 6–18 years old) were questioned through an online survey. An overview of descriptive results is presented regarding (1) teachers’ reported technology use, (2) their perceptions towards adaptivity and dashboards in DPL tools and (3) their expectations of support in view of implementing DPL. Based on a cluster analysis, three teacher clusters are distinguished. Results reveal all three clusters had positive perceptions towards DPL. Nevertheless, there is great variety in reported use of DPL tools.
KerkoCite.ItemAlsoKnownAs: 10.1007/s11528-022-00802-0 2339240:9J7AXDVG 2405685:LATP7UQ7
Keywords: Adaptive technology; Cluster analysis; Digital personalized learning; Educational technology; Teachers

Sierra Leone Case Study: Review of Technology-Based Interventions to Address Child Marriage and Female Genital Mutilation - Data-Pop Alliance; United Nations Population Fund; UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:CEHUC88T 2405685:S24H3HV7

Cambodia Digital Education Landscape Scan - World Education (2023)
The Cambodian Ministry of Education, Youth and Sport (MoEYS) is committed to increasing the efficiency and effectiveness of teaching and learning across classrooms, school libraries, teacher training centers, and other educational institutions by leveraging digital tools and resources. In August 2022, MoEYS shared a draft National Statement of Commitment To Transform Education System in Cambodia in which advancing digital education is one of eight top priorities.1 In line with MoEYS’s national priorities, World Education, (WE) has been contracted by UNICEF under CDPF III to support the design and development of an improved digital educational environment for educators and learners that will enhance outcomes by encouraging active learning, enabling greater differentiation and personalization in instruction, improving cooperation among learners, educators, students, and increasing positive attitudes towards learning. From October 2022 to January 2023, WE conducted a Cambodia Digital Education landscape scan to map existing efforts and assess their quality, effectiveness and impact, accessibility and adoption, and efficiency and sustainability. The goal of this national landscape scan was to gain a deeper understanding of the existing or emerging digital learning interventions for teachers and students, including platforms and centers, that were or are in use and for whom and in what contexts they are effective or not. WE employed a mixed-methods approach that featured key informant interviews, online surveys, desk research, focus group discussions with teacher educators and general education teachers. In total, research was conducted with over 500 stakeholders in diverse education settings across 20 provinces. It is important to note that there were two limitations of our study: the first that there was a high proportion of teacher educators (approximately 62%) from our sample in comparison to general education teachers (30%), which skewed results and made it difficult to generalize; the team sought to mitigate this by disaggregating responses by teacher role where possible. The second limitation is that the online surveys were distributed digitally so teachers in rural areas where internet access is limited would not have been able to access the online survey. The landscape scan culminated in a co-design workshop in February 2023 bringing together 25 participants from technical departments of MoEYS, other relevant government agencies, and development partners to triangulate findings and co-develop recommendations.
KerkoCite.ItemAlsoKnownAs: 2339240:FFQ88P88 2405685:DNTQUVAC

Ensuring Equality in Education Access: The Dynamics and Challenges for Vietnamese Ethnic Minority Girls - Yen, Nguyen Thi Hong; Hoi, Nguyen Van (Journal of Contemporary Sociological Issues, 2023)
Education access is one of the critical human rights that has been decided for the development of everyone and has been codified in the international and national legal systems. Despite important achievements in ensuring and promoting fundamental human rights in general, with the characteristics of being one of the most vulnerable in society, ethnic minority girls experienced discrimination and double inequality in benefiting their rights, including access to education. Regarding the education right of girls in the ethnic minority in Vietnam today, the following article focuses on the following matters: (i) Analysing the Vietnamese legal framework in ensuring the education right of ethnic minority girls; (ii) Presenting the difficulties and challenges in ensuring this right for ethnic minority girls in Vietnam; (iii) Proposing necessary recommendations for the Government to improve the enjoyment of the right for Vietnamese ethnic minority girls in the upcoming time. Keywords: Education Access, Equality, Ethnic Minority Girls, Vietnam, Women's rights
Number: 1 KerkoCite.ItemAlsoKnownAs: 10.19184/csi.v3i1.31549 2339240:KFMMHW3M 2405685:7BFS8ESR

KEY FIGURES: 5th Rwanda Population and Housing Census (PHC) - National Institute of Statistics of Rwanda. (National Institute of Statistics of Rwanda., 2023)
The fifth Population and Housing Census in Rwanda, was conducted in August 2022. The Census operation was coordinated by the National Census Commission. Various census technical and administrative structures have been put in place to ensure a successful census operation.

The State Service of Education Quality of Ukraine presented EvaluEd system - The State Service of Education Quality of Ukraine (2023)
"A year ago, we set a goal to implement the EvaluEd information and analytical system by 2025. Today, this system has been tested during teachers`
KerkoCite.ItemAlsoKnownAs: 2339240:HWYBZ849 2405685:LR6THX5M

Digital 2023: Sierra Leone - Kemp, Simon (DataReportal – Global Digital Insights, 2023)
All the data, insights, and trends you need to help you make sense of the “state of digital” in Sierra Leone in 2023, including detailed statistics for internet use, social media use, and mobile use, as well as user numbers for all the top social platforms.
KerkoCite.ItemAlsoKnownAs: 2339240:RA9DJ5IT 2405685:G5WRLUDH

The RISE Education Systems Diagnostic: A Tool for Identifying Strategic Priorities for Education System Reform - RISE (RISE Programme, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:L6DMXC88 2405685:EDFKIHY7 4656463:HLNCGPFR

Forced Displacement and Education: Building the Evidence for What Works - Burde, Dana; Coombes, Andrea; De Hoop, Thomas; Guven, Ozen; Okhidoi, Otgonjargal; Ring, Hannah; Rothbard, Victoria; Holla, Chinmaya (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:J9I6HCRP 2405685:F7QHKN3L

Continuous Teacher Training Goes Nationwide in Tanzania - World Bank (World Bank, 2023)
A World Bank-funded program is piloting continuous professional development for primary school teachers in Tanzania.
KerkoCite.ItemAlsoKnownAs: 2339240:6CUKPF4H 2405685:RR47SXDT

Annual Report 2021 - Solve Education! (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:RH5G2MPB 2405685:JVQQPGU8

Exploring the benefits and challenges of AI-language learning tools - Rebolledo Font de la Vall, Roxana; Gonzalez Araya, Fabian (International Journal of Social Sciences and Humanities Invention, 2023)
AI language learning tools are computer programs or software applications that use artificial intelligence (AI) algorithms to help users learn and improve their skills in a foreign language. These technologies have a lot of benefits, such as the ability to save time and speed up learning, to give students personalized learning experiences, and to help them learn about other cultures. In this study, the scientific literature was looked at to find out the pros, cons, opportunities, and challenges of using AI language learning tools, such as the need for more human interaction, the complexities of language in context, and the fact that training needs a lot of data. In the future, these AI tools could be used to make changes, like combining VR and AR, developing better algorithms for processing natural language, and using more advanced algorithms for adaptive learning. By addressing these problems and limitations, AI learning systems could become even more powerful and valuable tools for learning languages. Their integration is critical to improving the effectiveness and efficiency of learning user experience solutions.
KerkoCite.ItemAlsoKnownAs: 10.18535/ijsshi/v10i01.02 2405685:5DI6FYSP 2486141:SRGMXZD2

Nigerian schools: Flogged for speaking my mother tongue - Cecilia Macaulay (BBC News, 2023)
Nigeria wants local languages to replace English in primary education, but some say it's not practical.
KerkoCite.ItemAlsoKnownAs: 2405685:B6YLK9BX 4042040:CFVHDDHY

Towards Systemic EdTech Testbeds: A Global Perspective - Vanbecelaere, Stefanie; Adam, Taskeen; Sieber, Carmen; Clark-Wilson, Alison; Boody Adorno, Katie; Haßler, Björn; Open Development & Education (GETN, 2023)
KerkoCite.ItemAlsoKnownAs: 10.53832/opendeved.0285 2339240:3NTUF39G 2405685:HPMBNHEY

Educational loss at times of crisis: the role of games in students’ learning in Palestine and Iraq - Ali, Kareema; Burgos, Daniel; Affouneh, Saida (Sustainability, 2023)
This study examines the role of educational games in compensating for educational loss and their impact on students’ motivation towards learning during crises in Palestine and Iraq. Additionally, the study considers the challenges facing the employment of this strategy and ways to overcome these challenges. By performing separate open semi-structured interviews with a group of 10 educators from university professors, teachers, and educational supervisors, the study used the qualitative descriptive approach which designs multiple case studies. The results showed the prominent role that educational games play in increasing students’ motivation towards learning and compensating for educational loss through what they add to the fun and suspense in the learning process and how they shorten time and effort and help students to engage and cooperate in acquiring knowledge, skills, and values. The results also reveal common challenges that face the employment of educational games. These challenges are social, economic, technological, challenges related to school environment, and psychological challenges. The study shows the possibility of overcoming these challenges by providing funding sources, preparing plans to employ educational games, and developing teachers’ capabilities to implement them in their teaching practices.
Number: 6 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/su15064983 2339240:CAV7LEBU 2405685:WGXG4UM5
Keywords: crises; educational games; educational loss; motivation

Ed-Tech landscape and challenges in Sub-Saharan Africa - Adediran, Adedeji; Adedeji, Abdulfatai; Nwosu, Emmanuel; Nwugo, Emmanuel; Nnamani, Great (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:HL8VRGVT 2405685:W6DWUGC9

Ed-Tech landscape and challenges in Sub-Saharan Africa - Adeniran, Adedeji; Adedeji, Abdulfatai; Nwosu, Emmanuel; Nwugo, Emmanuel; Nnamani, Great (Southern Voice, 2023)
This study examines the adoption of education technology (ed-tech) in primary and secondary education in 10 sub-Saharan African countries: Nigeria, South Africa, Sierra Leone, Uganda, Kenya, Tanzania, Cameroon, Benin, Malawi, and Senegal. The study assesses the development and implementation of ed-tech policies and programmes in the region, exploring how far ed-tech has advanced learning outcomes, improved access, and reduced education inequalities within and between countries in sub-Saharan Africa.
KerkoCite.ItemAlsoKnownAs: 2339240:RUBC88S3 2405685:TE8RFCSM

Autism in Africa: Prevalence, diagnosis, treatment and the impact of social and cultural factors on families and caregivers. A review - Aderinto, Nicholas; Olatunji, Deji; Idowu, Oluwatobi (Annals of Medicine and Surgery, 2023)
This paper presents a narrative review of current knowledge on autism in Africa, including prevalence, diagnosis, treatment and the impact of social and cultural factors on families and caregivers. The prevalence of autism in Africa is estimated to be similar to that in other regions. However, diagnosis and treatment access remain limited due to various challenges, such as a shortage of specialised healthcare professionals and resources, a lack of awareness and understanding of autism spectrum disorder (ASD) among healthcare providers, and cultural stigma surrounding mental health and developmental disorders. Alternative therapies are commonly used with other therapies, but their effectiveness is often unproven. The impact of ASD on families and caregivers in Africa is significant, with many facing challenges in accessing support services and coping with stigma. Efforts are being made to increase awareness and reduce the stigma around ASD in African communities, but more research is needed on effective interventions and culturally appropriate treatments. Policy recommendations include increasing resources and training for healthcare professionals, improving access to evidence-based interventions and promoting community awareness and support. With improved understanding and investment, the quality of life of individuals with ASD in Africa can be significantly improved.
KerkoCite.ItemAlsoKnownAs: 2339240:F4T7VNHT 2405685:KL7RIHQZ
Keywords: Africa; autism; neurology

AKU, Gilgit-Baltistan govt partner to boost teacher capacity | The Aga Khan University News - Aga Khan University (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:ZMELENAS 2405685:64PI7KX6

Women’s empowerment through social media: A comparative study of Brunei Darussalam and Malaysia - Ahmad, Nehaluddin; Hj Abdul Aziz, Hjh Hanan; Zulkiffle, Norulaziemah (Journal of Southeast Asian Research, 2023)
In today’s world, social media are one of the most effective tools that can be used to further women’s empowerment efforts, which is a significant indicator of a country’s overall level of development. Before social media, women suffered a lot, especially when they lacked knowledge. However, through social media, women’s empowerment is rapidly growing as social media are easy to access, and they are learning more about their rights and powers. This article discusses the definition of women’s empowerment as well as the definition of social media in an effort to achieve its purpose. First and foremost, the purpose of this research is to provide an overview of how far social media have contributed to women’s empowerment. Further, this article will analyse women’s empowerment in Brunei and Malaysia using a comparative approach. In the end, it can be concluded that despite the fact that there is no doubt that women in today’s society have access to numerous social media platforms that support them in their day-to-day lives and assist them in empowering themselves, there are obstacles, such as cybercrime, that prevent women from upholding their empowerment. It is recommended that each country must provide and improve its national policies and laws to protect women, particularly regarding their use of social media.
KerkoCite.ItemAlsoKnownAs: 2339240:DNXTF9V2 2405685:JFV8RHWC
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

2023 Cost-Effective Approaches to Improve Global Learning: What does recent evidence tell us are "Smart Buys" for improving learning in low- and middle-income countries? - Akeyampong, K; Andrabi, T; Banerjee, A; Banerji, R; Dynarski, S; Glennerster, R; Grantham-McGregor, S; Muralidharan, K; Piper, B; Ruto, S; Saavedra, J; Schmelkes, S; et al. (World Bank, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:F52H6KKX 2405685:NP2EKHJP 2405685:V968A8F8 2486141:PEQB9DK3
Keywords: ⛔ No INSPIRE recid found

Guidance note on using implementation research in education - Allison, C (Building Evidence in Education (BE2), 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:LNYGTD8Y 2405685:MPR522L4

The Latest Tanzanian National Panel Survey Shows Progress in Education - Amankwah, Akuffo; Palacius-Lopez, Amparo; Gul, Maryam (2023)
The state of education in a country has cascading impacts across multiple facets of development. In line with SDG 4, providing equitable quality education remains a key mission for countries, especially those with low literacy rates. Zooming in on Tanzania...
KerkoCite.ItemAlsoKnownAs: 2339240:WCFIJEQE 2405685:2HP9RXUH

The “MATHEMA” application as a mathematics learning media for children with Down syndrome - Amatullah, Fadilah Halfa; Annisi, Mughi Puspa (Journal of ICSAR, 2023)
This research aims to create application-based learning media to help ease children with Down syndrome in learning mathematics. The research method used is a qualitative method, with research subjects of teachers, parents, and children with Down syndrome grade three SDLB. In accordance with the results of the analysis of objective conditions of the ability, inability, and needs of the subject, as well as theoretical analysis of learning mathematics, a 'Mathema' application was developed, namely an interactive learning media in which there are features to learn about the concept of numbers, number sequences, number symbols, and addition and subtraction operations, which based on conceptual validation is feasible to use and based on empirical validation has proven effective for improving the ability to learn mathematics in the subject so that the findings of the 'Mathema' media are expected a solution for teachers in helping ease learning mathematics in children with Down syndrome
0 citations (Crossref) [2024-04-29] KerkoCite.ItemAlsoKnownAs: 10.17977/um005v7i22023p321 2339240:6ZBSEHTG 2405685:6RPPUB7N
Keywords: ⛔ No INSPIRE recid found

Narrowing the gender digital divide in Pakistan: Mobile phone ownership and female labor force participation - Amber, Hina; Chichaibelu, Bezawit Beyene (Review of Development Economics, 2023)
Abstract The unprecedented growth in access to mobile phones and smartphones has opened up new possibilities in the way people live and work. However, women in developing countries are unable to take advantage of this growth due to certain factors and socio‐cultural norms that give rise to the gender digital divide. In this study, using the nationally representative Pakistan Social and Living Standards Measurement Survey (2019–2020), we investigate the gender and rural–urban (female) digital divide in a country with one of the most considerable digital divides. Furthermore, we employ an instrumental variable approach to study the effect of mobile or smartphone ownership on female labor force participation. The results indicate that institutional and sociocultural norms explain most of the ownership gap of mobile or smartphones between men and women. The instrumental variable approach demonstrates that mobile or smartphone ownership increases the participation of women in the labor force. We also find that the differences between observable characteristics, especially literacy and education, explain the rural–urban digital divide among females. Considering the importance of mobile or smartphone ownership in facilitating women's labor supply decisions, providing women with digital tools and upskilling them has wider implications for their economic well‐being.
KerkoCite.ItemAlsoKnownAs: 10.1111/rode.12994 2339240:T54WZHNB 2405685:HKDUY9UA

Building Resilient Education Systems: Evidence from Large-Scale Randomized Trials in Five Countries - Angrist, Noam; Ainomugisha, Micheal; Bathena, Sai Pramod; Bergman, Peter; Crossley, Colin; Cullen, Claire; Letsomo, Thato; Matsheng, Moitshepi; Panti, Rene Marlon; Sabarwal, Shwetlena; Sullivan, Tim (National Bureau of Economic Research, 2023)
KerkoCite.ItemAlsoKnownAs: 10.3386/w31208 2339240:B5AL6QWY 2405685:AFKK5JK7

Accelerating Digital Inclusion for Women and Girls in Asia and the Pacific - Asian Development Bank (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:7G79A7ZH 2405685:BWQZKPTZ
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Reimagine Tech-Inclusive Education: Evidence, practices, and road map - Asian Development Bank (Asian Development Bank, 2023)
Edition: 0 ISBN: 9789292701864 9789292701857 KerkoCite.ItemAlsoKnownAs: 10.22617/TCS230233 2339240:2QCED3SK 2405685:IM9IKLSU

Second Strengthening Higher Education Project - Asian Development Bank (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:F5UK9J9L 2405685:66435KZD
Keywords: ⛔ No INSPIRE recid found

Ambassador of Timor-Leste to ASEAN presents credentials to Secretary-General of ASEAN - Association of Southeast Asian Nations Secretariat (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:JXJT3LQX 2405685:7YHUJ7JJ

Inclusive educational transitions for refugees with disabilities: Intersectionality and the right to inclusive Education - Bacakova, Marketa (Perspectives on Transitions in Refugee Education, 2023)
The right to education belongs to the fundamental human rights. Its realisation builds the cornerstone for the exercise of other human rights, such as the right to vote, the right to free speech, or the right to work. Nonetheless, more than 260 million children and young people worldwide still lack access to education and 750 million adults remain illiterate (UNESCO 2018, 122). Despite global investments and initiatives such as the Sustainable Development Goals (SDGs), the inequalities prevail not only in the area of access to education. Diverse factors contribute to the failed goal of education for all, such as gender
KerkoCite.ItemAlsoKnownAs: 10.2307/j.ctv32bm1gz.6 2339240:KEWY9GWM 2405685:ZGU6MCG8
Keywords: ⛔ No INSPIRE recid found

2023 Cost-Effective Approaches to Improve Global Learning - What does recent evidence tell us are “Smart Buys” for improving learning in low- and middle-income countries? - Banerjee, A; Banerji, R; Andrabi, T; Dynarski, S; Glennerster, R; Grantham-McGregor, S; Muralidharan, K; Piper, B; Saavedra, J; Yoshikawa, H; Ruto, S; Schmelkes, S (World Bank Group, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:2BGTWZKU 2339240:X7GEK8EA 2405685:9X68BZ9M 2405685:J3TLG7EN 2405685:XW55C644

Digital Africa: Technological Transformation for Jobs - Begazo, Tania; Blimpo, Moussa P.; Dutz, Mark (World Bank Group, 2023)
Digital Africa, Technological Transformation for Jobs examines pathways to produce and promote the expanded use of affordable and attractive digital technologies (DTs) that are appropriate for Sub-Saharan Africa’s growing workforce and facilitate continued learning through use. DTs are defined broadly to include digital and data infrastructure, broadband internet, smart phones, tablets, and computers. They also include specialized management upgrading, worker training, and training in procurement, marketing, logistics, financing, and insurance.
KerkoCite.ItemAlsoKnownAs: 2339240:HSECCCXQ 2405685:CE2YV4CW
Keywords: ⛔ No INSPIRE recid found

Facing the Challenges of Girls’ Education in Pakistan - Bend, May; Baron, Juan (World Bank Blogs, 2023)
Girls’ education is smart economics, and Pakistan has committed to guaranteeing the right of both girls and boys to access quality education (SDG 4).
KerkoCite.ItemAlsoKnownAs: 2339240:687RZHPT 2405685:75GZWIJP

Refugee education: Financing what matters - Benveniste, Luis; Silva, Karishma; Hoogeveen, Johannes (World Bank Blogs, 2023)
At the Global Refugee Forum this week, education stakeholders will pledge to include all refugee children in national education systems. Three major questions arise: what does inclusion mean, why does it matter and how do we get there?
KerkoCite.ItemAlsoKnownAs: 2339240:ALQKVA5M 2405685:VEWR66YZ

Emergency curriculum: An alternative curricular and pedagogical practice for school education - Bharti, Uma; Musthafa, M.N. Mohamedunni Alis (Shodhak : A Journal of Historical Research, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:UF29W84P 2405685:KVHFXEGL
Keywords: ⛔ No DOI found

Study on the ASEAN Digital Economy Framework Agreement - Boston Consulting Group (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:2EI22QLN 2405685:PWX2SZKR 2405685:R4DB7646

Cambodia Introduction and Quick Facts - Britannica (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:8R4HFGR8 2405685:SGYLFNVE

Barriers and Supports for Technology Integration: Views from teachers - Burns, M (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:NLR9P9KT 2339240:VE6BN54S 2405685:8ZMY7CJ8 2405685:D478G32F

Can technology improve the classroom experience in primary education? An African experiment on a worldwide program - Cardim, Joana; Molina-Millán, Teresa; Vicente, Pedro C. (Journal of Development Economics, 2023)
Primary school coverage has been increasing in most developing countries. Yet, it has not been accompanied by signiﬁcant improvements in learning indicators. We implemented a randomized experiment in Angola around the introduction of ProFuturo, a worldwide educational program. The program includes a Computer-assisted Learning (CAL) software directed at improving the regular classroom experience. One year after the program started, we ﬁnd higher familiarity with technology. Teachers miss fewer days of classes and implement better teaching practices. Students become more interested in learning and pro-social. Finally, the program improves students’ test scores in the most popular subject in the CAL platform.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jdeveco.2023.103145 2339240:TBU4TXPC 2405685:V8C3T7HA

Edtech and marginalization: Scaling for learning equity - Castillo, N. M.; Wagner, D; Alrawashde, G; Moog, C (UNESCO GEM Background paper, 2023)
KerkoCite.ItemAlsoKnownAs: 10.54676/ZKZT2998 2405685:GW9DLVYF 2405685:MWQ38NIE

Save Schools in Ukraine - Centre for Information Resilience (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:R98DXCEV 2405685:4VCSX4VJ

Wi De Ya, One Tablet Per School, Sierra Leone - CGA Technologies (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:YP3PPJRH 2405685:X9WGBYV4

V-Dem Dataset v13 - Coppedge, M. et al. (Varieties of Democracy (V-Dem) Project, 2023)
KerkoCite.ItemAlsoKnownAs: 10.23696/VDEMDS23 2405685:NZ5PTPJ9

Live tutoring calls did not improve learning during the COVID-19 pandemic in Sierra Leone - Crawfurd, Lee; Evans, David K.; Hares, Susannah; Sandefur, Justin (Journal of Development Economics, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.jdeveco.2023.103114 2405685:D8BHBGK9

Ed-tech in the Global South: Research gaps and opportunities (Occasional Paper No. 91) - Cueto, Santiago; Balarin, Maria; Saavedra, Mauricio; Sugimaru, Claudia (Southern Voice, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:8Y7C786Q 2405685:4VAWU8ZD

Lao People’s Democratic Republic: Prime Minister’s Decree on Lifelong Learning, issued in 2020 | Institute for Lifelong Learning - Dalbéra, Jean-Pierre (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:MH5689VH 2405685:9YURZAZ5
Keywords: ⛔ No INSPIRE recid found

How technology shapes advice: Professional–parent interaction in a digital pediatric treatment - Dalmaijer, Evi; Pas, Berber; Spooren, Wilbert; Stommel, Wyke (Frontiers in Communication, 2023)
Introduction Technology-enabled treatments (TET) have emerged in pediatric care as an effective solution for early and intensive intervention. There is a lack of research in the field of digitalized health care on the interaction between professionals and parents on which these treatments are based, and at the same time too little is known about the impact of remoteness and technology on interaction in the field of health communication. Method We use a conversation analytical approach to examine the interaction between occupational therapists and parents in one such treatment on a micro level, with a focus on advice-giving and the role of professional and parental authorities in this. Results Our analyses show that professionals in TET work together with the parents of children in treatment to achieve children's rehabilitation goals. In advice-giving in TET, the professionals interactionally downgrade their epistemic and deontic authority, orienting toward the imposition on parents inherent to advice and orienting toward parental authority. Discussion By describing three different patterns of the interactional unfolding of advice-giving, we provide insights into how professionals carefully initiate and return to advice and show how this activity is shaped by the technology used for the interaction. Our study offers a better understanding of how paramedical professionals practice their profession given remoteness and technology and what TET entails interactionally in terms of advice-giving.
KerkoCite.ItemAlsoKnownAs: 10.3389/fcomm.2023.1205883 2339240:3X3RZ6RP 2405685:DLRLGR9D

Access to employment: A comparison of autistic, neurodivergent and neurotypical adults’ experiences of hiring processes in the United Kingdom - Davies, Jade; Heasman, Brett; Livesey, Adam; Walker, Amy; Pellicano, Elizabeth; Remington, Anna (Autism, 2023)
Autistic people face high unemployment rates. One reason for this may be that hiring processes are inaccessible. This study aimed to establish autistic people’s unique experiences of hiring processes in the United Kingdom, by comparing them to the experiences of non-autistic neurodivergent people and neurotypical people. Using qualitative and quantitative data from 225 autistic, 64 non-autistic neurodivergent and 88 neurotypical adults, we identified a series of (dis)similarities in participants’ views and experiences of recruitment for employment. Similarities across the three groups included (1) frustration with the focus on social skills; (2) a perceived need for more flexible hiring processes; (3) a desire for more clarity and (4) the importance of the environment. Participants also acknowledged the important role employers play in one’s decision to disclose a diagnosis or access need. Yet, autistic people faced a set of unique barriers to successful recruitment, over and above those that non-autistic people faced. For example, the perceived pressure to mask autistic traits to succeed and concerns about stigma and discrimination. Participants’ recommendations for improvements included the use of more practical recruitment strategies (e.g. work trials), more clarity about what to expect, and improvements in recruiters’ understanding of the challenges autistic and neurodivergent candidates may face.Lay abstract Autistic people are less likely to have a job than non-autistic people. One reason for this may be that hiring processes (e.g. job applications, interviews) can be challenging for autistic people. To better understand the experiences of hiring processes in the United Kingdom, we asked 225 autistic, 64 neurodivergent (but not autistic) and 64 adults with no reported area of neurodivergence questions about their experiences using an online survey. We found a range of similarities and differences in responses. For example, participants in all three groups were frustrated with the focus on social skills in recruitment and said they wanted more practical methods (e.g. work trials) that help them show their skills and abilities. Autistic and otherwise neurodivergent participants discussed the importance of the environment (e.g. the interview/assessment room) in improving experiences. Participants also discussed how employers can impact whether somebody decides to disclose their diagnosis or needs – or not. Autistic people experienced some barriers to successful recruitment that non-autistic people did not. For example, autistic people felt they had to hide their autistic traits to gain employment and many autistic people were worried about being discriminated against if they disclosed that they were autistic during the hiring process. To make experiences better, our participants said that employers should offer candidates different recruitment methods and give them more information about the hiring process. They also said employers should improve their understanding of autism and other hidden disabilities so they know the challenges that people might face during recruitment.
_eprint: https://doi.org/10.1177/13623613221145377 KerkoCite.ItemAlsoKnownAs: 10.1177/13623613221145377 2339240:YKSBLQQD 2405685:XAUNUHLD

Gilgit-Baltistan sees threefold rise in funds for education sector: Chief secretary - DAWN News (DAWN.COM, 2023)
"If we make our government schools modern and technology-oriented, people will switch from private to public schools," says CS.
KerkoCite.ItemAlsoKnownAs: 2339240:H57D2DE6 2405685:M7YH24AI

Technology in Education: A case study on Thailand – UNESCO Digital Library - Dipendra, K.C. (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:YMK9YPIB 2405685:JEDTWDAF
Keywords: ⛔ No INSPIRE recid found

Flagship Projects - Directorate of Science, Technology & Innovation (Directorate of Science, Technology & Innovation, Government of Sierra Leone, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:94U79QP8 2405685:ZEJRQ8R7

Designing learning technology collaboratively: Analysis of a chatbot co-design - Durall Gazulla, Eva; Martins, Ludmila; Fernández-Ferrer, Maite (Education and Information Technologies, 2023)
Abstract Collaborative design approaches have been increasingly adopted in the design of learning technologies since they contribute to develop pedagogically inclusive and appropriate learning designs. Despite the positive reception of collaborative design strategies in technology-enhanced learning, little attention has been dedicated to analyzing the challenges faced in design processes using a collaborative approach. In this paper, we disclose the collaborative design of a chatbot for self-regulated learning in higher education using an action research approach. We analyze the design process of EDUguia chatbot, which includes diverse evidence from questionnaires and workshops with students and lecturers, as well as intermediary design objects. Based on the qualitative analysis, we identify several challenges that are transversal to the co-design work, as well as specific to the design phases. We critically reflect on the strategies deployed to overcome these challenges and how they relate to decision-making processes, highlighting the need to make stakeholders’ tacit knowledge explicit, cultivate trust-building and support democratic decision-making in technology design processes. We believe that the recommendations we present in this paper contribute to developing best practices in the collaborative design of chatbots for the self-regulation of learning, as well as learning technology in general.
KerkoCite.ItemAlsoKnownAs: 10.1007/s10639-022-11162-w 2339240:5LDCI3BY 2405685:IVSZL6MP

Results – Rapid Scans – The EdTech Hub - EdTech Hub (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:4MLKCQH6 2405685:M78IF9TS 4656463:IAPZ4MLA

Teachers’ Digital Skills & Digital Competency Frameworks for Teaching and Learning - EdTech team (World Bank Group, 2023)
Teachers’ Digital Skills & Digital Competency Frameworks for Teaching and Learning (English)
KerkoCite.ItemAlsoKnownAs: 2339240:S2BHCDCA 2405685:LILBMRRH

What we do – EducAid - EducAid (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:AGW2HFBI 2405685:ZYFV2WII

Leveraging Education in Emergencies for Climate Action - EiE Hub (Geneva Global Hub for Education in Emergencies, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:DJQE6RS5 2405685:LDPAP6F7

Technology in Education: A Case Study on the Philippines - Espinosa, Allen A; Gomez, C Arsenia; Praksis, Miranda A; Adonis, David P; Edna Luz, Abuljon R; Hermosisima, Victoria C; Quinosa Jr, Edwin A; Soliman, Abegail A; De Vera, Jayson L; Claros, Ian Harvey; Cruz, Hardie Gieben; Gonzales, Nepthalie SJ (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:69B6XGVC 2405685:WMR4S8BZ
Keywords: ⛔ No INSPIRE recid found

Torino Process System Monitoring Report: Ukraine 2023 - European Training Foundation (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:2PENYGJV 2405685:TWBKYA2H

AI for Education AI Assessments Event Summary - Fab Inc. (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:RSKXEXU8

National Artificial Intelligence Strategy - Federal Ministry of Communications, Innovation and Digital Economy (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:PB4MH6T7 2405685:G5ZG7T9Z

Climate Change and Education in Kenya - Fitzpatrick, Rachael; Amenya, Donvan (Education Development Trust, 2023)
What impact does climate change have on education, especially in areas which are vulnerable to climate disasters and extreme weather events? In this report, we explore the impact of climate change on schools and learning in six counties in Kenya (Nairobi, Mombasa, Turkana, Tana River, Kwale and Kilifi).
KerkoCite.ItemAlsoKnownAs: 2339240:D863LELH 2405685:XKNUY5HA

New UK funding to boost education opportunities for women and girls in Southeast Asia - Foreign, Commonwealth & Development Office (GOV.UK, 2023)
At the 2023 Education World Forum the International Development Minister launched a Girls’ Education and Skills Programme following the UK-ASEAN Plan of Action.
KerkoCite.ItemAlsoKnownAs: 2339240:8ZYWIH6Z 2405685:F5PI3ZR2
Keywords: ⛔ No INSPIRE recid found

Can A/B Testing at Scale Accelerate Learning Outcomes in Low- and Middle-Income Environments? - Friedberg, Aidan (Artificial Intelligence in Education. Posters and Late Breaking Results, Workshops and Tutorials, Industry and Innovation Tracks, Practitioners, Doctoral Consortium and Blue Sky, 2023)
On current trends the world will fail to reach the objectives set in the UN’s Sustainable Development Goals for Education by 2030 or even within the 21st century. Changing this trend will require a significant acceleration in learning outcomes. Digital personalised learning (DPL) tools are a potentially cost-effective intervention that can contribute to this acceleration. In particular, the continuous experimentation afforded by these tools through software A/B testing, has considerable potential to create compounding improvements in learning outcomes. This paper provides an overview of EIDU, an educational platform combining student focused DPL content with digital structured pedagogy programmes in public pre-primary schools in Kenya. Collection of student’s longitudinal unsupervised assessment data at scale creates the possibility of learning outcome focused A/B testing. This is a novel contribution to the development and research field as up until now this type of capability has largely been confined to students in high-income environments.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-36336-8_119 2339240:EWGWHJXK 2339240:SL8MC9DM 2405685:FG4XFKKM 2405685:MYQJA7TD

Sierra Leone – Giga - GIGA; UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:5D9RW69Z 2405685:7YBMSLS4

2022 Achievements: Ukraine - Global Education Cluster (2023)
2022 Achievements | Strengthening coordination for a robust Education in Emergencies response in Ukraine Since the war broke out on 24th of February 2022 nearly two-thirds of Ukrainian children have been displaced either in-country or to bordering countries, including an estimated 5.7 million school-aged children (ages 3-18), including approx. 570,000 children with disabilities, Ukraine had very close to total enrollment before the war. Education facilities have been attacked from the very beginning of the war and continued to be targeted throughout 2022, creating an unpredictable and unsafe learning environment leading to increased learning loss. According to the Ministry of Education and Science of Ukraine, in the first four months of the war, 1,849 educational facilities were damaged amid ongoing hostilities and 212 were destroyed. The situation has further impacted mental health and psychosocial wellbeing of students and teachers. 75% of parents reported that their children have symptoms of psychological trauma, 90% of teachers (83% women) self-reported their psychological state of mind as worsening. More than 15 million people (out of a population of approx. 41 million) need humanitarian assistance; 34% of those (5.2 million including teachers) have education needs. In 2022, Ukraine Education Cluster partners reached a total of 1,336,746 school-aged children with the provision of Education in Emergencies services. The Global Education Cluster immediately deployed its Rapid Response Team members (a Senior Coordinator and Information Management Officer) to remotely reinforce the Ukraine Education Cluster. Immediate support provided by the RRT include development of the education component of the OCHA Flash Appeal. The RRTs also supported development of the Education Cannot Wait First Emergency Response (FER) for Ukraine. The deployment lasted eight weeks, until interim Cluster Coordinators from each Cluster Lead Agency took over. This was a first for GEC in fastness and possible due to having a Ukraine focal point and a heightened awareness of the situation. The Rapid deployments ensured that Education was represented and visible from the moment the war began; both in terms of focal point for the many national and international actors, and as engaged party to the Inter-Cluster Coordination Group. With support from the CLA, the Ukraine Education Cluster also strengthened monitoring attacks on education, and supported authorities in designing a rapid Needs Assessment and analyzing data, which were reviewed by the GEC and REACH, to inform the current and future Education in Emergencies response. The GEC maintained its support all through 2022 and will continue its assistance to the Ukraine Cluster in 2023.
KerkoCite.ItemAlsoKnownAs: 2339240:U5U93QGM 2405685:EPWMKN6X

Cost-Effective Approaches to Improve Global Learning - Global Education Evidence Advisory Panel (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:URLC9S2L 2486141:9A53JU2Q

Accelerated Funding Grant Progress Report - Global Partnership for Education (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:VPX89MS5 2405685:B5S8KK2E

Decision on Multiplier Grant to Ukraine: April 2023 - Global Partnership for Education (2023)
The Board of Directors approved a $25.55 million grant from the GPE Multiplier to Ukraine as accelerated financing.
KerkoCite.ItemAlsoKnownAs: 2339240:DGFF77EH 2405685:94H3QKU2

Education in Ukraine: Over $51 million in grants and in-kind support announced from GPE, Google and Microsoft - Global Partnership for Education (2023)
As the war continues in Ukraine, severely disrupting education, GPE, Google, Microsoft Corporation and UNESCO will provide over US$51 million for distance learning and psychosocial support for children in conflict-affected areas. The program will be rolled out by UNESCO and UNICEF in Ukraine in partnership with the Ministry of Education and Science of Ukraine.
KerkoCite.ItemAlsoKnownAs: 2339240:DXGPR83S 2405685:R73YDTKY

GPE 2025 Results Framework for Lao PDR - Global Partnership for Education (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:XHMG8A45 2405685:LX7QPQDY
Keywords: ⛔ No INSPIRE recid found

Guidelines for Accelerated Funding - Global Partnership for Education (2023)
These guidelines describe the criteria for eligibility, amount, eligible activities and duration of accelerated funding from GPE.
KerkoCite.ItemAlsoKnownAs: 2339240:LQLLE5W9 2405685:NIKFTMA8

Education Sector Budget Proposal Report 2023/24 - Government of Kenya (Government of Kenya, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:N7CKV3JH 2405685:NHE2TZSP 4656463:RVPQB2Q4

Report of the Presidential Working Party on Education Reform: ​​Transforming education, training and research for sustainable development in Kenya - Government of Kenya (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:4REVBWCX

Building Educational Foundations through Innovation & Technology (BEFIT): Malawi Scale-Up Program Overview - Government of Malawi (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:VG6HFP8C 2405685:CHYEF38Q 2405685:GHJ6XWR4

Basic and Senior Secondary Education Act, 2023 - Government of Sierra Leone (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:X4WE79XI 2405685:JWZZ6UGY

Voluntary National Review 2023 on the implementation of the Sustainable Development Goals - Government of the Socialist Republic of Vietnam (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:ZBCTGAQ4 2405685:QMSAZF8C

National Strategic Plan for Digital Development and Information and Communication Technology (Timor 2032) - Government of Timor-Leste (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:IE6KWICQ 2405685:VI55FQQX

Fiscal Transfers: View Consolidated formulae - Government of Uganda (OTIMS, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:TULVRHIN 2405685:ECEJKUEU 4656463:XPMJKJ47

Nigeria Has More Than 500 Languages, 300 Ethnic Groups... And Critically Important Elections. | Wilson Center - Green, Mark (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:S5GG8IDQ 2405685:QS3VCRAI

Assistive Technologies for Children with Disabilities in Inclusive and Special Schools in Indonesia - Hata, Anna; Wang, Han; Yuwono, Joko; Nomura, Shinsaku (The World Bank, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1596/40387 2339240:VSXIUHXY 2405685:PQZH5HEB
Keywords: Enhancing the quality of education for children with disabilities; including through the use of assistive technology; accepted; study addresses this knowledge gap; focusing on the Indonesian context; world bank; ⛔ No INSPIRE recid found

Technology use in teacher preparation and professional development in low-and middle-income countries - UNESCO Digital Library - Hennessy, Sara; D'Angelo, Sophia; Koomar, Saalim; Kreimeia, Adam; Adam, Taskeen; Cao, Lydia; Haßler, Björn (UNESCO, 2023)
https://doi.org/10.54676/NJZV8067 KerkoCite.ItemAlsoKnownAs: 2339240:9URXV92S 2405685:UU8FCJCF

18 Months Later: A mental health and psychosocial needs assesment across Ukraine - HIAS (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:YPDSQU5B 2405685:7PWATPPL

Cochrane Handbook for Systematic Reviews of Interventions Version 6.4 - Higgins, J.P.T; Chandler, J; Cumpston, M; Li, T; Page, M.J; Welch, V. A (Cochrane, 2023)
KerkoCite.ItemAlsoKnownAs: 2405685:2F9DRA2K

Big data-driven public policy decisions: Transformation toward smart governance - Hossin, Md Altab; Du, Jie; Mu, Lei; Asante, Isaac Owusu (SAGE Open, 2023)
Big data analytics (BDA) enhances knowledge and decision-making. Despite its importance, the connection between technical progress and political change is neglected in the administrative process. Most studies focus on e-government, e-governance, and how technology can improve existing operations of the bureaucracy. However, this article aims to explore the potential of BDA for public policy systems and provide a linkage for the transformation toward digital and smart governance using preferred reported items for systematic review and meta-analysis (PRISMA) approach to reveal the relevant documents and narrative review approach to interpret the application of BDA at each step of the public policy system. In addition, this study identifies several common public policy-related big data sources and techniques that could be used at the various stages of the public policy process. This study argues that BDA has the potential to be used for policy formulation in the four main phases—planning, design, service delivery, and evaluation. Most studies confirm its potential in the policy process for taxation, health, education, transportation, law, economy, and social system. This study reveals that it is also suitable for public policy execution stages, such as public supervision, public regulation, service delivery, and policy feedback. Previous studies have indicated that the application of BDA can transform traditional or manual governance systems into digital and smart governance. We contend that the policy cycle should be seen as a dynamic and iterative process characterized by continuous evolution. Though each step of transformation has its unique challenges in handling BDA and maintaining the Information and Communication Technology (ICT) infrastructure, it can ensure an accurate, prompt, and context-oriented public policy system. These insights provide a novel outlook on effectively managing the interplay between innovation and traditional approaches in the realm of public policy development.Plain Language SummaryImportance: Big data analytics (BDA) enhances knowledge and decision-making. Despite its importance, the connection between technical progress and political change is neglected in the administrative process. Most studies focus on e-government, e-governance, and how technology can improve existing operations of the bureaucracy. Aims: However, this article aims to explore the potential of BDA for public policy systems and provide a linkage for the transformation toward digital and smart governance using preferred reported items for systematic review and meta-analysis (PRISMA) approach to reveal the relevant documents and narrative review approach to interpret the application of BDA at each step of the public policy system. In addition, this study identifies several common public policy-related big data sources and techniques that could be used at the various stages of the public policy process. Findings: This study argues that BDA has the potential to be used for policy formulation in the four main phases—planning, design, service delivery, and evaluation. Most studies confirm its potential in the policy process for taxation, health, education, transportation, law, economy, and social system. This study reveals that it is also suitable for public policy execution stages, such as public supervision, public regulation, service delivery, and policy feedback. Implications: Previous studies have indicated that the application of BDA can transform traditional or manual governance systems into digital and smart governance. Though each step of transformation has its unique challenges in handling BDA and maintaining the Information and Communication Technology (ICT) infrastructure, it can ensure an accurate, prompt, and context-oriented public policy system.
_eprint: https://doi.org/10.1177/21582440231215123 KerkoCite.ItemAlsoKnownAs: 10.1177/21582440231215123 2339240:33SNH7ZA 2405685:SQ39EZWB

The relationship between parental involvement and psychological adjustment among Chinese children with autism spectrum disorder in the transition from kindergarten to primary school: A chain-mediating model - Hou, Yujia; Yan, Tingrui; Zhang, Junfang (Frontiers in Psychology, 2023)
Introduction This study examined the impact of parental involvement on the psychological adjustment of children with autism spectrum disorder (ASD), and the role of parenting self-efficacy and parenting stress in the transition from kindergarten to primary school. Methods Using the questionnaires, we collected data from 237 Chinese parents of children with ASD. Results Mediation analyses showed that parental involvement partially promoted the psychological adjustment of children with ASD, which was reflected in the fact that parental involvement promoted children’s prosocial behavior but did not reduce their emotional/behavioral problems. Mediation analyses also revealed the role of the mediator in parenting stress between parental involvement and the psychological adjustment of children. Additionally, the results suggested that parenting self-efficacy and parenting stress played a chain-mediating role in the association between parental involvement and psychological adjustment in children with ASD. Discussion These findings enhance our understanding of the mechanisms underlying the relationship between parental involvement and psychological adjustment in children with ASD in the transition from kindergarten to primary school.
KerkoCite.ItemAlsoKnownAs: 10.3389/fpsyg.2023.1087729 2339240:VVM5PG5N 2405685:ABPGLJ3J

The state of education in Ukraine and steps for future progress - Hrynevych, Liliia (Learning during crisis: Insights for Ukraine from across the globe, 2023)
PDF | In this publication, countries participating in the OECD programme on the Future of Education and Skills (Education 2030) are offering a range of... | Find, read and cite all the research you need on ResearchGate
KerkoCite.ItemAlsoKnownAs: 2339240:HX27XGVK 2405685:3TY6XMVT

Automated knowledge extraction from IS research articles combining sentence classification and ontological annotation - Huettemann, Sebastian (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:APEG3W9C 2486141:M878DKL8
Keywords: _Added-ailr-2024; ⛔ No DOI found

Promoting Climate-Sensitive Early Childhood Care and Education in Emergencies - INEE (Inter-agency Network for Education in Emergencies (INEE), 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:JDEMSN5P 2405685:PUXYLSLB

Disability-Inclusive Education in Emergencies: Key concepts, approaches, and principles for practice - Inter-agency Network for Education in Emergencies (INEE) (INEE, 2023)
KerkoCite.ItemAlsoKnownAs: 2405685:LXTVX8S5

Disability-Inclusive EiE Resources Mapping and Gap Analysis - Inter-agency Network for Education in Emergencies (INEE) (INEE, 2023)
KerkoCite.ItemAlsoKnownAs: 2405685:M3KFL76D

Conceptual Framework for Education in Emergencies Data - International Institute for Educational Planning (IIEP)-UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:KRMCTW9E 2405685:YJWX532U

Guidelines and Toolkit for a Diagnosis of the Education in Emergencies Data Ecosystem - International Institute for Educational Planning (IIEP)-UNESCO (2023)
Manual and Guideline in English on World about Education and Protection and Human Rights; published on 22 Dec 2023 by UNESCO
KerkoCite.ItemAlsoKnownAs: 2339240:AVQ5XNH7 2405685:SWSLMKIC

Institutionalizing Education in Emergencies Data Production and Use for Crisis-sensitive Educational Planning - International Institute for Educational Planning (IIEP)-UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:KSW9JNS9 2405685:2EFXI4ZB

The Geneva Declaration on Education in Emergencies and Protracted Crises - International Parliamentary Network for Education; Geneva Global Hub for Education in Emergencies (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:6KT9Q5TP 2405685:G8LS285S

Digital Development Dashboard - International Telecommunication Union (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:TVWZ829S 2405685:FS45JUH5

Digital Development Dashboard: Lao PDR - International Telecommunication Union (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:P7H7DAB5 2405685:PU2YEQ4W

ICT Price Baskets - International Telecommunication Union (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:IS7K38GU 2405685:KASHFILH

Ukraine Digital Development Country Profile - International Telecommunication Union (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:U5QQ2YSC 2405685:GQQG3WFD

AIED Unplugged: Leapfrogging the digital divide to reach the underserved - Isotani, Seiji; Bittencourt, Ig Ibert; Challco, Geiser C.; Dermeval, Diego; Mello, Rafael F. (Artificial Intelligence in education. Posters and late breaking results, workshops and tutorials, industry and innovation tracks, practitioners, doctoral consortium and Blue Sky, 2023)
Artificial Intelligence in Education (AIED) is a driving force to improve education. Nevertheless, policymakers from the Global South fear that AI will increase the digital divide and reduce the opportunities for students in these regions to thrive. To address this problem, we analyzed the past 30 years of data on four aspects of the digital divide. Then, based on these findings and a series of discussions with stakeholders (e.g., policymakers), we proposed the concept of AIED Unplugged. An approach to creating AI-based educational technologies that do not require changes in current school settings (e.g., infrastructure), do not rely on stable internet access, and do not ask for digital skills to use them. We applied this concept to redesign an education policy in Brazil to help students improve their writing skills. Our results show a reduction in time, cost and complexity to running the policy, and a positive impact on more than 500,000 students in 7,000 schools in the country.
KerkoCite.ItemAlsoKnownAs: 10.1007/978-3-031-36336-8_118 2405685:ZCMV5IK4

Walking the Talk for the Right to Education – A field note on Gilgit Baltistan and its Delivery Lab - Jamil, Baela (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:4IBJHGM5 2405685:B4VGTA42

The Mobile Gender Gap Report 2023 - Jeffrie, Nadia (GSMA, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:MT35DFDN 2405685:WMZXG7EA

Low-tech personalised learning to improve girls' education in Kenya. - Jordan, K; Damani, K; Khagame, P; Mongeau, C; Mumbi, A; Myers, C; Njuguna, L; Otieno, J; Zhao, A (EdTech Hub and M-Shule, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:M7HVSHJG 2405685:KN2IBMDV

How can messaging apps, WhatsApp and SMS be used to support learning? A scoping review - Jordan, Katy (Technology, Pedagogy and Education, 2023)
In response to disruption to education during the Covid-19 pandemic, mobile phone-based messaging has emerged in some instances as an accessible, low-connectivity way of promoting interactivity. However, no recent reviews have been undertaken in relation to how social media and messaging apps can be used to effectively support education in low- and middle-income countries. In this scoping review, 43 documents were identified for inclusion and three main thematic areas emerged: supporting student learning (including interacting with peers and other students, peer tutoring and collaborative learning; and interacting with teachers, through content delivery, teaching and assessment); teacher professional development (including structured support and prompts, and informal communities of practice); and supporting refugee education. The discussion and findings are both of practical use, to inform responses to the current pandemic and designing initiatives in the future, and will also be useful for advancing research in this expanding field.
Accepted: 2022-05-18T23:30:06Z Publisher: Routledge KerkoCite.ItemAlsoKnownAs: 10.17863/CAM.84697 2405685:8XW8JR6H

Nudging or Nagging? Conflicting Effects of Behavioral Tools - Kalil, Ariel; Liu, Haoxuan; Mayer, Susan; Rury, Derek; Shah, Rohen (SSRN Electronic Journal, 2023)
KerkoCite.ItemAlsoKnownAs: 10.2139/ssrn.4318177 2339240:HNT2VXJ7 2405685:5FJWAQY9

Learning on Hold: The Toll of COVID-19 School Closures on Mozambique’s Foundational Literacy - Kan, Sophia; Pontuschka, Rafael (UNICEF, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:75A4XTSW 2405685:4WR5TEQR
Keywords: ⛔ No INSPIRE recid found

Exploring the landscape of autism in Africa: Challenges in diagnosis, support, and resources – a short communication - Kantawala, Burhan; Abu-Bakr, Aya; Kasini, Benoît; Ndayambaje, Martin; Ian Soh, Shi; Nazir, Abubakar; Wojtara, Magda; Uwishema, Olivier (Annals of Medicine and Surgery, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:Y3AM9QLT 2405685:C99PD49S

War & Education - Kohut, Iryna; Nikulina, Olena; Syrbu, Olena; Zherobkina, Tetiana; Nazarenko, Yuliia (savEd, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:8VWRJ3VR 2405685:2X7VKAUW

The evolution of systematic evidence reviews: Past and future developments and their implications for policy analysis - Lemire, Sebastian; Peck, Laura R.; Porowski, Allan (Politics & Policy, 2023)
Abstract Evidence reviews are widely used to summarize findings from existing studies and, as such, are an important base for policy analysis. Over the past 50 years, three waves of evidence reviews have emerged: (1) the meta‐analysis wave, (2) the mixed‐methods synthesis wave, and (3) the core components wave. The present article first describes these waves and reflects on the benefits and limitations of each wave in the context of policy analysis. Informed by this historical account, the article then identifies and discusses three trends that are likely to influence future directions of evidence reviews: (1) using data science tools, (2) embedding an equity focus, and (3) translating research into practice. The concluding discussion connects these developments to public policy, identifying how evidence from systematic evidence reviews informs—or could better inform—policy decisions. Related Articles Nunes Silva, Carlos. 2012. “Policy and Evidence in a Partisan Age: The Great Disconnect—By Paul Gary Wyckoff.” Politics & Policy 40(3): 541–43. https://doi.org/10.1111/j.1747‐1346.2012.00363.x . Sinclair, Thomas A. P. 2006. “Previewing Policy Sciences: Multiple Lenses and Segmented Visions.” Politics & Policy 34(3): 481–504. https://doi.org/10.1111/j.1747‐1346.2006.00025.x . Smith‐Walter, Aaron, Holly L. Peterson, Michael D. Jones, and Ashley Nicole Reynolds Marshall. 2016. “Gun Stories: How Evidence Shapes Firearm Policy in the United States.” Politics & Policy 44(6): 1053–88. https://doi.org/10.1111/polp.12187 . , La evolución de las revisiones sistemáticas de evidencia: Desarrollos pasados y futuros y sus implicaciones para el análisis de políticas Las revisiones de evidencia se utilizan ampliamente para resumir los hallazgos de estudios existentes y, como tales, son un tipo importante de análisis de políticas. En los últimos 50 años, han surgido tres oleadas de revisiones de evidencia: (1) la oleada de metanálisis, (2) la oleada de síntesis de métodos mixtos y (3) la oleada de componentes centrales. El presente artículo primero describe estas oleadas y reflexiona sobre los beneficios y limitaciones de cada oleada en el contexto del análisis de políticas. Basado en este relato histórico, el artículo luego identifica y analiza tres tendencias que probablemente influirán en las direcciones futuras de las revisiones de evidencia: (1) usar herramientas de ciencia de datos, (2) incorporar un enfoque de equidad y (3) traducir la investigación a la práctica. La discusión final conecta estos desarrollos con la política pública, identificando cómo la evidencia de las revisiones sistemáticas de evidencia informa, o podría informar mejor, las decisiones de política. , 系统性证据审查的演变:过去和未来的发展及其对政策分析的影响 证据审查被广泛用于总结现有研究结果，因此是一种重要的政策分析类型。过去50年里，出现了三次证据审查浪潮，即荟萃分析、混合方法综合、以及核心组分法。本文首先描述了这三种方法，并在政策分析情境下反思了每种方法的优势和局限性。根据这一历史叙述，本文随后识别并探讨了可能影响证据审查未来方向的三种趋势:(1)使用数据科学工具，(2)嵌入公平视角，(3)将研究转化为实践。结论将这些发展与公共政策相联系，识别了来自系统性证据审查的证据如何影响政策决策(或如何能更好地影响政策决策)。
KerkoCite.ItemAlsoKnownAs: 10.1111/polp.12532 2405685:HNC2CICS 2486141:KBTHBHWM 2486141:U8BG8VRZ
Keywords: _Added-ailr-2024; análisis de políticas; componentes básicos; core components; evidence review; meta-analysis; metanálisis; mixed methods; métodos Mixtos; policy analysis; research synthesis; revisión de evidencia; revisión sistemática; systematic review; síntesis de Investigación; 政策分析; 核心组分; 混合方法; 研究综合; 系统性综述; 荟萃分析; 证据审查

Providing distance education during the war: The experience of Ukraine - Londar, Lidia; Pietsch, Marcus (Information Technologies and Learning Tools, 2023)
Explore millions of resources from scholarly journals, books, newspapers, videos and more, on the ProQuest Platform.
KerkoCite.ItemAlsoKnownAs: 2339240:UTUWTKU9 2405685:V9CKBERQ

Introduction of an EdTech intervention to support learning of foundational skills in Sierra Leone: policy, teacher, and community perspectives - Lurvink, Anne-Fleur; Pitchford, Nicola J. (Frontiers in Education, 2023)
Background: Like many other countries, Sierra Leone faces significant challenges with primary education resulting in many children leaving primary school without acquiring basic foundational skills. To address these challenges, an educational technology (EdTech) intervention was implemented in 20 primary schools located in two marginalized districts in Sierra Leone. While this EdTech intervention has been shown to raise learning outcomes, little is known about the impacts on the broader education ecosystem. This paper investigates how this EdTech intervention might address some the challenges faced with primary education in Sierra Leone, by examining policy, teacher, and community perspectives. Method: A mixed methods approach was employed which included a policy mapping exercise, a survey of teachers training needs in supporting the development of foundational skills with grade 1 learners, an interview with teachers after they had delivered the EdTech intervention to garner their perceptions and experiences of using the technology in their class, and focus groups with teachers and other community members to gain insights into how the EdTech intervention had been received. Results: Findings from the policy mapping exercise and quantitative data from the survey of teacher training needs were triangulated with qualitative data from the interviews and focus groups. Four key themes emerged relating to the effective and sustained use of this EdTech intervention to support the acquisition of foundational skills by primary school children in Sierra Leone: (1) the need for continued teacher professional development, (2) the use of English as the language of instruction, (3) access to the technology by children with special educational needs and disabilities (SEND), and (4) the importance of active community engagement in supporting the intervention. Discussion: Collectively, results indicated that the EdTech intervention employed in this study aligned well to the education policy in Sierra Leone. Enhanced teacher training is needed, especially in using English as the language of instruction, and continued community engagement is essential for scaling the intervention effectively and ensuring that all children, including those with SEND, access the technology at primary school. These results have implications for other EdTech intervention deployed in resource-poor settings to enhance learning of foundational skills.
KerkoCite.ItemAlsoKnownAs: 2339240:J83HRBE6 2405685:BTDXQFJ9

Building Education Foundations through Innovation & Technology: Malawi Scale-Up Program Overview - Malawi Ministry of Education (Government of Malawi, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:989PJPWR 2405685:35X56FZB

Building Education Foundations through Innovation & Technology: Malawi Scale-up Program Overview - Malawi MoE (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:J8T5KC5S 2405685:U5E6UYNQ

Building Education Foundations through Innovation & Technology: Malawi Scale-up Program Overview - Malawi MoE (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:J8T5KC5S 2405685:U5E6UYNQ

Issues and strategies in inquiry-based learning evaluation - Mao, Yiqing (Open Journal of Social Sciences, 2023)
KerkoCite.ItemAlsoKnownAs: 10.4236/jss.2023.114030 2339240:ZGTCQ2SK 2405685:HTEUGKNQ

Feasibility of a mobile phone training on autism spectrum disorders for teachers in Tanzania - Martino, Daniele C.; Naqvi, Nilofer C. (Technology, Pedagogy and Education, 2023)
Despite the rising global prevalence of autism spectrum disorders (ASD), significant disparities in ASD knowledge persist worldwide. Professional development trainings are effective in increasing teacher knowledge of ASD; however, in-person trainings pose accessibility concerns for teachers in low- and middle-income countries. In sub-Saharan Africa, few teacher development opportunities exist and logistical barriers limit attendance, highlighting the need for a more accessible training modality. The present study used a pre-post-test methodology among general and special education teachers in urban Tanzania to evaluate the feasibility of a mobile phone-delivered training on ASD. Results indicated a robust 84% participation rate and high quiz scores across training modules. The benefits of using mobile phone technology in a low-resource setting are presented. As the first asynchronous ASD training developed and implemented among teachers in Tanzania, this study can guide future research that explores how best to increase ASD knowledge among community members using technology.
Publisher: Routledge _eprint: https://doi.org/10.1080/1475939X.2023.2192517 KerkoCite.ItemAlsoKnownAs: 10.1080/1475939X.2023.2192517 2339240:YYWSMV9B 2405685:24U764C8

Mobile application based early educational intervention for children with autism: A pilot trial - Mazumdar, Arpita; Banerjee, Mallika; Chatterjee, Biswajoy; Saha, Sayan; Gupta, Gauri Shankar (Disability and Rehabilitation: Assistive Technology, 2023)
To design and develop a mobile application for pre-school readiness of children with autism and also to identify their learning pattern. Based on strong foundation of functional academics, we have developed a mobile application for providing an early educational intervention program to the children with autism. Three successive software trials have been conducted among 31 children with autism of age group of three to 10 years. The mobile app has been provided to educators and parents and they have been allowed to supervise the children during their learning phase for eight to 10 weeks. The imprint of learning pattern is recorded and learning progress profile is generated for individual child. Data analysis of learning progress profile shows that 90% of the participants preferred drag and drop or simple touch approach over conventional methods practised during classroom teachings. More than 84% of the children are found to adapt pre-requisite skills for writing like scribbling, tracing, dots joining, copying, etc. after using the app on their tablet who are reluctant to hold pencil and paper otherwise. Twenty-five percent of the participants are reported to reciprocate the greeting etiquettes in class such as greeting teachers and their peers. The mobile application made a valuable contribution to early intervention program for children with autism by imparting appropriate learning opportunities readily available to them. Performance metrics underlying each activity form a strong base of identification of learning patterns and formulation of revised individualized education plan (IEP).Implications for RehabilitationChildren with autism need the mobile application as an educational intervention program for it is readily available and user friendly.Educators need the mobile application to quantify the performance parameters and there by monitor/evaluate the progress of the child.Overall, the present research has aimed to develop an easy reach app by which educating as well as handling challenging behaviour of the children with autism would be easier. Children with autism need the mobile application as an educational intervention program for it is readily available and user friendly. Educators need the mobile application to quantify the performance parameters and there by monitor/evaluate the progress of the child. Overall, the present research has aimed to develop an easy reach app by which educating as well as handling challenging behaviour of the children with autism would be easier.
Publisher: Taylor & Francis _eprint: https://doi.org/10.1080/17483107.2021.1927208 KerkoCite.ItemAlsoKnownAs: 10.1080/17483107.2021.1927208 2339240:YYX46NHC 2405685:TC6RT9DR

The current landscape and future of tablet-based cognitive assessments for children in low-resourced settings - McHenry, Megan S.; Mukherjee, Debarati; Bhavnani, Supriya; Kirolos, Amir; Piper, Joe D.; Crespo-Llado, Maria M.; Gladstone, Melissa J. (PLOS digital health, 2023)
Publisher: Public Library of Science San Francisco, CA USA

Implementation of Universal Design for Learning in Low- and Middle-Income Countries: ‘I Thought These Principles Could Have Been Written by Me’ - McKenzie, Judith; Karisa, Amani; Kahonde, Callista (Disabilities, 2023)
UNESCO’s Global Education Monitoring Report (2020) strongly recommends the adoption of Universal Design for Learning (UDL) at the government level so that it becomes an integral part of countries’ inclusive education policies. However, UDL has largely been developed in high-income countries with technology as a central theme. The question is whether the purported benefits of the UDL approach can translate into low and middle-income country (LMIC) contexts. This study explores the relevance and fit of UDL to LMIC contexts by use of interviews (either individual or group) with 12 representatives of international agencies, non-governmental organizations (NGOs), and UDL experts who have experience in providing inclusive education services in LMICs. Three themes are reported: understanding of UDL, UDL supporting inclusive education, and UDL in teacher-training initiatives and capacity building. The concept of UDL is not new in LMICs, although the name may be. The potential for UDL to support inclusive education in LMICs is recognized. UDL needs to be mainstreamed in teacher training programs, and its implementation should be adapted to respond to the contextual realities of LMICs. The encounter between UDL proponents from high-income countries and education stakeholders in LMICs should be mutually enriching rather than imposing the approach from high-income countries on those in LMICs.
0 citations (Crossref) [2024-04-17] Number: 4 Publisher: Multidisciplinary Digital Publishing Institute KerkoCite.ItemAlsoKnownAs: 10.3390/disabilities3040043 2339240:3UU6C6DM 2405685:MGRLI3CU
Keywords: LMIC; UDL; disability; inclusion; ⛔ No INSPIRE recid found

Damage Assessment Report - Ukraine June 2023 - Ministry of Education and Science (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:74B24PKH 2405685:G52JBKMN

Strategic Action Plan by 2027 - Ministry of Education and Science of Ukraine (Gov. of Ukraine, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:MNDVZV58 2405685:JGPLIIF4

Результати міжнародного дослідження якості освіти PISA-2022 - Ministry of Education and Science of Ukraine (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:BI8G7RRA 2405685:B7P2M4MT

Transforming Education Through Technology: EdTech Masterplan 2030 - Ministry of Education, Singapore (2023)
Gain insights on the strategic focus of our Educational Technology (EdTech) Plan, or “EdTech Masterplan 2030” for short.
KerkoCite.ItemAlsoKnownAs: 2339240:F4B6JD72 2405685:FUWKND2F

Teacher Policy Action Plan - Ministry of Education, Youth and Sports, Kingdom of Cambodia (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:5LW2KVIY 2405685:SQQQQFA8

The Education, Youth and Sport Performance Report to Congress for the Academic Year 2021–2022 - Ministry of Education, Youth and Sports, Kingdom of Cambodia (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:CGQEWIVZ 2405685:D93IM5EY

National Information & Communication Technology Policy 2023 - Ministry of Technology and Science (Government of the Republic of Zambia, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:65KP6H7Z 2405685:5C2ASXS5

What’s Behind the Growing Number of Attacks in Southern Thailand? - Mishra, Rahul (2023)
Whoever ends up leading the country’s next government, they need to prioritize the implementation of the 2013 peace plan.
KerkoCite.ItemAlsoKnownAs: 2339240:CWDUSCXJ 2405685:YA3ISDK7
Keywords: ⛔ No INSPIRE recid found

Navigating narratives in Ukraine: Humanitarian response amid solidarity and resistance - Moallin, Zainab; Hargrave, Karen; Saez, Patrick (Overseas Development Institute (ODI Global), 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:8SJZVNV9 2405685:IMTIGRFL
Keywords: ⛔ No DOI found

A digital accessibility and inclusive design-based e-module in Higher Education: Does it work in a classroom with a deaf student? - Musayaroh, Siti; Asmiati, Neti; Utami, Yuni Tanjung; Mulia, Dedi; Sidik, Sistriadini Alamsyah; Febri, Reza; Abadi, Toni Yudha Pratama; Maslahah, Sayidatul; Pramudyo, Anggoro Suryo (ASEAN Journal of Community and Special Needs Education, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:9P7P2HPK 2405685:LD8V7CAU
Keywords: accepted; ⛔ No DOI found; ⛔ No INSPIRE recid found

Eduten Partners with Laos for a Landmark 12-Week Educational Research Project - Muurimaa, Henri (2023)
Eduten is excited to announce the launch of a new 12-week research project in Laos, in collaboration with local educational authorities.
KerkoCite.ItemAlsoKnownAs: 2339240:G6CJP2T7 2405685:UM48XU3W

National Digital Literacy Framework - National Information Technology Development Agency (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:3KLFM6DN 2405685:322MJ36E

Learning Disabilities - National Institute of Neurological Disorders and Stroke (2023)
Learning disabilities are disorders that affect the ability to understand, or use spoken or written language, do mathematical calculations, coordinate movements, and/or direct attention. Learning disabilities occur in very young children, yet they are usually not noticed until the child reaches school age. Learning disabilities can be lifelong conditions.
KerkoCite.ItemAlsoKnownAs: 2339240:EQFZVDN5 2405685:D5FS9SBN
Keywords: ⛔ No INSPIRE recid found

National Numeracy Programme (NNP) – Objectives - National Numeracy Programme (NNP) (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:XAY8PSPU 2405685:CZYI6TCY

Challenges encountered by teachers in supporting children with autism in primary schools in Tanzania - Ndunguru, N.E.; Kisanga, S.E. (Papers in Education and Development, 2023)
This paper reports the challenges experienced by teachers in supporting children with autism (CA) in primary schools in Tanzania. It is a qualitative study that employed purposive sampling technique to select seven primary school teachers of CA from two schools. Data were collected using a semi-structured interview and were analysed thematically. The findings of the study revealed that teachers experience challenges when supporting CA due to inadequate knowledge in managing the behaviours of CA. Also, teachers received little collaboration from parents of CA due to a lack of commitment to the education of their CA. The paper recommends for continuous professional development training to teachers of CA to enhance the acquisition of updated knowledge and skills for supporting CA. Also, there is a need for effective collaboration between teachers and parents for the successful support of CA.
KerkoCite.ItemAlsoKnownAs: 2339240:265RB2L2 2405685:TVG5APMB

Implementation Completion and Results Report – Vietnam Quality Improvement of Primary Education for Deaf Children Project (QIPEDC) - Nguyen, Anh Thuy (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:G228NA6E 2405685:G5KF52UM
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Toward a holistic approach to EdTech effectiveness: Lessons from Covid-19 research in Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone - Nicolai, Susan; Jordan, Katy; Adam, Taskeen; Kaye, Tom; Myers, Christina (International Journal of Educational Development, 2023)
KerkoCite.ItemAlsoKnownAs: 10.1016/j.ijedudev.2023.102841 2405685:EFV98PTB

Edtech and parental engagement - Nicolai, Susan; Rui, Tingting (Yang); Zubairi, Asma; Chebet, Seluget; Kamninga, Tony (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:85L97CQM 2405685:VWMAPDA5
Keywords: ⛔ No INSPIRE recid found

Technology in education: a case study on Lao People's Democratic Republic - Nietschke, Yung; Dabrowski, Anna (International Education Research, 2023)
This paper was commissioned by the Global Education Monitoring Report as background information for the development of the 2023 Global Education Monitoring (GEM) Report: technology and education, Southeast Asia. Digital technology has the potential to transform learning and offer a solution to persistent challenges in equity of access and quality of learning for all students. COVID-19 has accelerated the adoption of technology to deliver alternative modes of education. It has also put the spotlight on the digital divide that technology creates. This Case Study explores the progress of technology integration in the education sector in Lao PDR in line with its aspirations for a thriving digital economy driven by a digitally-skilled workforce. It explores the current conditions that facilitate or inhibit digitalization of the education sector and considers the impact across the system, sector-wide and school levels. This includes issues relating to digital access, digital literacy of teachers and students, technology infrastructure investments and the regulatory environment. The findings suggest that many of these challenges are not unique to Lao PDR. However, with a clear strategy, political commitment and sustainable resourcing of the education sector, there are opportunities for the Government of Lao PDR and its partners, to set a strong foundation for digitalizing the education system.
Publisher: Global Education Monitoring Report Team KerkoCite.ItemAlsoKnownAs: 2339240:4QQEEHZ3 2405685:V9RN8N7R
Keywords: accepted; checks the GP(disadvntaged group-OOS)T; publisher: Global education Monitering report; ⛔ No DOI found; ⛔ No INSPIRE recid found

Technology in education: a case study on Lao People's Democratic Republic - Nietschke, Yung; Dabrowski, Anna (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:2G8JRHPM 2405685:9XD3CL25

Improving Enrollment and Learning through Videos and Mobiles: Experimental evidence from Northern Nigeria - Orozco-Olvera, Victor; Rascon-Ramirez, Ericka (World Bank Group, 2023)
Improving Enrollment and Learning through Videos and Mobiles : Experimental Evidence from Northern Nigeria (English)
KerkoCite.ItemAlsoKnownAs: 2339240:X4A27Y5Y 2405685:36KDW9TD

Collaboration to Realise Kenya’s National Learning Goals through EdTech - Otieno, Jennifer; Omuthe, Ronald; Ampofo, Rudolph (EdTech Hub, 2023)
An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 10340063 ZenodoArchiveConcept: 10340062 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10340063 10.53832/edtechhub.0179 2405685:A76IFCAT
Keywords: _r:AddedByZotZen

Law of Ukraine "About complete general secondary education" - Parliament of Ukraine (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:R3B7YNYJ 2405685:4KD4Q8CE

Personal communication: Research on solar-power projector DPL implementation in Malawi - Pitchford, Nicola J. (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:KKKZIMMM 2405685:XW8TKKQ5

Access to Education for Refugee Children in Indonesia During the COVID-19 Pandemic: Challenges and Adaptation Strategies - Prabaningtyas, Raden Ajeng Rizka Fiani; Pudjiastuti, Tri Nuke; Alami, Athiqah Nur; Farhana, Faudzan; Arfan (ASEAS - Advances in Southeast Asian Studies, 2023)
The protracted refugee situation in Indonesia during the COVID-19 pandemic has increased refugee children's vulnerability due to the non-fulfillment of their fundamental rights, including the right to education. Drawing on data collected through interviews and observation of refugee children during fieldwork in the cities of Batam and Makassar, this paper aims to investigate how and why their access to education has changed during the pandemic. This study finds that, shortly before the pandemic, the Indonesian government provided access to education for refugee children through the issuance of the Circular Letter from the Secretary General of the Ministry of Education, Culture, Research and Technology Number 752553/A.A4/HK/2019 dated on 10 July 2019. However, the pandemic complicated the accessibility of education for refugee children suggested by the Circular Letter due to lockdown policy and mobility restrictions. The complication is apparent in four aspects of accessibility, namely: access to information, activities in the learning process, environmental support, and the motivation of refugee children. Notwithstanding, this study also finds that the pandemic has induced developments of adaptation strategies through the adoption of online learning among refugee communities to enable wider access to education for refugee children. Therefore, the pandemic may have revealed the urgency for a more rights-based policy on refugee treatment in Indonesia.
KerkoCite.ItemAlsoKnownAs: 10.14764/10.ASEAS-0089 2339240:YEH7PUI9 2405685:ULFVXVLS
Keywords: Bildungsbeteiligung; Bildungschance; Epidemie; Flüchtling; Indonesia; Indonesien; Kind; child; educational opportunity; epidemic; participation in education; refugee

Basic Education Data - President's Office — Regional Administration and Local Government; Government of Tanzania (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:CDQPB2XK

What Can the Education Sector Do to Adapt to the Forthcoming Impacts of Climate Change? - Proctor, Jamie (Global Partnership for Education, 2023)
Practitioner experience and reflections on what can be done specifically within the education sector to adapt and reduce the negative impacts of climate change on education.
KerkoCite.ItemAlsoKnownAs: 2339240:MY2CVJ8E 2405685:ERFH7B7U

Breaking through limitations: enhanced systematic literature reviews with large language models - Reason, Tim; Langham, Julia; Gimblett, Andy; Malcolm, Bill; Klijn, Sven (Population, 2023)
KerkoCite.ItemAlsoKnownAs: 2405685:CBPEMXNV 2486141:ELIALEJV
Keywords: _Added-ailr-2024; ⛔ No DOI found

Dakar Framework for Action - Right To Education (2023)
The Education for All (EFA) movement is a global commitment to provide quality basic education for all children, youth and adults. At the World Education Forum (Dakar, 2000), 164 governments pledged to achieve EFA and identified six goals to be met by 2015. Governments, development agencies, civil society and the private sector are working together to reach the EFA goals.[ESPAÑOL] [FRANÇAIS]
KerkoCite.ItemAlsoKnownAs: 2339240:HABZPLAK 2405685:NYUFHM6B

Investigating the situation for children with autism and their families in Cambodia - Rose, Richard; Jegannathan, Bhoomikumar; Mong, Dalin; Pat, Puthy; Sok, Derozet (Education Sciences, 2023)
Publisher: MDPI KerkoCite.ItemAlsoKnownAs: 10.3390/educsci13060565 2339240:EHPCL9IH 2405685:G28FIFX4
Keywords: ⛔ No INSPIRE recid found

Mapping National Digital Learning Platforms: Full Dataset - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Hasiniavo, Rasolohery (EdTech Hub, 2023)
The dataset provided here as a link to a spreadsheet presents raw data from a global mapping exercise of 471 national digital platforms across 184 countries conducted by EdTech Hub as part of a Helpdesk request from UNICEF. The mapping exercise examined three key areas of availability, usability, and inclusivity of national digital learning platforms. Analysis from the dataset was used to generate a report on national digital learning platforms. The datasheet includes the authors’ organisation of the dataset under key indicators. Readers can use the datasheet to replicate or conduct their own analysis. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 10256767 ZenodoArchiveConcept: 10256766 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.10256767 10.53832/edtechhub.0178 2405685:SPWJF5UR
Keywords: _r:AddedByZotZen

Systematic Review using a Spiral approach with Machine Learning - Saeidmehr, Amirhossein; Steel, Piers; Samavati, Faramarz (2023)
With the accelerating growth of the academic corpus, doubling every nine years, machine learning is a promising avenue to make systematic review manageable. Though several notable advancements have already been made, the incorporation of machine learning is less than optimal, still relying on a sequential, staged process designed to accommodate a purely human approach, exemplified by PRISMA. Here, we test a spiral, alternating or oscillating approach, where full-text screening is done intermittently with title/abstract screening, which we examine in three datasets by simulation under 360 conditions comprised of different algorithmic classifiers, feature extractions, prioritization rules, data types, and information provided (e.g., title/abstract, full-text included). Overwhelmingly, the results favored a spiral processing approach with Logistic Regression, TF-IDF for vectorization, and Maximum Probability for prioritization. Results demonstrate up to a 90% improvement over traditional machine learning methodologies, especially for databases with fewer eligible articles. With these advancements, the screening component of most systematic reviews should remain functionally achievable for another one to two decades.
KerkoCite.ItemAlsoKnownAs: 10.21203/rs.3.rs-2497596/v1 2405685:RINZQERU 2486141:SJ799IB8
Keywords: _Added-ailr-2024

Text classification using deep learning techniques: A bibliometric analysis and future research directions - Sarin, Gaurav; Kumar, Pradeep; Mukund, M. (Benchmarking: An International Journal, 2023)
Publisher: Emerald Publishing Limited KerkoCite.ItemAlsoKnownAs: 10.1108/BIJ-07-2022-0454 2405685:9AAKZ7EL 2486141:J6KNBKMH 2486141:KMNV7QKL
Keywords: Bibliometric analysis; Classification; Data mining; Deep learning; Text analytics; _Added-ailr-2024

Towards a Resilient Education Recovery from Pakistan's Floods: Rapid Response Research - Sarwar, Moizza Binat (Malala Fund & Pakistan Coalition for Education, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:9HVG3REL 2405685:9TT63AI4

The use of technology in hybrid learning for student with special needs - Sarwendah, Ade Putri; Azizah, Nur; Mumpuniarti, Mumpuniarti (Journal of Education and Learning (EduLearn), 2023)
KerkoCite.ItemAlsoKnownAs: 10.11591/edulearn.v17i2.20810 2339240:B5GU9HBR 2405685:T2X4XT4J
Keywords: ⛔ No INSPIRE recid found

The use of technology in hybrid learning for student with special needs - Sarwendah, Ade Putri; Azizah, Nur; Mumpuniarti, Mumpuniarti (Journal of Education and Learning (EduLearn), 2023)
KerkoCite.ItemAlsoKnownAs: 10.11591/edulearn.v17i2.20810 2339240:B5GU9HBR 2405685:T2X4XT4J
Keywords: ⛔ No INSPIRE recid found

Education Needs Assessment Report Mykolaiv City, Ukraine - Save the Children (Save the Children International, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:FIE7ICI3 2339240:GT3AYM8W 2405685:7C935XCA

Nearly half a million children in Malawi unable to attend school due to Cyclone Freddy - Save the Children (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:IXQQVSWL 2405685:94SBLT7H

About IDELA - Save the Children, IDELA (IDELA, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:E2PD2ZUF 2405685:YP77AGZ8

Digital degrowth: toward radically sustainable education technology - Selwyn, Neil (Learning, Media and Technology, 2023)
This paper outlines how ideas of ‘degrowth’ might be used to reimagine sustainable forms of education technology. In essence, degrowth calls for a proactive renewal of technology use around goals of voluntary simplicity and slowing-down, community-based coproduction and sharing, alongside conscious minimalization of resource consumption. The paper considers how core degrowth principles of conviviality, commoning, autonomy and care have been used to develop various forms of ‘radically sustainable computing’. The paper then suggests four ways in which degrowth principles might frame future thinking around education technology in terms of: (i) curtailing current manipulative forms of education technology, (ii) bolstering existing convivial forms of education technology; (iii) stimulating the development of new convivial education technologies; and (iv) developing digital technologies to achieve the eventual de-schooling of society. It is concluded that mobilisation of these ideas might support a much-needed reorientation of digital technology in education along low-impact, equitable lines.
Publisher: Routledge _eprint: https://doi.org/10.1080/17439884.2022.2159978 KerkoCite.ItemAlsoKnownAs: 10.1080/17439884.2022.2159978 2339240:UK94S6MG 2405685:UUGQ439A
Keywords: Degrowth; Illich; digital; education; sustainability

The quality of translated children's literature in the Let’s Read application: Evaluating source text meaning accuracy using Angelelli's Scoring Rubric - Setiajid, Harris; Krisnarani, Natalia; Nirwinastu, Diksita Galuh (ResearchGate, 2023)
PDF | This study evaluates the translation quality of a children's story, "Dive", in the Let’s Read app using Angelelli's scoring rubric. The focus is... | Find, read and cite all the research you need on ResearchGate
KerkoCite.ItemAlsoKnownAs: 10.32996/ijllt.2023.6.7.11 2339240:W6CCCTRZ 2405685:F87Y2452

Urgent, accelerated efforts needed for universal eye coverage, vision for all: WHO - Sharma, Shamila (World Health Organization Southeast Asia, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:I2CMSQ87 2405685:72LC2G6W
Keywords: ⛔ No INSPIRE recid found

Government embracing EdTech: The case of the TeleSchool app - Sheikh, Maira; Nadeem, Umar (Tabadlab, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:P5IR25BD 2405685:SCY647ID
Keywords: ⛔ No DOI found

Independent Evaluation of the Girls’ Education Challenge Phase II – Evaluation Study 4: Educating Girls with Disabilities in GEC II - Singal, N; Niaz, Laraib; Gupta, Romanshi; Bligh, Libby; Ogando-Portela, María José; Aslam, Monazza; Rawal, Shenila (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:IVWNNMWL 2405685:NKRI4L5E

Overview of Allocation Formulas for Education Subvention in Ukraine - SKL International (2023)
Jan Herczyński “Support to Decentralization in Ukraine” SKL International 1. Education subvention in the system of public finance in...
KerkoCite.ItemAlsoKnownAs: 2339240:WNGR66GH 2405685:DUNI2UF4

Lao PDR National Education System - Southeast Asia Ministers of Education Organization (SEAMEO) Secretariat (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:NWQLT3QR 2405685:SQGKDJ2N
Keywords: ⛔ No INSPIRE recid found

Human-AI collaboration to identify literature for evidence synthesis - Spillias, Scott; Tuohy, Paris; Andreotta, Matthew; Annand-Jones, Ruby; Boschetti, Fabio; Cvitanovic, Christopher; Duggan, Joe; Fulton, Elizabeth; Karcher, Denis; Paris, Cecile (2023)
Systematic approaches to evidence synthesis can improve the rigour, transparency, and replicability of a traditional literature review. However, these systematic approaches are time and resource intensive. We evaluate the ability of OpenAI’s ChatGPT to undertake two initial stages of evidence syntheses (searching peer-reviewed literature and screening for relevance) and develop a novel collaborative framework to leverage the best of both human and AI intelligence. Using a scoping review of community-based sheries management as a case study, we nd that with substantial prompting, the AI can provide critical insight into the construction and content of a search string. Thereafter, we evaluate ve strategies for synthesising AI output to screen articles based on prede ned inclusion criteria. We nd low omission rates (< 1%) of relevant literature by the AI are achievable, which is comparable to that of human screeners. These ndings show that generalised AI tools can assist reviewers with evidence synthesis to accelerate the implementation and improve the reliability of a review.
KerkoCite.ItemAlsoKnownAs: 10.21203/rs.3.rs-3099291/v1 2405685:CCUCADRD 2486141:AHW2MJ6E
Keywords: _Added-ailr-2024

Subeb Jigawa Embarks on Digital Initiative: Capturing Lgea Staff Data Online – - State Universal Basic Education Board (Jigawa State Universal Basic Education, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:SDBTYNL8 2405685:U4QPX9SM

What Is Data Governance and Why Does It Matter? - Stedman, Craig (Data Management, 2023)
Learn what data governance is, why it's important, its benefits, who's responsible for it, data governance best practices and more in this in-depth guide.
KerkoCite.ItemAlsoKnownAs: 2405685:RVIX6BEZ

Large-scale simulation study of active learning models for systematic reviews - Teijema, Jelle Jasper; de Bruin, Jonathan; Bagheri, Ayoub; van de Schoot, Rens (2023)
The active learning methods for prioritising systematic reviews have undergone significant progress and innovation in recent years. This rapid development, however, has inadvertently highlighted the disparity between the rapid development of these methodologies and their rigorous evaluation, stemming from constraints in simulation size, lack of infrastructure, and the use of few datasets. We embark on a large-scale simulation study involving over 27 thousand simulations and over 156 million datapoints, designed to provide robust empirical evidence of active learning methodologies performance. We evaluate 13 combinations of different classification models and feature extraction techniques across high-quality datasets sourced from the SYNERGY dataset. We run a single simulation for each possible combination of selected classification model, feature extraction technique, dataset, and relevant document. The spectrum of performance varies considerably, from marginally better than random reading to near flawless results. Still, every single model-feature extraction combination outperforms random screening. Results are publicly available for analysis and replication. This study advocates for large-scale simulations as the gold standard for assessing active learning methods; it underscores the importance of comprehensive testing to reduce reporting bias and enhance result reliability. It also highlights the need for curating diverse datasets for systematic review literature.
Publisher: PsyArXiv KerkoCite.ItemAlsoKnownAs: 10.31234/osf.io/2w3rm 2405685:QH5K46LQ 2486141:PSU8KBB4
Keywords: _Added-ailr-2024

Childhood Cost Calculator (C3): User Guide. A costing tool for education and early childhood development - The Brookings Institution (Center for Universal Education at The Brookings Institution, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:Z93XE5YE 2405685:8MHTNSJ5

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
ZenodoArchiveID: 7906889 ZenodoArchiveConcept: 7906888 KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.7906875 10.5281/zenodo.7906889 10.53832/edtechhub.0163 2339240:2LWVXYCV 2405685:4CB23ZC6 2405685:AG764A26 2405685:VWJXTPI8
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Population and Housing Census 2022 - Timor-Leste National Institute of Statistics (2023)
The Population and Housing Census 2022 is the fourth census to be conducted since independence in 2002 and the first-ever digital census for Timor-Leste. The Timor-Leste National Institute of Statistics (INETL), formerly the General Directorate of Statistics, implemented the Population and Housing Census 2022 under the slogan ‘Our census, our future be part of it’.
KerkoCite.ItemAlsoKnownAs: 2339240:A44MDJQ4 2405685:E8JA424L

A meta-analysis of studies on the effects of active learning on Asian students’ performance in science, technology, engineering and mathematics (STEM) subjects - Ting, Fridolin S. T.; Shroff, Ronnie H.; Lam, Wai Hung; Garcia, Raycelle C. C.; Chan, Chi Lok; Tsang, Wing Ki; Ezeamuzie, Ndudi O. (The Asia-Pacific Education Researcher, 2023)
Document Title, Type of Document, Journal Name and References fields. The selection of keywords in the Scopus database was critical to our meta-analytic analysis since the keywords directly influenced the amount of data that was retrieved. Different active learning pedagogies and treatments were extracted from those included in Freeman’s meta-analysis, and keywords were used in a comprehensive search for titles and abstracts in Scopus to narrow down literature related to active learning.
5 citations (Crossref) [2024-04-17] KerkoCite.ItemAlsoKnownAs: 10.1007/s40299-022-00661-6 2339240:TYKSA6TA 2405685:AGLZE3BJ
Keywords: ⛔ No INSPIRE recid found

Pandemic pedagogy conceptualizations of university students during emergency remote education - Toquero, Cathy Mae Dabi; Toquero, Joel Paco (Mediterranean Journal of Social & Behavioral Research, 2023)
During the spike of the global health crisis, literature has conceived pandemic pedagogy in a broad sense of meaning based on pedagogical assumptions. Few studies explore the conceptualizations of students regarding pandemic pedagogy. Based on state university students’ reflections and insights during emergency remote learning, this study examined pandemic pedagogy through the content analysis of 37 learning modules. The student teachers conceptualize pandemic pedagogy as encompassing six approaches to mitigate learning during emergency remote education in the context of the Philippines. Pandemic pedagogy encapsulates the pedagogical concepts of personalized learning, human centered pedagogy, pedagogy of care, active learning pedagogy, game-based learning, and contextualized online pedagogy. Through a better understanding of how students choose to learn, teachers can improve online course plans to sustain students’ engagement in emergency online or remote learning.
Publisher: Bastas KerkoCite.ItemAlsoKnownAs: 10.30935/mjosbr/13403 2339240:9TEL5NRB 2405685:KCBYYLHK

Non-Regulatory Guidance: Using Evidence to Strengthen Education Investments - U.S. Department of Education (Department for Education, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:2RD8XYP8 2405685:2S4YRDXC

DigitALL: Innovation and technology for gender equality in Viet Nam - UN Resident Coordinator's Office; UN Women Viet Nam (UN Women Viet Nam, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:VHKBC4AA 2405685:X72GJ7D9

Independent Country Programme Evaluation – Cambodia - UNDP (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:7YATNZFX 2405685:YK57R5YE

2023 Global Education Monitoring Report - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:ECQUWCGL 2405685:K3KHG3I8

An Ed-Tech Tragedy? Educational technologies and school closures in the time of COVID-19 - UNESCO (United Nations Educational, Scientific and Cultural Organization (UNESCO), 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:5U643BBF 2405685:2U4WRAJU

Basic Education Equivalency Programme (BEEP) - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:IIZQ47BY 2405685:JZNL3WVY

Cameroon | Technology | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:L3E2LANV 2405685:QE6D578N

Comores | Technologie | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:32E643W9 2405685:GBYEAM3C

Côte d’Ivoire | Technologie | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:43HRRSK2 2405685:BQM7PQFN

Education in Ukraine: Over $51 million in grants and in-kind support - UNESCO (2023)
As the war continues in Ukraine, severely disrupting education, the Global Partnership for Education (GPE), Google, Microsoft Corporation and UNESCO will provide over US$51 million for distance
KerkoCite.ItemAlsoKnownAs: 2339240:7ICL4U65 2405685:XH55HLYJ

Education in Ukraine: UNESCO mobilizes US$12 million to step up its action on the ground - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:X8FT7PYE 2405685:I3HSFKTW

Eritrea | Technology | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:BVIUTANS 2405685:PEWAHUDZ

Gabon | Technologie | Education Profiles - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:PE9UP4I8 2405685:MT9U7UWD

Global Education Monitoring Report 2023, Southeast Asia: Technology in education: A tool on whose Terms? - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:4VJ9EU2N 2339240:E8ZGUYFI 2339240:EJ68N2Y9 2339240:L87JJPJZ 2339240:Z4QTVM9P 2405685:2XRYSW93 2405685:4RSN6K3Q 2405685:DLCVX3ZD 2405685:QH4H9WNX 2405685:TZGBVL5R 2405685:XV7PXR7J
Keywords: ⛔ No INSPIRE recid found

Global Education Monitoring Report 2023: Technology in Education: A tool on whose terms? - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:5RJYHALW 2339240:WLDUAVSG 2405685:BMFQI9CG 2405685:W5352YJ5

Guinea Ecuatorial | Tecnología | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:N7NRN3ZH 2405685:K3IWGYRN

Guinée | Technologie | Education Profiles - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:2IQHAW5P 2405685:WT42DJG9

Mauritanie | Technologie | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:UX3DNTLN 2405685:AXSFRRG7

Mozambique | Technology | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:QGBPDHE8 2405685:X6MFPSY4

Namibia | Technology | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:S5HSX4CW 2405685:4QD96WEE

Nigeria | Technology | Education Profiles - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:8DC6MTFL 2405685:HRYISUM3

République centrafricaine | Technologie | Education Profiles - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:XYQLTSRU 2405685:UPL88NXL

République Démocratique du Congo | Technologie | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:UFHCPKEK 2405685:8YECZSY9

São Tomé and Príncipe | Technology | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:9BJ8S8YQ 2405685:AIVXTUJF

SDG 4 September 2023 - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:62TKMKGR

Sénégal | Technologie | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:489788Y9 2405685:WJ9JVQX5

South Sudan | Technology | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:YM9SZ24G 2405685:SIHAYPMH

Strengthening resilience of education system in Ukraine for emergency response and recovery - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:3JKVSFL2 2405685:L4RF84PJ

Tchad | Technologie | Education Profiles - UNESCO (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:M4URZ2B7 2405685:BGUZE96P

Ukraine: UNESCO mobilizes support for learning continuity - UNESCO (2023)
UNESCO is mobilizing support to maintain continuity of education and to help teachers and learners in Ukraine. Through its Global Education Coalition, the Organization will provide computer hardware
KerkoCite.ItemAlsoKnownAs: 2339240:KGD5UWJB 2405685:XGARJ3ZW

UNESCO laureate Room to Read Cambodia helps girls stay in school - UNESCO (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:WAASFV2G 2405685:U3I44G64

Technology in Education: A Case Study on Timor-Leste - UNESCO Global Education Monitoring Report Team; SEAMEO Regional Centre for Quality Improvement for Teacher and Education Personnel in Science (UNESCO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:2WMNVB74 2405685:TXI2CPWV

Technology in Disability-Inclusive Education - UNESCO Global Education Monitoring Report Team; SEAMEO Regional Centre for Special Educational Needs (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:WISL429K 2405685:U9RHMCM3
Keywords: ⛔ No INSPIRE recid found

Conceptual Framework for Education in Emergencies Data - UNESCO-IIEP (International Institute for Educational Planning, 2023)
KerkoCite.ItemAlsoKnownAs: 2405685:493VUCUL

Data for Education. a Guide for Policymakers to Leverage Education Data - UNESCO Institute for Statistics (UIS, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:D6W74EL9 2405685:BJV962J3

Asia-Pacific regional synthesis: climate change, displacement and the right to education - UNESCO Digital Library - UNESCO; UNESCO Multisectoral Regional Office in Bangkok; United Nations University Institute for the Advanced Study of Sustainability (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:B3G7KR9I 2405685:YZFBUIXS

Principles of Digital Learning for Refugee-host Communities - UNHCR; UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:GC9THSKP 2405685:J53RTAAC

46 million school-aged children out of school across Eastern and Southern Africa | UNICEF Eastern and Southern Africa - UNICEF (2023)
Education in emergencies is a human right yet millions of children are denied access to learning
KerkoCite.ItemAlsoKnownAs: 2339240:HI52N43L 2405685:DMPY5HDS
Keywords: ⛔ No INSPIRE recid found

Digital learning tools open a world of possibilities for ethnic minority girls in remote Viet Nam - UNICEF (2023)
Digital learning tools open a world of possibilities for ethnic minority girls in remote Viet Nam
KerkoCite.ItemAlsoKnownAs: 2405685:99EWNUUI

Federal Ministry of Education and UNICEF Celebrate 500,000 Registered Users on the Nigeria Learning Passport - UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:PUHN9YN7 2405685:IHKLX2ZC

Harnessing the Transformative Potential of Education for Climate Change Mitigation, Adaptation and Resilience Building in Europe and Central Asia - UNICEF (UNICEF Europe and Central Asia (ECA), 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:YFA74E4I 2405685:WLSBB8EQ

Humanitarian Action for Children: Ukraine and refugee response. Revision 1 - UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:YPTAFSTX 2405685:M3SN2XEE

Humanitarian Action for Children: Ukraine and refugee response. Revision 2 - UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:M2YBMAAM 2405685:ATED7BMU

Lao Peoples Democratic Republic 2023: Country Office Annual Report - UNICEF (UNICEF, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:JW6NSTVA 2405685:PKE4GWZP
Keywords: ⛔ No INSPIRE recid found

NIGERIA Country Programme 2023-2027 - UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:ZCK3IHWW 2405685:GIFTD5G7

Transforming Education with Equitable Financing - UNICEF (UNICEF, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:4YHEX9SQ 2405685:48BJTSEZ

Ukraine Humanitarian Situation Report No. 26 - UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:WB2DV8C8 2405685:GVDWMYTZ

UNICEF Data Warehouse - UNICEF (2023)
KerkoCite.ItemAlsoKnownAs: 2405685:8ZJYGFWF

Girls’ Digital Literacy in the East Asia and Pacific Region: Spotlight on Cambodia, Indonesia, Lao PDR, Timor-Leste and Vietnam - UNICEF East Asia and Pacific Regional Office (EAPRO) (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:TU368GB2 2405685:AYVJESPV
Keywords: ⛔ No INSPIRE recid found

Girls’ Digital Literacy in the East Asia and Pacific Region: Spotlight on Cambodia, Indonesia, Lao PDR, Timor-Leste and Viet Nam - UNICEF East Asia and the Pacific Regional Office (UNICEF EAPRO, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:FYMA9R75 2405685:Y5U6K9T3
Keywords: ⛔ No INSPIRE recid found

Gateways to Public Digital Learning - United Nations (United Nations, 2023)
Publisher: United Nations KerkoCite.ItemAlsoKnownAs: 2339240:SAJHETWJ 2405685:2P8S8N6F

World Population Dashboard Cambodia - United Nations Fund for Population Activities (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:589WI5HI 2405685:5J7TCHIB

All Children Reading: A Grand Challenge for Development – Final Report - USAID (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:8YBAE6L9 2405685:RWC4U47Y
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

Coaching & mentoring report Tz Jifunze Uelewe 2023 - USAID (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:YP2KC2IL 2405685:2WPHNISK

Vietnam Innovation & Tech Investment Report 2023 - Vietnam National Innovation Center (Vietnam National Innovation Center, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:QPFU5P4Y 2405685:FPXGK75X

Cambodia - TED: Strengthening teacher trainers through blended trainings - VVOB (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:FK29ZH6H 2405685:8HQ39DNJ

An exploratory investigation into the factors related to EdTech use among Kenyan girls - Watson, Joe; Baier, Jasmin; Mughogho, Winnie; Millrine, Mark (British Journal of Educational Technology, 2023)
This paper contributes to the scarce literature on factors affecting EdTech use in households. These factors were considered through exploratory mixed-methods analyses of cross-sectional data on Kenyan girls and caregivers, captured during the COVID-19 pandemic. Quantitative analysis of the child dataset (n = 544) suggested the importance of both structural factors—such as technology hardware availability—and non-structural factors—including caregiver permission. Findings were supported by a thematic analysis of interview data from girls' caregivers (n = 58), which emphasised the role they play in girls' use of EdTech. Interviews also highlighted numerous caregiver concerns with EdTech, related to the relevance and rigour of educational content, the possibility of children accessing age-inappropriate material and child health (especially eyesight). Policy makers could alleviate these concerns by providing guidance on EdTech use and clearly signalling their approval of verified initiatives. Practitioner notes What is already known about this topic EdTech can benefit girls' education, yet there are various barriers to it being used. Existing research shows clearly that EdTech use can be impeded by structural factors (eg, hardware ownership). However, we find insufficient empirical evidence on the role of non-structural or behavioural factors. What this paper adds This paper addresses this gap, using a mixed-methods approach to explore the influence of 33 different measures (including non-structural factors) that could affect the number of hours girls spend using EdTech at home. Findings from a quantitative sample of girls (n = 544) and a qualitative sample of girls' caregivers (n = 58) highlighted the importance of non-structural factors, especially caregiver permission. The variable most strongly associated with girls' EdTech usage in our selected quantitative model concerned whether this was sanctioned by their caregivers. Our qualitative data suggested why caregiver permission to use EdTech might be withheld: caregivers emphasised perceived concerns about the risks and rigour of EdTech. Implications for practice and/or policy Our findings suggest the viability of policy interventions that provide EdTech guidance to caregivers. Caregivers uncertain about EdTech could be reassured of the appropriateness of verified initiatives, while those already convinced might be aided in their attempts to support EdTech learning. Such guidance could provide a low-cost means of further exploiting the benefits that household EdTech learning can provide.
1 citations (Crossref) [2024-02-28] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/bjet.13307 KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13307 2339240:Q94ZI2GS 2405685:W4VSMH86
Keywords: COVID-19; EdTech; Kenya; caregivers; girls' education; ⛔ No INSPIRE recid found

An exploratory investigation into the factors related to EdTech use among Kenyan girls - Watson, Joe; Baier, Jasmin; Mughogho, Winnie; Millrine, Mark (British Journal of Educational Technology, 2023)
This paper contributes to the scarce literature on factors affecting EdTech use in households. These factors were considered through exploratory mixed-methods analyses of cross-sectional data on Kenyan girls and caregivers, captured during the COVID-19 pandemic. Quantitative analysis of the child dataset (n = 544) suggested the importance of both structural factors—such as technology hardware availability—and non-structural factors—including caregiver permission. Findings were supported by a thematic analysis of interview data from girls' caregivers (n = 58), which emphasised the role they play in girls' use of EdTech. Interviews also highlighted numerous caregiver concerns with EdTech, related to the relevance and rigour of educational content, the possibility of children accessing age-inappropriate material and child health (especially eyesight). Policy makers could alleviate these concerns by providing guidance on EdTech use and clearly signalling their approval of verified initiatives.
KerkoCite.ItemAlsoKnownAs: 10.1111/bjet.13307 2339240:WEWKJFWR 2405685:W8HYZ879

Factors associated with attention deficit hyperactive disorder in school-age Thai children - Weerakul, Jiranun; Patigburt, Pakakrong (Journal of the Medical Association of Thailand, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:LERK58WL 2405685:9RVEGQ5T
Keywords: ⛔ No DOI found; ⛔ No INSPIRE recid found

An Ed-Tech Tragedy? Educational Technologies and School Closures in the Time of COVID-19 - West, Mark (UNESCO Digital Library, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:5BJFU66N 2405685:8ZYQZDCC
Keywords: ⛔ No INSPIRE recid found

Teacher Development Multi-Year Study Series. Evaluation of Australia’s investment in teacher development in Lao PDR. Final report - Wong, Debbie; Hollingsworth, Hilary; Anderson, Prue; Goundar, Payal; Mercer, Agnes (Australian Council for Educational Research, 2023)
The Australian Government is supporting the Government of Lao PDR to undertake significant primary education reforms through its flagship Basic Education Quality and Access in Lao PDR program (BEQUAL). A key focus of these reforms is the rollout of a new national primary curriculum intended to improve teaching quality and learning outcomes for students. As part of a multi-year study series, the Education Analytics Service (EAS) investigated how the BEQUAL program made a difference to improving these teaching and learning outcomes.
KerkoCite.ItemAlsoKnownAs: 10.37517/978-1-74286-728-1 2339240:W8CVIUCN 2405685:SAK8WE7Q
Keywords: ⛔ No INSPIRE recid found

Children Out of School in Cambodia - World Bank (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:ALJSI95V 2405685:6RQA27BK

Education and Technology Readiness Index (ETRI) - World Bank (World Bank, 2023)
The ETRI webpage describes the EdTech Readiness Index, its global context and potential uses, how ETRI can be implemented, where it has been piloted, useful resources (e.g., videos, podcasts, technical note, toolkit, and indicators), and the ETRI team.
KerkoCite.ItemAlsoKnownAs: 2339240:NWKQLVFE 2405685:JL9W9EHV

Human Capital Country Brief Ghana - World Bank (World Bank, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:3HFIBJCH 2405685:P6EK2X2R

Mozambique Energy For All (ProEnergia) - World Bank (World Bank, 2023)
Development Projects : Mozambique Energy For All (ProEnergia) - P165453
KerkoCite.ItemAlsoKnownAs: 2339240:SS9I9V2L 2405685:MH2KZZZP
Keywords: ⛔ No INSPIRE recid found

South Africa Public Expenditure and Institutional Review for Early Childhood Development - World Bank (2023)
South Africa Public Expenditure and Institutional Review for Early Childhood Development (ECD PEIR) (English)
KerkoCite.ItemAlsoKnownAs: 2339240:TLMPZ4F7 2405685:QQVW5HWF

The World Bank in Eastern and Southern Africa: Development news, research, data - World Bank (World Bank, 2023)
Home to about 700 million of Africa’s people, the World Bank’s Eastern and Southern Africa Region is a geographically, culturally and economically diverse region of 26 countries stretching from the Red Sea in the North to the Cape of Good Hope in the South.
KerkoCite.ItemAlsoKnownAs: 2339240:WHSAUIK2 2405685:P7WT2Z5S
Keywords: ⛔ No INSPIRE recid found

World Bank Data Bank: Population in Cambodia - World Bank (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:3F9N2TNZ 2405685:VXFC8SDJ

World Bank Open Data - World Bank (World Bank Open Data, 2023)
Free and open access to global development data
KerkoCite.ItemAlsoKnownAs: 2339240:W3PW6XRL 2405685:C3DL958R

Global Gender Gap Report 2023 - World Economic Forum (2023)
The Global Gender Gap Index annually benchmarks the current state and evolution of gender parity across four key dimensions (Economic Participation and Opportunity, Educational Attainment, Health and Survival, and Political Empowerment). It is the longest-standing index tracking the progress of numerous countries’ efforts towards closing these gaps over time since its inception in 2006.
KerkoCite.ItemAlsoKnownAs: 2405685:P5NWGCS2

In some Southeast Asian markets, more than one in five of smartphone users connect to the Internet only on mobile networks | Opensignal - Wyrzykowski, Robert (2023)
In the latest regional benchmark analysis Opensignal looks at the proportions of smartphone users in ten Southeast Asian markets, who rarely or never connect to Wi-Fi services. The analysis shows a diverse picture between Southeast Asian markets — the percentage of mobile-only users ranges from less than 10% of total smartphone users in countries like Vietnam, Brunei, or the Philippines, to more than a quarter in markets like East Timor, Laos, Thailand or Malaysia.
KerkoCite.ItemAlsoKnownAs: 2339240:QKC3W4U3 2405685:R59VY689
Keywords: ⛔ No INSPIRE recid found

Using Education Technology to Improve K-12 Student Learning in East Asia Pacific: Promises and Limitations - Yarrow, Noah; Alyono, Kevin; Shen, Sharon (World Bank Group, 2023)
KerkoCite.ItemAlsoKnownAs: 2339240:5U9N8CQL 2405685:JNTXSVTG
Keywords: ⛔ No INSPIRE recid found

Government policies to evaluate edtech in Africa - Zelezny-Green, Ronda; Metcalfe, Hannah (2023)
KerkoCite.ItemAlsoKnownAs: 2339240:W6ZIXXD7 2405685:W2KC8XG5